Electricity storage system
By using a positive electrode active substance that can maintain a reversible change in the crystal structure under a high charging voltage in the charger, detecting and controlling the changes in the crystal structure of the positive electrode active substance, the problem of insufficient energy density and safety of secondary batteries in the prior art is solved. , realizes a secondary battery with high energy density and long life.
Patent Information
- Application Number
- CN202380047905.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-08
- Filing Date
- 2023-06-30
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to realize lithium-ion secondary batteries with high energy density and high safety, especially during the charging and discharging process, and abnormalities such as overdischarge, overcharge, overcurrent or short circuit are prone to occur, affecting the life and safety of the battery.
By using a positive electrode active material that can maintain a reversible change in the crystal structure under a high charging voltage in the charger, the crystal structure changes of the positive electrode active material are detected and controlled, thereby optimizing the charging and discharging process of the secondary battery.
The high energy density and long life of the secondary battery are achieved, while improving the safety of the battery, avoiding battery deterioration and safety risks caused by overcharge and discharge.
Smart Images

Figure CN119422269A_ABST
Abstract
Description
Technical Field
[0001] One embodiment of the present invention relates to a power storage system, a method for operating the power storage system, a secondary battery, and a method for operating the secondary battery. In addition, one embodiment of the present invention relates to a method for charging a secondary battery. In addition, one embodiment of the present invention relates to a semiconductor device and a method for operating the semiconductor device. In addition, one embodiment of the present invention relates to a battery control circuit, a battery protection circuit, a power storage device, an electronic device, and methods for operating the same.
[0002] Note that one embodiment of the present invention is not limited to the above-mentioned technical field. The technical field of one embodiment of the invention disclosed in this specification, etc., relates to an object, a method, a driving method, or a manufacturing method. In addition, one embodiment of the present invention relates to a process, a machine, a product, or a composition of matter. Therefore, specifically, as an example of the technical field of one embodiment of the present invention disclosed in this specification, etc., semiconductor devices, display devices, light-emitting devices, power storage devices, optical devices, camera devices, lighting devices, computing devices, control devices, storage devices, input devices, output devices, input-output devices, signal processing devices, electronic computers, electronic devices, their driving methods, or their manufacturing methods can be cited. Background Art
[0003] In recent years, the development of various power storage devices (also called batteries or secondary batteries) such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries or all-solid-state batteries has become increasingly popular. In particular, with the development of the semiconductor industry, the demand for high-output and high-capacity lithium-ion secondary batteries has increased dramatically, and as a rechargeable energy supply source, it has become a necessity in the modern information society.
[0004] Power storage devices are used in various fields such as small electronic devices and automobiles. As the application range of batteries expands, the application of battery stacks using a multi-cell structure in which a plurality of battery cells are connected in series has increased.
[0005] The power storage device is equipped with a circuit for detecting abnormalities during charging and discharging, such as over-discharging, over-charging, over-current, or short-circuiting. In such a circuit, data such as voltage and current are obtained, and the data is used to control the stop of charging and discharging or battery balancing. In this way, the battery can be protected and controlled.
[0006] Patent Document 1 discloses a protection IC used as a battery protection circuit. Specifically, Patent Document 1 discloses a protection IC that has a plurality of comparators therein and detects abnormalities during charging and discharging by comparing a reference voltage with a voltage at a terminal connected to a battery.
[0007] Furthermore, Patent Document 2 discloses a battery state detection device for detecting a micro short circuit (also referred to as an internal short circuit or a micro short circuit) of a secondary battery and a battery pack incorporating the same.
[0008] Furthermore, Patent Document 3 discloses a protective semiconductor device for protecting a battery pack including secondary battery cells connected in series.
[0009] Furthermore, the various circuits for detecting abnormalities during charge and discharge of the secondary battery and protecting and controlling the battery, and the various integrated circuits (ICs) including the circuits are also semiconductor devices formed using transistors.
[0010] As semiconductor materials that can be used for transistors, silicon-based semiconductors are widely known. As other materials, oxide semiconductors have attracted attention. It is known that the off-state current of a transistor using an oxide semiconductor is extremely small in a non-conducting state. For example, Patent Documents 4 and 5 disclose a central processing unit (CPU) that can reduce power consumption by applying the very small off-state current characteristic of a transistor using an oxide semiconductor and a storage device that can retain stored content for a long time.
[0011] For example, secondary batteries for portable electronic devices are required to have a large discharge capacity per unit weight and high cycle characteristics. In order to meet these requirements, improvements are being actively made to the positive electrode active material contained in the positive electrode of the secondary battery. In addition, research on the crystal structure of the positive electrode active material has been conducted (Non-Patent Documents 1 and 2).
[0012] In addition, XRD (X-ray Diffraction) pattern is one of the methods for analyzing the crystal structure of the positive electrode active material. For example, by using ICSD (Inorganic Crystal Structure Database) introduced in Non-Patent Document 3, XRD data can be analyzed. In the analysis using the Rietveld method, for example, the analysis program RIETAN-FP (Non-Patent Document 4) can be used.
[0013] As image processing software, for example, ImageJ is known (Non-Patent Documents 5 to 7). By using this software, for example, the shape of the positive electrode active material can be analyzed.
[0014] [Prior technical literature]
[0015] [Patent Document]
[0016] [Patent Document 1] U.S. Patent Application Publication No. 2011-267726
[0017] [Patent Document 2] Japanese Patent Application Publication No. 2010-66161
[0018] [Patent Document 3] Japanese Patent Application Publication No. 2010-220389
[0019] [Patent Document 4] Japanese Patent Application Publication No. 2012-257187
[0020] [Patent Document 5] Japanese Patent Application Publication No. 2011-151383
[0021] [Non-patent literature]
[0022] [Non-patent document 1] Motohashi, T. et al., "Electronic phase diagram of the layered cobalt oxide system LixCoO2 (0.0≤x≤1.0)", Physical Review B, 80(16); 165114
[0023] [Non-patent document 2] Zhaohui Chen et al., "Staging Phase Transitions in LixCoO2", Journal of The Electrochemical Society, 2002, 149(12)A1604-A1609
[0024] [Non-patent document 3] Belsky, A. et al., "New developments in the InorganicCrystal Structure Database (ICSD): accessibility in support of materials research and design", Acta Cryst., (2002) B58 364-369.
[0025] [Non-patent document 4] F. Izumi and K. Momma, Solid State Phenom., 130, 15-20 (2007)
[0026] [Non-patent document 5] Rasband, WS, ImageJ, USNational Institutes of Health, Bethesda, Maryland, USA, http: / / rsb.info.nih.gov / ij / , 1997-2012.
[0027] [Non-patent document 6] Schneider, CA, Rasband, WS, Eliceiri, KW "NIH Image to ImageJ: 25 years of image analysis". Nature Methods 9, 671-675, 2012.
[0028] [Non-patent document 7] Abramoff, MD, Magelhaes, PJ, Ram, SJ "Image Processing with ImageJ". Biophotonics International, volume 11, issue 7, pp. 36-42, 2004. Summary of the invention
[0029] Technical problem to be solved by the invention
[0030] One of the purposes of one embodiment of the present invention is to provide a power storage system with high energy density. Another purpose of one embodiment of the present invention is to provide a power storage system with high safety. Another purpose of one embodiment of the present invention is to provide a charging method for a power storage system with high energy density. Another purpose of one embodiment of the present invention is to provide a charging method for a power storage system with high safety. Another purpose of one embodiment of the present invention is to provide a secondary battery with high energy density. Another purpose of one embodiment of the present invention is to provide a secondary battery with high safety. Another purpose of one embodiment of the present invention is to provide a novel charging method for a secondary battery. Another purpose of one embodiment of the present invention is to provide a power storage system using a highly reliable positive electrode active material. Another purpose of one embodiment of the present invention is to provide a highly reliable positive electrode active material. Another purpose of one embodiment of the present invention is to provide an excellent power storage system by using a positive electrode active material of one embodiment of the present invention in a power storage system of one embodiment of the present invention. Another purpose of one embodiment of the present invention is to estimate the state of a secondary battery. Another purpose of one embodiment of the present invention is to estimate the depth of charge of a secondary battery. Another purpose of one embodiment of the present invention is to estimate the deterioration state of a secondary battery by estimating the fully chargeable capacity of a secondary battery. Another purpose of one embodiment of the present invention is to estimate the dischargeable capacity of a secondary battery.
[0031] In addition, one of the purposes of one embodiment of the present invention is to provide a novel charger, charging control circuit, battery control circuit, battery protection circuit, power storage device, semiconductor device, vehicle, electronic device, etc. In addition, one of the purposes of one embodiment of the present invention is to provide a charger, charging control circuit, battery control circuit, battery protection circuit, power storage device, semiconductor device, vehicle, electronic device, etc. with low power consumption. In addition, one of the purposes of one embodiment of the present invention is to provide a charger, charging control circuit, battery control circuit, battery protection circuit, power storage device, semiconductor device, vehicle, electronic device, etc. with high integration.
[0032] Note that the purpose of one embodiment of the present invention is not limited to the above-mentioned purpose. The above-mentioned purpose does not prevent the existence of other purposes. In addition, other purposes are purposes that are not mentioned above but will be described in the following description. Those skilled in the art can derive and appropriately extract the purposes not mentioned above from the description of this specification or the drawings, etc. Note that one embodiment of the present invention achieves at least one of the above-mentioned purpose and other purposes.
[0033] Solutions to technical problems
[0034] The charger of one embodiment of the present invention can be particularly suitably used in combination with a secondary battery using a positive electrode active material of one embodiment of the present invention. The charger of one embodiment of the present invention has the following function: by measuring the charging voltage and charging current of the secondary battery and analyzing the measured charging voltage and charging current, the change of the crystal structure of the positive electrode active material of one embodiment of the present invention during the charging process is detected.
[0035] In a secondary battery, the discharge capacity can be increased by increasing the charging voltage to a limit during repeated charge and discharge. In addition, in order to realize a secondary battery with a long life, it is preferred that the crystal structure of the positive electrode active material also changes roughly reversibly under the increased charging voltage. A charging method in one embodiment of the present invention is a charging method, in which the collapse of the crystal structure of the positive electrode active material during charging is suppressed because the crystal structure of the positive electrode active material changes roughly reversibly, thereby realizing a secondary battery with a large discharge capacity and a long life.
[0036] In the positive electrode active material of one embodiment of the present invention, the crystal structure of the positive electrode active material can also be substantially reversibly changed under the increased charging voltage. The charger of one embodiment of the present invention has the following function: by appropriately using the positive electrode active material of one embodiment of the present invention for a secondary battery, the charger of one embodiment of the present invention detects the change of the crystal structure of the positive electrode active material within the range where the charging voltage is high and the crystal structure substantially reversibly changes, thereby controlling the charging.
[0037] The positive electrode active material of one embodiment of the present invention changes from an O3 type crystal structure to an O3' type crystal structure described later. In addition, the change in crystal structure occurs when the depth of charge of the secondary battery is large. The charger of one embodiment of the present invention has a function of detecting the change from the O3 type crystal structure to the O3' type crystal structure to control charging. (1)
[0039] One embodiment of the present invention is a power storage system including a secondary battery and a differentiator, wherein the differentiator includes a register, the differentiator has a function of converting a first voltage of the secondary battery into first voltage data by analog-to-digital conversion, the differentiator has a function of measuring the time required for the first voltage to change by a first voltage value, the register has a function of storing second voltage data having a data value higher than the first voltage data and corresponding to the first voltage value, and the differentiator has a function of stopping the supply of power to the register during the period until the first voltage changes by the first voltage value. (2)
[0041] In addition, in the above (1), the differentiator may also include a digital-to-analog conversion circuit, the digital-to-analog conversion circuit may also have a function of outputting a second voltage based on second voltage data, and the differentiator may also have a function of stopping the supply of power to the digital-to-analog conversion circuit during the period until the first voltage changes to the first voltage value. (3)
[0043] In the above (1), the differential device may include a transistor including an oxide semiconductor in a channel formation region. (4)
[0045] In the above (2), the differential device may include a transistor including an oxide semiconductor in a channel formation region. (5)
[0047] Furthermore, in any one of (1) to (4) above, it is preferred that the secondary battery includes a positive electrode, the positive electrode contains lithium cobalt oxide, and a crystal structure identified by X-ray diffraction is a crystal structure represented by space group R-3m. (6)
[0049] Furthermore, in the above (5), the lithium cobalt oxide may contain magnesium in the surface layer portion.
[0050] Effects of the Invention
[0051] According to one embodiment of the present invention, a power storage system with high energy density can be provided. In addition, according to one embodiment of the present invention, a power storage system with high safety can be provided. In addition, according to one embodiment of the present invention, a secondary battery with high energy density can be provided. In addition, according to one embodiment of the present invention, a secondary battery with high safety can be provided. In addition, according to one embodiment of the present invention, a novel charging method for a secondary battery can be provided. In addition, according to one embodiment of the present invention, a power storage system using a positive electrode active material with high reliability can be provided. In addition, according to one embodiment of the present invention, a positive electrode active material with high reliability can be provided. In addition, according to one embodiment of the present invention, an excellent power storage system can be provided by using the positive electrode active material of one embodiment of the present invention in the power storage system of one embodiment of the present invention. In addition, according to one embodiment of the present invention, the state of the secondary battery can be estimated. In addition, according to one embodiment of the present invention, the depth of charge of the secondary battery can be estimated. In addition, according to one embodiment of the present invention, the capacity of the secondary battery that can be fully charged can be estimated to estimate the degradation state of the secondary battery. In addition, according to one embodiment of the present invention, the capacity of the secondary battery that can be discharged can be estimated.
[0052] In addition, according to one embodiment of the present invention, a novel charger, a charging control circuit, a battery control circuit, a battery protection circuit, a power storage device, a semiconductor device, a vehicle, an electronic device, etc. can be provided. In addition, according to one embodiment of the present invention, a charger, a charging control circuit, a battery control circuit, a battery protection circuit, a power storage device, a semiconductor device, a vehicle, an electronic device, etc. with low power consumption can be provided. In addition, according to one embodiment of the present invention, a charger, a charging control circuit, a battery control circuit, a battery protection circuit, a power storage device, a semiconductor device, a vehicle, an electronic device, etc. with high integration can be provided.
[0053] Note that the effects of one embodiment of the present invention are not limited to the effects listed above. The effects listed above do not prevent the existence of other effects. Other effects are effects that are recorded below and are not described above. Those skilled in the art can derive and appropriately extract the effects that are not described above from the description of this specification or the drawings, etc. Note that one embodiment of the present invention has at least one of the effects listed above and other effects. Therefore, one embodiment of the present invention sometimes does not have the effects listed above. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1A and Figure 1B This is a block diagram showing an example of a power storage system.
[0055] Figure 2A and Figure 2B This is a block diagram showing an example of a power storage system.
[0056] Figure 3A and Figure 3B This is a block diagram showing an example of a power storage system.
[0057] Figure 4A and Figure 4B This is a block diagram showing an example of a power storage system.
[0058] Figure 5 This is a flowchart illustrating a method for charging a secondary battery.
[0059] Figure 6 This is a flowchart illustrating a method of charging a secondary battery.
[0060] Figure 7 is a flowchart showing a method of charging a secondary battery.
[0061] Figure 8 is a block diagram showing a configuration example of a power storage system.
[0062] Fig. 9 : is a flowchart showing an operation example of the power storage system.
[0063] Fig.10 is a block diagram showing a configuration example of a power storage system.
[0064] Fig.11 Schematic diagram showing an operation example of the power storage system.
[0065] Fig.12 This is a flowchart illustrating an operation example of the power storage system.
[0066] FIG. 13A to FIG. 13C This is a block diagram showing an example of a power storage system.
[0067] Fig.14A and Fig. 14B It is a cross-sectional view of the positive electrode active material. FIG. 14C to FIG. 14F This is a part of the cross-sectional view of the positive electrode active material.
[0068] Fig.15 This is an example of a TEM image where the crystal orientation is roughly uniform.
[0069] Fig.16A This is an example of a STEM image where the crystal orientation is roughly uniform. Fig. 16B It is the FFT pattern of the region of the rock salt type crystal structure RS. Fig. 16C It is the FFT pattern of the region of layered rock salt type crystal structure LRS.
[0070] Fig.17 It is a diagram illustrating the crystal structure of the positive electrode active material.
[0071] Fig.18 This is a diagram illustrating the crystal structure of a conventional positive electrode active material.
[0072] Fig.19A and Fig.19B It is a cross-sectional view of the positive electrode active material. Fig.19C and Fig.19D This is a part of the cross-sectional view of the positive electrode active material.
[0073] Fig. 20 It is a figure which shows the XRD pattern calculated from the crystal structure.
[0074] Fig.21 It is a figure which shows the XRD pattern calculated from the crystal structure.
[0075] Fig. 22 It is a cross-sectional view of the positive electrode active material.
[0076] FIG. 23A to FIG. 23C It is a diagram for explaining a method for producing a positive electrode active material.
[0077] FIG. 24A to FIG. 24H It is a diagram for explaining an example of an electronic device.
[0078] FIG. 25A to FIG. 25D It is a diagram for explaining an example of an electronic device.
[0079] FIG. 26A to FIG. 26C It is a diagram for explaining an example of an electronic device.
[0080] FIG. 27A to FIG. 27C It is a diagram for explaining an example of a vehicle.
[0081] Fig.28A and Fig.28B The dQ / dV-V curve is shown.
[0082] Fig.29A and Fig.29B The dQ / dV-V curve is shown.
[0083] Fig. 30A The VC curve is shown. Fig. 30B A ΔV-t curve is shown.
[0084] Fig.31 The evaluation results of the cycle characteristics of the secondary batteries are shown.
[0085] Fig.32 It is a graph showing the relationship between the number of charge and discharge cycles and the charge end voltage.
[0086] FIG. 33A to FIG. 33C The dQ / dV-V curve of the secondary battery is shown.
[0087] Fig.34A and Fig.34B The dQ / dV-V curve of the secondary battery is shown. DETAILED DESCRIPTION
[0088] In this specification, etc., a semiconductor device refers to a device that utilizes semiconductor characteristics, for example, a circuit including a semiconductor element (for example, a transistor or a diode, etc.) or a device including the circuit, etc. In addition, a semiconductor device refers to all devices that can function by utilizing semiconductor characteristics. For example, as examples of semiconductor devices, there are integrated circuits including semiconductor elements, chips including integrated circuits, electronic components containing chips in packages, or electronic devices equipped with electronic components, etc. In addition, for example, display devices, light-emitting devices, power storage devices, optical devices, camera devices, lighting devices, computing devices, control devices, storage devices, input devices, output devices, input-output devices, signal processing devices, electronic computers or electronic devices, etc., are themselves semiconductor devices, and sometimes include semiconductor devices.
[0089] Hereinafter, the embodiments are described with reference to the accompanying drawings. Note that the embodiments can be implemented in a plurality of different forms. Thus, a person skilled in the art can easily understand that the methods and details can be transformed into various forms without departing from the purpose and scope thereof. Therefore, the present invention should not be interpreted as being limited to the contents described in the embodiments.
[0090] In addition, in this specification, the structure shown in each embodiment can be appropriately combined with the structure shown in other embodiments to constitute one mode of the present invention. In addition, when multiple structures are shown in one embodiment, these structures can be appropriately combined and regarded as one mode of the present invention.
[0091] Note that with respect to the drawings illustrating the embodiments, in the structure of the invention, the same symbols are sometimes used in common in different drawings to represent the same parts or parts with the same function, thereby omitting repeated descriptions. In addition, in the drawings, when representing parts with the same function, for example, the same hatching is sometimes used without adding special symbols. For example, in a stereogram or a top view (also called a "plan view"), for the sake of clarity, the illustration of some constituent elements is sometimes omitted. For example, the description of some hidden lines in the drawings is sometimes omitted. In addition, for example, the description of hatching in the drawings is sometimes omitted.
[0092] In the drawings, dimensions, layer thicknesses, or regions are sometimes exaggerated for the sake of clarity. Therefore, the drawings are not limited to, for example, the dimensions or aspect ratios in the drawings. In addition, in the drawings, ideal examples are schematically shown, so the present invention is not limited to, for example, the shapes or values shown in the drawings. For example, in actual manufacturing processes, layers or resist masks are sometimes unintentionally thinned due to processes such as etching, but this is sometimes not reflected in the drawings for ease of understanding. In addition, in actual circuit operation, for example, voltage or current may be uneven due to noise or timing deviation, but this is sometimes not reflected in the drawings for ease of understanding.
[0093] In this specification and the drawings, the components of the present invention are sometimes classified according to their functions and represented as components that are independent of each other. However, it is difficult to classify the components according to their functions, and sometimes one component involves multiple functions or multiple components involve one function. Therefore, the components shown in this specification and the drawings are not limited to the description thereof, and sometimes the words and phrases can be appropriately changed according to the situation.
[0094] In this specification and the drawings, when the same symbol is used for multiple components and it is necessary to distinguish them, sometimes an identification symbol such as "A", "b", "_1", "[n]" or "[m, n]" is added to the symbol.
[0095] Note that in this specification, etc., the "conductive state" or "open state" of a transistor refers to, for example, a state in which the source and drain of the transistor are electrically short-circuited or a state in which current can flow between the source and drain. For example, the following states are sometimes referred to as "conductive state" or "open state": in an n-channel transistor, the voltage between the gate and the source is higher than the threshold voltage; or in a p-channel transistor, the voltage between the gate and the source is lower than the threshold voltage. In addition, the "non-conductive state", "disconnected state" or "off state" of a transistor refers to a state in which the source electrode and the drain electrode of the transistor are electrically disconnected. For example, the following states are sometimes referred to as "non-conductive state", "disconnected state" or "off state": in an n-channel transistor, the voltage between the gate and the source is lower than the threshold voltage; or in a p-channel transistor, the voltage between the gate and the source is higher than the threshold voltage.
[0096] In addition, in this specification, etc., unless otherwise specified, the "on-state current" of a transistor refers to the current flowing between the source and the drain when the transistor is in the on state (also referred to as the drain current). In addition, in this specification, etc., unless otherwise specified, the "off-state current" of a transistor refers to the drain current when the transistor is in the off state. Note that in this specification, etc., the drain current when the transistor is in the off state and the current flowing between the gate and the source or drain (also referred to as the gate leakage current) are sometimes referred to as leakage current.
[0097] In this specification, etc., the space group is represented by the short notation of the international symbol (or Hermann-Mauguin symbol). In addition, the Miller index is used to represent the crystal plane and crystal orientation. In crystallography, the space group, crystal plane and crystal orientation are represented by a superscript bar attached to the number. However, in this specification, etc., due to the symbol limitation in the patent application, sometimes - (minus sign) is attached before the number to represent the space group, crystal plane and crystal orientation instead of attaching a superscript bar to the number. In addition, "[]" is used to represent the individual orientation of the orientation in the crystal, "<>" is used to represent the collective orientation of all equivalent orientations, "()" is used to represent the individual face of the crystal plane, and "{}" is used to represent the collective face with equivalent symmetry. In addition, in general, in order to facilitate the understanding of the structure, the trigonal crystal represented by the space group R-3m is represented by the composite hexagonal lattice of the hexagonal crystal. In this specification, etc., unless otherwise specified, the space group R-3m is also represented by the composite hexagonal lattice. Sometimes, (hkil) is used as the Miller index in addition to (hkl). Here, i is -(h+k).
[0098] In this specification, the particle is not limited to a spherical shape (a circular cross-sectional shape). The cross-sectional shape of each particle may be, for example, an ellipse, a rectangle, a trapezoid, a cone, a quadrangle with an arcuate corner, or an asymmetric shape. In addition, each particle may also be amorphous.
[0099] In this specification, etc., homogeneity refers to a phenomenon in which a certain element (for example, A) in a solid composed of multiple elements (for example, A, B, and C) has the same characteristics and is distributed in a specific region. Note that the element concentration between specific regions may be substantially the same. For example, the difference in element concentration between specific regions may be within 10%. Examples of specific regions include a surface portion, a surface, a convex portion, a concave portion, or a bulk.
[0100] In this specification and the like, segregation refers to a phenomenon in which a certain element (for example, B) is spatially non-uniformly distributed in a solid containing a plurality of elements (for example, A, B, and C).
[0101] In this specification, etc., a secondary battery of one embodiment of the present invention includes, for example, a positive electrode and a negative electrode. As a material constituting the positive electrode, a positive electrode active material can be cited. For example, the positive electrode active material is a substance that performs a reaction that contributes to the charge and discharge of the secondary battery. In addition, the positive electrode active material may also include a substance that does not contribute to the charge and discharge of the secondary battery in part.
[0102] In addition, in this specification, etc., the positive electrode active material refers to a compound containing transition metals and oxygen in which lithium can be embedded and released. Note that carbonates or hydroxyls adsorbed after the positive electrode active material is manufactured are not included in the positive electrode active material. In addition, electrolytes, organic solvents, adhesives, conductive materials or compounds derived from them adsorbed after the positive electrode active material is manufactured are also not included in the positive electrode active material.
[0103] In addition, in this specification, etc., the positive electrode active material to which the additional element is added is sometimes recorded as, for example, a composite oxide, a positive electrode material, or a positive electrode material for a secondary battery. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a compound. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composition. In addition, in this specification, etc., the positive electrode active material of one embodiment of the present invention preferably includes a composite. In addition, the positive electrode active material refers to, for example, a particle collection of lithium cobalt nickel oxide.
[0104] In addition, the theoretical capacity of the positive electrode active material refers to the amount of electricity when all the lithium that can be embedded and detached in the positive electrode active material is detached. For example, the theoretical capacity of lithium cobalt oxide (LiCoO2) is 274mAh / g, the theoretical capacity of lithium nickel oxide (LiNiO2) is 274mAh / g, and the theoretical capacity of lithium manganese oxide (LiMn2O4) is 148mAh / g.
[0105] The state of charge (SOC) is a value indicating the state of how much charge has been applied based on the theoretical capacity of the positive electrode active material, that is, the value of the state of how much lithium has detached from the positive electrode. For example, in the case of using a positive electrode active material having a layered rock salt type crystal structure such as lithium cobaltate (LiCoO2) or lithium nickel x Co y Mn z O2 (x + y + z = 1)), when the theoretical capacity is 274 mAh / g, a state of charge of 0 means that lithium does not detach from the positive electrode active material, a state of charge of 0.5 means a state where lithium equivalent to 137 mAh / g has detached from the positive electrode, and a state of charge of 0.8 means a state where lithium equivalent to 219.2 mAh / g has detached from the positive electrode.
[0106] In addition, x in the composition formula, for example, x in Li x CoO2 or x in Li x MO2 can represent the amount of lithium remaining in the positive electrode active material relative to the theoretical capacity. Here, M means a transition metal that undergoes redox as lithium is intercalated and deintercalated. In this specification and the like, Li x CoO2 can be appropriately renamed as Li x MO2. When explaining the positive electrode active material in a secondary battery, x can be (theoretical capacity - charge capacity (charge amount)) / theoretical capacity. For example, when a secondary battery using LiCoO2 as the positive electrode active material is charged to 219.2 mAh / g, it can be said that the positive electrode active material is Li 0.2 CoO2 or it can be said that x = 0.2. A smaller x in Li x CoO2, for example, means a case where 0.1 < x ≤ 0.24.
[0107] When lithium cobaltate approximately satisfies the stoichiometric ratio, it is LiCoO2 and the occupancy of lithium at the lithium position is x = 1. In addition, lithium cobaltate in a secondary battery at the end of discharge can also be said to be LiCoO2 and x = 1. Here, "end of discharge" means, for example, a state where the current is 100 mA / g and the voltage is 2.5 V (versus lithium at the counter electrode) or less. In a lithium ion secondary battery, when the occupancy of lithium at the lithium position is x = 1 and no other lithium can be intercalated into the positive electrode active material, the voltage drops sharply. It can be said that the discharge ends at this time. Generally, the discharge voltage of a lithium ion secondary battery using LiCoO2 drops sharply before reaching 2.5 V, so it is assumed that the discharge ends under the above conditions. In addition, the positive electrode at the end of discharge can be confirmed to have a general LiCoO2 crystal structure when analyzed using an XRD pattern or the like.
[0108] For calculating Lix The charge capacity (charge amount) and discharge capacity of x in CoO2 are preferably measured under conditions without or with little effect of short circuit and electrolyte decomposition. For example, data of a secondary battery in which the capacity changes sharply as if it were a short circuit cannot be used to calculate x.
[0109] The space group of a crystal structure is identified by, for example, an XRD pattern, an electron diffraction pattern, or a neutron diffraction pattern, etc. Therefore, in this specification, etc., belonging to a certain space group or a space group means being identified as a certain space group.
[0110] In addition, when the configuration of anions is roughly close to cubic closest packing, it can be regarded as cubic closest packing. The cubic closest packed anion configuration refers to the following state: the anions of the second layer are configured on the gaps of the anions filled in the first layer, and the anions of the third layer are configured just on the gaps of the anions of the second layer but not just on the anions of the first layer. Therefore, the anions may not be strictly cubic lattices. In addition, in fact, crystals all have defects, so the analysis results may not be based on theory. For example, spots may also appear in FFT (Fast Fourier Transformation: Fast Fourier Transformation) patterns of electron diffraction patterns or TEM (Transmission Electron Microscope: Transmission Electron Microscope) images, etc., at positions slightly different from the theoretical positions. For example, when the difference in orientation from the theoretical position is less than 5 degrees or less than 2.5 degrees, it can be said that there is a cubic closest packed structure.
[0111] Generally speaking, as the charging voltage of the secondary battery increases, the potential of the positive electrode also increases. The positive electrode active material of one embodiment of the present invention has a stable crystal structure even at a high charging voltage. The crystal structure of the positive electrode active material in the charged state is stable, so the reduction in the fully charged capacity due to repeated charging and discharging can be suppressed.
[0112] In addition, the short circuit of the secondary battery can cause heat and fire in addition to causing at least one of the charging and discharging operations of the secondary battery. In order to achieve a safe secondary battery, it is preferred to suppress the short-circuit current even at a high charging voltage. The positive electrode active material of one embodiment of the present invention can also suppress the short-circuit current at a high charging voltage. Therefore, a secondary battery that achieves both high charge and discharge capacity and safety can be manufactured.
[0113] Note that, unless otherwise specified, the materials included in the secondary battery in the state before deterioration (e.g., positive electrode active material, negative electrode active material, and electrolyte, etc.) are described. For example, the following situation can be referred to as the state before deterioration: the case where the secondary battery has a fully charged capacity of more than 97% of the rated capacity. The rated capacity is in accordance with JIS C8711:2019. In addition, in this specification, etc., the state before deterioration of the materials included in the secondary battery is sometimes referred to as the initial article or initial state and the state after deterioration (the state where the secondary battery has a fully charged capacity of less than 97% of the rated capacity) is referred to as an article in use or in a state in use or a used article or a used state.
[0114] (Implementation Method 1)
[0115] In this embodiment, a charger according to one embodiment of the present invention and a power storage system including the charger according to one embodiment of the present invention are described.
[0116] <Example 1 of Power Storage System>
[0117] Figure 1A 2 is a block diagram showing an example of a power storage system 200. The power storage system 200 includes a charger 201 and a secondary battery 121. The charger 201 is electrically connected to each of a positive electrode and a negative electrode of the secondary battery 121.
[0118] The charger 201 includes a control circuit 153, a current measurement circuit 152, and a voltage measurement circuit 151. In addition, the charger 201 preferably also includes a temperature sensor TS. The temperature sensor TS can measure the ambient temperature of the secondary battery. The temperature sensor TS is, for example, set to contact the outer packaging body or frame of the secondary battery. The charging control using the temperature sensor TS will be described later.
[0119] The current measurement circuit 152 has a function of measuring the current of the secondary battery 121 (the current flowing through the secondary battery 121). In particular, the current measurement circuit 152 preferably has a function of measuring the charging current of the secondary battery 121 (the current flowing when the secondary battery 121 is charged). The current measurement circuit 152 can provide the measured current value to the control circuit 153.
[0120] The voltage measurement circuit 151 has a function of measuring the voltage of the secondary battery 121 (the potential difference generated between the positive electrode and the negative electrode of the secondary battery 121). In particular, the voltage measurement circuit 151 preferably has a function of measuring the charging voltage of the secondary battery 121 (the potential difference generated between the positive electrode and the negative electrode when the secondary battery 121 is charged). The voltage measurement circuit 151 can provide the measured voltage value to the control circuit 153.
[0121] The control circuit 153 has a function of controlling the start and stop of charging of the secondary battery 121. In addition, the control circuit 153 has a function of controlling the charging conditions of the secondary battery 121. Specifically, for example, the control circuit 153 has a function of controlling the charging current of the secondary battery 121.
[0122] As the control circuit 153 , for example, a CPU (Central Processing Unit) or an MCU (Micro Controller Unit) can be used.
[0123] The control circuit 153 has a function of calculating the voltage of the secondary battery 121 provided by the voltage measurement circuit 151 over time or a function of calculating the time differential of the voltage. The calculation of the voltage over time or the calculation of the voltage time differential, for example, refers to obtaining a plurality of data sets of voltage values and time and using the obtained plurality of data sets to perform calculations. The control circuit 153 preferably includes an analog-to-digital conversion circuit. When the voltage value of the secondary battery 121 obtained is an analog value, the control circuit 153 can use an analog-to-digital conversion circuit to convert the analog value into a digital value. When an MCU is used as the control circuit 153, a structure in which the control circuit 153 includes a voltage measurement circuit 151 and an analog-to-digital conversion circuit unit can also be adopted. In addition, the analog-to-digital conversion circuit and the control circuit 153 can also be prepared separately.
[0124] In addition, the control circuit 153 has a function of calculating the time integral of the current of the secondary battery 121 supplied from the current measurement circuit 152, that is, a function of calculating the electric quantity of the secondary battery 121. Calculating the time integral of the current, that is, calculating the electric quantity means, for example, obtaining a plurality of sets of data of current values and time, and calculating using the obtained plurality of sets of data. In addition, the control circuit 153 has a function of calculating the voltage differential (dQ / dV) of the electric quantity of the secondary battery 121. Calculating the voltage differential of the electric quantity means, for example, obtaining a plurality of sets of data of voltage values, current values, and time, and calculating using the obtained plurality of sets of data.
[0125] In addition, the control circuit 153 includes a storage circuit. The storage circuit is used as a register or cache memory in the CPU or MCU, for example. In addition, the storage circuit has a function of storing various programs used in the power storage system 200 and various data required for the operation of the power storage system 200, for example.
[0126] Figure 1B 2 is a block diagram showing another example of the power storage system 200 . Figure 1B The power storage system 200 shown includes a charger 201 in addition to Figure 1AIn addition to the components shown, the present invention also includes a detection circuit 185, a detection circuit 186, a short circuit detection circuit SD, a micro short circuit detection circuit MSD, a transistor 140, and a transistor 150. The detection circuit 185, the detection circuit 186, the short circuit detection circuit SD, the micro short circuit detection circuit MSD, the transistor 140, and the transistor 150 will be described in detail later.
[0127] Figure 2A and Figure 2B It is shown Figure 1A and Figure 1B 2 is a block diagram of a specific configuration example of the current measurement circuit 152 in the charger 201 included in the power storage system 200 shown in FIG. Figure 2A and Figure 2B As shown, the current measurement circuit 152 includes a resistor 152a and a circuit 152b.
[0128] The resistor 152a is used as a shunt resistor. The circuit 152b has a function of measuring the voltage across both ends of the resistor 152a.
[0129] Note that the current measurement circuit 152 is not limited to Figure 2A and Figure 2B The current measuring circuit 152 is a resistance detection type structure using a shunt resistor (resistor 152a) as shown. The current measuring circuit 152 may also be a magnetic field detection type structure using, for example, a coil, a hole element, a magnetoresistive element, a magneto-impedance element, or a fluxgate.
[0130] Figure 3A and Figure 3B 2 is a block diagram showing another example of the power storage system 200 . Figure 3A and Figure 3B The power storage system 200 shown in FIG. Figure 2A and Figure 2B In addition to the structure shown, a DC-DC converter 157, a circuit 158 and a diode 159 are also included.
[0131] like Figure 3A and Figure 3B As shown, the power storage system 200 may further include a DC-DC converter 157. The DC-DC converter 157 includes a voltage conversion circuit (not shown) and a control circuit (not shown). The DC-DC converter 157 has a function of converting the voltage of the secondary battery 121 and outputting the voltage.
[0132] In addition, if Figure 3A and Figure 3BAs shown, the power storage system 200 may also include a circuit 158. The circuit 158 is preferably used as an AC adapter. That is, the circuit 158 has, for example, a function of converting alternating current into direct current. In addition, the circuit 158 has, for example, a voltage conversion function. In addition, the circuit 158 has a function of supplying the power converted into direct current to the secondary battery 121. The circuit 158 may also have a function of controlling the current value and the voltage value provided when supplying power to the secondary battery 121. In addition, the circuit 158 may also have a function of controlling the current value and the voltage value provided to the secondary battery 121 according to the signal supplied by the control circuit 153.
[0133] exist Figure 3A and Figure 3B In the power storage system 200 shown, a diode 159 may be provided between the circuit 158 and the charger 201. The diode 159 has a function of suppressing a reverse current from the charger 201 to the circuit 158.
[0134] Figure 4A and Figure 4B 1 is a block diagram for explaining the measurement of the voltage of the secondary battery 121 by the voltage measurement circuit 151 in the power storage system 200. The voltage measurement circuit 151 may be Figure 4A The voltage Vb1 between the positive and negative electrodes of the secondary battery 121 is measured as shown in FIG. Figure 4B As shown, the voltage obtained by dividing the voltage Vb1 by resistance is measured.
[0135] exist Figure 4B In the embodiment, the voltage Vb1 is divided into the voltage Vb2 and the voltage Vb3 by the resistors 122 and 123. The voltage measuring circuit 151 measures the divided voltage Vb3.
[0136] like Figure 4B As shown, when the voltage Vb1 between the positive and negative electrodes of the secondary battery 121 is measured by the voltage Vb3 obtained by resistor division, the voltage measurement circuit 151 or the control circuit 153 can also estimate the voltage Vb1 between the positive and negative electrodes of the secondary battery 121 based on the voltage Vb3 divided by the resistor.
[0137] In addition, the charger 201 is preferably used as a coulomb meter. For example, the charger 201 has a function of calculating the cumulative amount of electricity of the secondary battery 121 using the current measurement circuit 152 and the control circuit 153 to calculate the charging capacity (charged electricity) and the discharging capacity of the secondary battery 121. In addition, the charger 201 may also have a function of analyzing the depth of charge using the calculated charging capacity (charged electricity) and discharging capacity.
[0138] {Charge}
[0139] Next, charging of a secondary battery using the charger according to one embodiment of the present invention will be described.
[0140] In a secondary battery, as the depth of charge increases (charge capacity (charge amount) increases), the crystal structure of the positive electrode active material in the secondary battery changes. When the crystal structure changes irreversibly, the fully chargeable capacity of the secondary battery may decrease due to repeated charging.
[0141] Therefore, in order to realize a secondary battery with a large discharge capacity and a long life, for example, it is necessary to increase the charge depth of the secondary battery and control the charge depth of the secondary battery within a range in which the crystal structure changes substantially reversibly.
[0142] For example, by charging with a specified voltage as the upper limit of the charging voltage of the secondary battery, the charging depth of the secondary battery can be controlled within the range of roughly reversible changes in the crystal structure. However, in the secondary battery, the state changes due to repeated charging and discharging, so even if charging is performed with the same voltage as the upper limit, it is difficult to keep the charging depth of the secondary battery the same as the charge and discharge cycles increase. Therefore, in order to control the charging depth of the secondary battery within the range of roughly reversible changes in the crystal structure, a unit that monitors the charging process is required.
[0143] By using a charger of one embodiment of the present invention, the charging process can be monitored, and the charging depth of the secondary battery can be controlled within a range where the charging depth is large and the crystal structure changes substantially reversibly. In addition, the secondary battery preferably uses the positive electrode active material of one embodiment of the present invention.
[0144] A charger according to one embodiment of the present invention can suppress the collapse of the crystal structure of the positive electrode active material in the secondary battery by controlling the charging conditions of the secondary battery. More specifically, for example, a charger according to one embodiment of the present invention can increase the charging voltage of the secondary battery to the limit within a range that can suppress the collapse of the crystal structure, and can achieve high energy density by efficiently utilizing the secondary battery to the limit while improving the reliability of the secondary battery.
[0145] In a charger of one embodiment of the present invention, in particular, the collapse of the crystal structure of a positive electrode active material having a layered crystal structure can be suppressed. In a positive electrode active material having a layered crystal structure, for example, metals used as carrier ions are arranged in layers. For example, in lithium cobalt oxide, lithium exists in layers between CoO2 layers. In a positive electrode active material having a layered crystal structure, when carrier ions are separated as charging occurs, crystal distortion, changes in the crystal structure caused by the separation of carrier ions, and the like sometimes occur. For example, in lithium cobalt oxide, when lithium ions are separated as charging occurs, changes such as deviation of the CoO2 layer and reduction of the interlayer distance of the CoO2 layer sometimes occur. In the crystal structure of the positive electrode active material, when such a change is a reversible change, the reduction in the fully charged capacity and discharge capacity during repeated charging and discharging can be suppressed. On the other hand, when the charging voltage is too high, the depth of charge increases, and the amount of carrier ions separated increases. When the depth of charge increases, the crystal structure changes irreversibly as charging occurs, so during repeated charging and discharging, the fully charged capacity and discharge capacity may decrease.
[0146] In addition, excessively high charging voltage may cause the constituent elements of the positive electrode active material to dissolve into the electrolyte, which may cause the collapse of the crystal structure of the positive electrode active material. In addition, charging at a high voltage may cause decomposition reactions of the constituent elements of the electrolyte.
[0147] A charger according to one embodiment of the present invention can detect changes in the crystal structure using a simple method, increase the charging voltage to the maximum within a range that can ensure high reliability, and utilize the secondary battery efficiently to the maximum.
[0148] The secondary battery using the charger of one embodiment of the present invention can preferably determine the upper limit voltage of charging based on the waveform obtained during charging. Here, the waveform can be various shapes such as a curve, a straight line, a combination of a curve and a straight line. In addition, the waveform is not limited to a periodic wave. As the waveform obtained during charging, for example, a dQ / dV-V curve or a ΔV-t curve generated from the data of the voltage, time, and current during charging can be cited. That is, in the waveform obtained during charging of the secondary battery using the charger of one embodiment of the present invention, it is preferable to detect the extreme value caused by the crystal structure change of the positive electrode active material. In addition, in the secondary battery using the charger of one embodiment of the present invention, it is preferable to increase the charging voltage during repeated charging and discharging to the limit, and it is preferable that the crystal structure of the positive electrode active material also changes roughly reversibly at the increased charging voltage. Here, roughly reversible means: reversible; or even if it is irreversible, the deterioration caused by the repeated crystal structure change is extremely small. The positive electrode active material of one embodiment of the present invention changes from the O3 type crystal structure to the O3' type crystal structure described later when the charging depth of the secondary battery is about 80% or thereabouts. When this change occurs, an extreme value is observed on a dQ / dV curve, etc. A charger according to one embodiment of the present invention has a function of detecting the extreme value and controlling charging.
[0149] In addition, in a secondary battery using a charger of one embodiment of the present invention, in order to efficiently utilize the secondary battery to the limit within the range in which the crystal structure changes substantially reversibly, the extreme value caused by the change in the crystal structure is preferably near the upper limit voltage of charging. For example, it is preferred that the extreme value caused by the change in the crystal structure is lower than the upper limit voltage of charging, and the difference between the voltage when the extreme value is detected and the upper limit voltage of charging is 0.15V or less.
[0150] In a secondary battery using a charger of one embodiment of the present invention, it is preferred that even if charging is performed for a certain period of time after exceeding the voltage at which the above extreme value is detected, the crystal structure of the positive electrode active material can be substantially reversibly changed during charging and discharging. When a secondary battery using a charger of one embodiment of the present invention has such characteristics, the charger of one embodiment of the present invention can simply control the upper limit voltage of charging for efficiently utilizing the secondary battery to the limit using the above extreme value.
[0151] The extreme value caused by the change in the crystal structure is detected, for example, on a voltage change curve of the secondary battery over time, or on a voltage time differential curve (dV / dt curve) of the secondary battery.
[0152] In addition, the extreme value caused by the change in the crystal structure is detected on, for example, a voltage differential curve (dQ / dV curve) of the electric quantity of the secondary battery.
[0153] When charging a secondary battery, constant current constant voltage (CCCV: Constant Current, Constant Voltage) charging is sometimes used. In CCCV charging, constant current charging is performed, and constant voltage charging is performed after the upper limit voltage of charging is reached during constant current charging. In CCCV charging, for example, constant voltage charging is performed at the upper limit voltage of constant current charging, so that charging can be performed for a long time at the upper limit voltage, and the charging capacity (charge amount) is not easily affected by impedance changes caused by the deterioration of the secondary battery, and a small uneven charging capacity (charge amount) can be obtained.
[0154] By increasing the charging voltage, the charging capacity (charge amount) can be increased. However, depending on the performance of the positive electrode active material, charging at a high voltage may cause the collapse of the crystal structure of the positive electrode active material, and may cause decomposition reactions of the constituent elements of the electrolyte, etc. Therefore, constant voltage charging at an upper limit voltage has the concern of accelerating the deterioration of the secondary battery. By utilizing constant current charging, the charging time at the upper limit voltage can be shortened and the life of the secondary battery can be extended, so it is preferred. In particular, when the ambient temperature of the secondary battery is a high temperature condition higher than 40°C, the degradation of the secondary battery is sometimes obvious during constant voltage charging at the upper limit voltage. Therefore, when the ambient temperature of the secondary battery is high, constant current charging is more preferably performed. In addition, when the ambient temperature of the secondary battery is high, it is preferably not to use constant voltage charging at a high voltage or to shorten the time of constant voltage charging at a high voltage as much as possible.
[0155] Here, the use of the chemical formula AM y O Z (y>0, z>0), more specifically, the charging of the case where the positive electrode active material represented by the chemical formula AMO2 is used. The chemical formula AM will be described later. y O Z (y>0, z>0), element A and metal M. Note that the positive electrode active material is represented by the chemical formula AMO2, but the composition of A:M:O is not limited to 1:1:2. In addition, lithium cobalt oxide is sometimes represented by LiCoO2. In addition, lithium nickel oxide is sometimes represented by LiNiO2.
[0156] For example, the secondary battery is charged using the charger of one embodiment of the present invention at a temperature of 35° C. to 55° C. so that the depth of charge is 85% or less, 80% or less, or 77% or less.
[0157] In addition, as the charge degree, the x in the composition formula, such as Li xIn CoO₂, x represents the amount of lithium that can be inserted and extracted remaining in the positive electrode active material. When explaining the positive electrode active material in a secondary battery, x can be (theoretical capacity - charging capacity (charging electric quantity)) / theoretical capacity. For example, when charging a secondary battery using LiCoO₂ as the positive electrode active material to 219.2 mAh / g, it can be said that the positive electrode active material is Li 0.2 CoO₂ or it can be said that x = 0.2. Li x A smaller x in Li
[0158] In a power storage system according to one embodiment of the present invention, charging may be performed in such a manner that x is 0.2 or less, 0.24 or less, or 0.3 or less.
[0159] In addition, in this case, for example, at a temperature of 35°C or higher and 55°C or lower, as the upper limit voltage of charging, the positive electrode potential is preferably 4.8 V or lower, more preferably 4.75 V or lower, further preferably 4.7 V or lower, and still preferably 4.65 V or lower, based on the lithium potential (Li / Li + ). Charging is performed in such a manner.
[0160] In addition, in this case, for example, at a temperature of 40°C or higher and 55°C or lower, the charging rate (C rate, also referred to as the capacity rate) is preferably 0.35 C or higher, more preferably 0.45 C or higher, further preferably 0.7 C or higher, and still preferably 0.9 C or higher. Here, "C" is a unit of rate. In particular, charging is performed in such a manner as to achieve this charging rate at a voltage where the positive electrode potential is 4.2 V or higher, 4.3 V or higher, or 4.4 V or higher, based on the lithium potential (Li / Li + ). Here, the charging rate of 1 C, for example, refers to the following current density: when the total amount of element A (when using lithium cobaltate, element A is lithium) in the positive electrode active material causes a charging reaction with an electric quantity of 1 and is charged to about 0.7 times the electric quantity in 1 hour.
[0161] Note that reducing the charging depth can extend the life of the secondary battery, but when the charging depth is too small, the discharge capacity of the secondary battery becomes small. Therefore, the charging depth is preferably 50% or more, more preferably 60% or more, further preferably 70% or more, and still further preferably 73% or more. In addition, the charging depth can also be greater than 75%.
[0162] Here, the charging capacity (charging electric quantity) per unit weight of the positive electrode active material is used as the charging depth for normalization, and the state where all the lithium in the positive electrode active material is extracted is regarded as the charging depth = 100%.
[0163] Note that the calculation method of the depth of charge of the secondary battery is not limited to the above example. For example, the charge equivalent to the rated capacity of the secondary battery can also be regarded as the depth of charge = 100%. In addition, the normalization of the charge capacity (charge amount) used for the depth of charge is not limited to the above example. Normalization can be performed using the volume of the secondary battery, the internal volume of the secondary battery, the volume of a part of the secondary battery, the weight of the secondary battery, the weight of the contents of the secondary battery, or the weight of a part of the secondary battery.
[0164] In a charger of one embodiment of the present invention, an extreme value caused by a change in the crystal structure of a positive electrode active material can be detected on a dQ / dV curve or the like to perform constant current charging. In addition, constant current charging using the detection of the extreme value is simple and has good controllability. Therefore, by using a charger of one embodiment of the present invention, a secondary battery can be realized in which the unevenness of the charging capacity (charging amount) is small and the degradation caused by high voltage charging is suppressed.
[0165] Details of a secondary battery that can be used as the secondary battery 121 will be described later.
[0166] <Charging method example 1>
[0167] Next, use Figure 5 The flowchart shown explains an example of a charging method using a charger according to one embodiment of the present invention.
[0168] First, in step S100, the process starts.
[0169] Next, in step S101, constant current charging of the secondary battery is started at time t1. This constant current charging is continuously performed until charging is stopped in step S107.
[0170] Next, in step S102, the voltage measurement circuit 151 starts measuring the voltage of the secondary battery. In addition, the current measurement circuit 152 starts measuring the current of the secondary battery. The voltage measurement circuit 151 provides the measured voltage value to the control circuit 153. The current measurement circuit 152 provides the measured current value to the control circuit 153.
[0171] Next, in step S103, the control circuit 153 accumulates the voltage value measured by the voltage measurement circuit 151 and the current value measured by the current measurement circuit 152 after step S102 as a data set with time. The data accumulation can use a storage circuit in the control circuit 153. As the time associated with the voltage value and the current value, for example, the time from the start of charging can be used.
[0172] Next, in step S104, the control circuit 153 uses the data set of voltage value, current value and time accumulated at any time to calculate the voltage differential curve (dQ / dV curve) of the power of the secondary battery. Here, in step S103, the voltage differential curve of the power of the secondary battery can also be calculated after accumulating the data set of voltage value, current value and time for a certain specified time. For example, the data set can also be accumulated during a period sufficient for extreme value detection.
[0173] Next, in step S105, the control circuit 153 analyzes the curve of the voltage differential dQ / dV (hereinafter, the dQ / dV-V curve) in which the horizontal axis represents the voltage V and the vertical axis represents the electric quantity Q to determine whether an extreme value (also called a peak) is detected. When an extreme value is detected on the dQ / dV-V curve, for example, when a local maximum value (also called an upwardly convex peak) is detected, the process proceeds to step S106. When no local maximum value is detected, the process returns to step S103. Note that sometimes multiple extreme values are detected on the dQ / dV-V curve. In this case, the extreme value that occupies the highest position among the multiple extreme values is detected. Alternatively, the upper r extreme values (r is an integer greater than 2) among the multiple extreme values may be detected and any extreme value may be selected from the r extreme values.
[0174] Here, the upper extreme value refers to an extreme value that is at the upper position in the order determined by a predetermined condition. For example, the upper extreme value may be determined by arranging the extreme values in descending order.
[0175] The control circuit 153 preferably continues to accumulate the data set of voltage value, current value and time during the repetition of step S103 to step S105. That is, when step S103 to step S105 are repeated n times, all the data of n times can be used to calculate the dQ / dV-V curve. Alternatively, only the latest one or the latest several data among the n times can be used.
[0176] Next, in step S106, the control circuit 153 determines whether the voltage of the secondary battery is greater than or equal to a predetermined voltage. When the voltage V of the secondary battery is greater than or equal to voltage V2, the process proceeds to step S107. When the voltage V is less than voltage V2, the process returns to step S103. Here, voltage V2 is, for example, greater than or equal to 4.25V or greater than or equal to 4.25 and less than 4.8V.
[0177] Alternatively, the magnitude of the voltage V and the voltage V2 in step S106 can also be determined based on the depth of charge of the secondary battery. For example, when the depth of charge of the secondary battery is S1% or more, the process proceeds to step S107, and when it is less than S1%, the process returns to step S103. Here, S1 is 60% or more or 60% or more and 95% or less.
[0178] The control circuit 153 may continue to accumulate the data set of the voltage value, the current value, and the time from the first step S103 to the step S107 in the multiple repetitions of step S103.
[0179] Next, in step S107, the time tp at which the dQ / dV-V curve takes an extreme value is analyzed and detected, and charging is stopped at time t2, which is a time after a predetermined time after time tp. Here, the predetermined time refers to, for example, the time required for the control circuit 153 to stop charging. Alternatively, for example, a region having a desired voltage width may be determined with the voltage taking an extreme value on the dQ / dV-V curve as the center, and the time corresponding to the voltage at the upper end of the region may be set as time t2. Note that, when no extreme value is detected in step S107, charging may be stopped when a predetermined charging voltage is reached.
[0180] In addition, although the extreme value detection is cited as the condition for stopping charging in step S107, for example, an inflection point may be detected and the charging stop may be controlled based on the elapsed time after the inflection point is detected.
[0181] The curve to be analyzed may also be smoothed. As a smoothing method, for example, a sliding average may be used.
[0182] Here, the inflection point detected at time tp is, for example, an inflection point caused by a change in the crystal structure of a positive electrode active material in the positive electrode of the secondary battery.
[0183] When the positive electrode active material of one embodiment of the present invention is used as the positive electrode active material, for example, by stopping the charging of the secondary battery at a time near time tp, collapse of the crystal structure of the positive electrode active material due to repeated charge and discharge can be suppressed.
[0184] As a specific example of an inflection point detected at time tp, by using a positive electrode active material of one embodiment of the present invention, an inflection point corresponding to the change of the crystal structure of the positive electrode active material from an O3 type crystal structure to an O3' type crystal structure can be used. Here, the positive electrode active material is, for example, lithium cobalt oxide. In addition, it is preferred that the charging voltage at time t2 is lower or the charging depth is smaller than the case where the crystal structure of the positive electrode active material changes to an H1-3 type crystal structure. The O3 type crystal structure, the O3' type crystal structure and the H1-3 type crystal structure will be described in detail later. Note that the change from the O3 type crystal structure to the O3' type crystal structure is sometimes expressed as a phase change.
[0185] In the power storage system of one embodiment of the present invention, for example, the crystal structure of the positive electrode active material of the secondary battery at time t2 is controlled to be an O3' type crystal structure. This can suppress the collapse of the crystal structure of the positive electrode active material during repeated charge and discharge of the secondary battery.
[0186] Note that when the positive electrode is analyzed using an XRD pattern in a charged state corresponding to time t2, the determined crystal structure is preferably represented by space group R-3m. In addition, it is more preferred that the determined crystal structure is represented by space group R-3m and shows an O3' type crystal structure.
[0187] For example, when the positive electrode obtained by disassembling a secondary battery charged using the power storage system of one embodiment of the present invention is evaluated by XRD pattern at the charging state corresponding to time t2, a spectrum corresponding to the space group R-3m is observed. For measurement conditions and measurement methods, etc., refer to the following description.
[0188] Furthermore, when the positive electrode is analyzed using an XRD pattern in a state before the secondary battery is charged, the crystal structure identified is also preferably represented by the space group R-3m.
[0189] In the power storage system of one embodiment of the present invention, when the positive electrode is analyzed by XRD pattern at time t2 and before charging, the crystal structure determined is represented by space group R-3m, so a secondary battery with little reduction in discharge capacity during charge and discharge cycles can be realized.
[0190] Here, consider the case where steps S101 to S107 are repeated s times. s is an integer greater than 2. In this case, the time tp and time t2 obtained based on the extreme values detected in steps S102 to S106 can also be used in the next charging cycle. Specifically, in step S107 of the s-th charging, the time tp and time t2 obtained in the (s-1)-th charging can also be used as a condition for stopping charging.
[0191] Then, in step S199, the processing ends.
[0192] Note that the above description is an example of continuing constant current charging from the start of charging in step S101 until charging stops in step S107. In this case, for example, the current value of constant current charging is set to a fixed current value from the start of charging in step S101 until charging stops in step S107. Alternatively, the current value in constant current charging may be changed in stages from the start of charging in step S101 until charging stops in step S107. As a specific example, when steps S103 to S105 are repeated n times, the current value after a certain number of times may be changed.
[0193] A charger according to one embodiment of the present invention can analyze the charging characteristics of a secondary battery in steps S103 to S106, and change the charging conditions of the secondary battery in step S107 according to the analysis results. Specifically, for example, the charging of the secondary battery can be stopped. The charging characteristics analyzed in steps S103 to S106 change according to the ambient temperature of the charging and discharging of the secondary battery, the deterioration of the secondary battery accompanying the charge and discharge cycle, and the like. In a charger according to one embodiment of the present invention, by changing the charging conditions of the secondary battery, such as the charging voltage of the secondary battery, according to such changes in the charging characteristics, the deterioration of the secondary battery can be suppressed.
[0194] Furthermore, in the charger according to one embodiment of the present invention, by analyzing the charging characteristics, the secondary battery can be charged to the limit within a range where degradation of the secondary battery is suppressed.
[0195] Alternatively, in step S107 , constant voltage charging may be performed at a voltage lower than the upper limit charging voltage of the constant current charging at time t2 after time t2 .
[0196] <Charging method example 2>
[0197] use Figure 6 The flowchart shown in FIG. 1 is an example of a charging method using a charger according to one embodiment of the present invention. Figure 6 In the charging method shown, the operation performed by the control circuit 153 is Figure 5 The charging method shown is simple and can sometimes be operated on a smaller circuit scale.
[0198] dQ / dV can be expressed by the following formula.
[0199] dQ / dV=(dQ / dt)×(dt / dV)
[0200] In constant current charging, dQ / dt is constant, so dQ / dV is proportional to dt / dV. Therefore, by evaluating the dt / dV characteristics in constant current charging, the same information as the dQ / dV characteristics can be obtained.
[0201] The following is an example of evaluating the dt / dV characteristic in a constant current charging region. It is not necessary to obtain the current value of the secondary battery at all times, and sometimes the dt / dV characteristic can be obtained more simply than the dQ / dV. In addition, the only parameters to be obtained are voltage and time, so the calculation is also simple, and sometimes the circuit scale can be reduced. In addition, the amount of data to be obtained can also be reduced, so sometimes the scale of the storage circuit can be reduced.
[0202] In addition, the change of dQ / dV in constant current charging may be slower than that in constant voltage charging.
[0203] In view of the above, in a power storage system of one embodiment of the present invention, even if the voltage resolution of the circuit for obtaining dt / dV characteristics during constant current charging is, for example, 12 bits or less, sufficient evaluation can be performed. In particular, in a secondary battery using a positive electrode active material of one embodiment of the present invention, the extreme value is stably observed on the dQ / dV curve during constant current charging. Therefore, charging can be controlled with high precision in a simpler measurement system.
[0204] First, in step S000, the process starts.
[0205] Next, in step S001, constant current charging of the secondary battery is started at time t3. This constant current charging is continuously performed until charging is stopped in step S007.
[0206] Next, in step S002 , the voltage measurement circuit 151 starts measuring the voltage of the secondary battery and supplies the measured voltage value to the control circuit 153 .
[0207] Next, in step S003, the control circuit 153 accumulates the voltage values measured by the voltage measurement circuit 151 after step S002 as a data set with time. The data accumulation may use a storage circuit in the control circuit 153. As the time associated with the voltage value, for example, the time from the start of charging may be used.
[0208] The acquired voltage value is converted from an analog value to a digital value in the control circuit 153. Alternatively, the control circuit 153 may use the acquired analog value for calculation without converting it into a digital value. Here, an example is described in which an MCU is used as the control circuit 153 and the voltage value is converted using an analog-to-digital conversion circuit incorporated in the MCU.
[0209] Here, an MCU in which an analog-to-digital conversion circuit having a voltage resolution of 12 bits is incorporated is used as an example.
[0210] When the change in voltage value or the absolute value of the change in voltage value exceeds a predetermined value, a data set of voltage value and time is acquired and accumulated. The predetermined value may be, for example, the minimum value of the voltage resolution of the analog-to-digital conversion circuit or a value greater than the minimum value.
[0211] When the change in voltage value or the absolute value of the change in voltage value is smaller than a specified value, a data set of voltage value and time is acquired and accumulated after a specified time has passed since the last acquisition of the data set.
[0212] Next, in step S004, the control circuit 153 uses the data set of voltage values and time accumulated at any time to calculate the change of voltage of the secondary battery over time. The change of voltage over time can be expressed as voltage [V(t)-V(t-Δt1)] using, for example, the voltage V(t) at time t and the voltage V(t-Δt1) at time (t-Δt1). The curve of voltage change over time is sometimes called a ΔV-t curve. For example, as the change of voltage over time, the time differential of voltage (dV / dt) can also be used. Note that the calculation of change over time is performed after time t becomes t=Δt1. Here, in step S003, the data set of voltage value and time can also be accumulated for a specified time, and then the change over time can be calculated. For example, the data set can also be accumulated during a period sufficient for extreme value detection.
[0213] Next, in step S005, the control circuit 153 analyzes the voltage change curve of the secondary battery over time (for example, the ΔV-t curve) to determine whether an extreme value is detected. When an extreme value is detected on the time-varying curve, for example, when a local minimum value (also called a downward convex peak) is detected, the process proceeds to step S006. When no local minimum value is detected, the process returns to step S003. Note that sometimes multiple extreme values are detected on the ΔV-t curve. In this case, the extreme value that occupies the highest position among the multiple extreme values is detected. Alternatively, the upper r extreme values (r is an integer greater than 2) among the multiple extreme values can be detected and any extreme value can be selected from the r extreme values.
[0214] The control circuit 153 preferably continues to accumulate the data set of voltage value and time during the repetition of step S003 to step S005. That is, when step S003 to step S005 are repeated n times, all the data of n times can be used to calculate the time-varying curve. Alternatively, only the latest one or the latest several data of n times can be used. Here, n is an integer greater than 1.
[0215] Next, in step S006, the control circuit 153 determines whether the voltage of the secondary battery is above a specified voltage. When the voltage V of the secondary battery is above the voltage V1, the process proceeds to step S007. When the voltage V is lower than the voltage V1, the process returns to step S003. Here, the voltage V1 is, for example, above 4.25V or above 4.25V and below 4.8V. Here, when the voltage measurement circuit 151 measures the voltage obtained by dividing the voltage between the positive and negative electrodes of the secondary battery by a resistor, it is preferred to use an estimated value of the voltage between the positive and negative electrodes of the secondary battery estimated from the voltage obtained by dividing the voltage by a resistor as the voltage V1.
[0216] Alternatively, the magnitude of the voltage V and the voltage V1 in step S006 can also be determined based on the depth of charge of the secondary battery. For example, when the depth of charge of the secondary battery is S1% or more, the process proceeds to step S007, and when it is less than S1%, the process returns to step S003. Here, S1 is 60% or more or 60% or more and 95% or less.
[0217] The control circuit 153 may continue to accumulate the data set of the voltage value and time during the period from the first step S003 to the step S007 in the multiple repetitions of step S003.
[0218] Next, in step S007, the time tq at which the ΔV-t curve takes an extreme value is analyzed and detected, and charging is stopped at time t4, which is a time after a predetermined time after time tq. Alternatively, for example, a region having a desired time width may be determined with the time at which the ΔV-t curve takes an extreme value as the center, and the time at the upper end of the region may be set as time t4. Here, the predetermined time refers to, for example, the time required for the control circuit 153 to stop charging. Note that, when no extreme value is detected in step S007, charging may be stopped when a predetermined charging voltage is reached.
[0219] In addition, although the extreme value detection is cited as the condition for stopping charging in step S007, for example, the inflection point may be detected and the charging stop may be controlled based on the elapsed time after the inflection point is detected.
[0220] Here, consider the case where steps S001 to S007 are repeated w times. w is an integer greater than 2. In this case, the time tq and time t4 obtained based on the extreme values detected in steps S002 to S006 can also be used in the next charging cycle. Specifically, in step S007 of the w-th charging, the time tq and time t4 obtained in the (w-1)-th charging can also be used as the condition for stopping charging.
[0221] Then, in step S099, the processing ends.
[0222] Note that the above description is an example of continuing constant current charging from the start of charging in step S001 until charging stops in step S007. In this case, for example, the current value of constant current charging is set to a fixed current value from the start of charging in step S001 until charging stops in step S007. Alternatively, the current value in constant current charging may be changed in stages from the start of charging in step S001 until charging stops in step S007. As a specific example, when steps S003 to S005 are repeated n times, the current value after a certain number of times may be changed.
[0223] <Charging method example 3>
[0224] use Figure 7 The flowchart shown explains an example of a charging method using a charger according to one embodiment of the present invention.
[0225] First, in step S200, the process starts.
[0226] Next, in step S201, constant current charging of the secondary battery is started. This constant current charging is continuously performed until charging is stopped in step S206.
[0227] Next, in step S202 , the voltage measurement circuit 151 starts measuring the voltage of the secondary battery and supplies the measured voltage V to the control circuit 153 .
[0228] Next, in step S203, the control circuit 153 compares the measured voltage V with a predetermined voltage V3. When the voltage V is equal to or higher than the voltage V3, the process proceeds to step S204, and when the voltage V is lower than the voltage V3, the process returns to step S202.
[0229] In step S204, the control circuit 153 evaluates dQ / dV. Here, the charging current is constant, so the dt / dV value is measured. The dt / dV value can be accumulated at any time during the charging process. The sliding average [dt / dV]mean and the maximum value [dt / dV]max of dt / dV are calculated using the accumulated data set of voltage V and time t.
[0230] Note that, as a value corresponding to dt / dV, for example, the time required for the voltage to change by a predetermined value may be calculated. The predetermined value may be, for example, 0.5 mV or more and 10 mV or less.
[0231] Next, in step S205, the moving average [dt / dV]mean is compared with the value obtained by multiplying the maximum value [dt / dV]max by the constant Rt. When the moving average [dt / dV]mean is less than the value obtained by multiplying the maximum value [dt / dV]max by the constant Rt, the process proceeds to step S206. When the moving average [dt / dV]mean is greater than the value obtained by multiplying the maximum value [dt / dV]max by the constant Rt, the process returns to step S204.
[0232] The time when the sliding average [dt / dV]mean is less than the value obtained by multiplying the maximum value [dt / dV]max by the constant Rt corresponds to, for example, the time when the voltage decreases from the local maximum value near V3 to (Rt×100)[%] of the local maximum value on the dt / dV curve.
[0233] In step S206, charging of the secondary battery is stopped.
[0234] Then, in step S299, the processing ends.
[0235] Notice, Figure 7 The flowchart shown shows an example of constant current charging, but when the charging current is not constant, for example, the value obtained by comparing the measurement time of the charge Q and the average value of the time near the charge Q with the maximum value of the charge Q multiplied by a constant can be replaced by comparing the sliding average [dt / dV]mean of dt / dV with the maximum value of the voltage [dt / dV]max multiplied by the constant Rt.
[0236] <Example 1 of voltage measurement circuit>
[0237] As an example of the voltage measurement circuit 151 included in the charger 201 , a voltage measurement circuit 151A will be described.
[0238] {Structure Example}
[0239] Figure 8 151A is a block diagram illustrating a configuration example of a voltage measuring circuit 151A.
[0240] like Figure 8 As shown, the voltage measurement circuit 151A includes a sample-and-hold circuit (S / H) 162, an S / H 174, a digital-to-analog conversion circuit (DAC) 172, a comparator 171, and a control unit 173. The control unit 173 includes a signal processing circuit 173a, a timing circuit 173b, and a register 173c. In addition, Figure 8 The secondary battery 121 and the control circuit 153 which are electrically connected to the voltage measurement circuit 151A in the power storage system 200 are shown.
[0241] Note that in the following description of the voltage measurement circuit 151A, unless otherwise specified, the voltage refers to a voltage based on the potential of the negative electrode of the secondary battery 121 .
[0242] The voltage measurement circuit 151A is used as a successive approximation analog-to-digital conversion circuit (ADC). In addition, the voltage measurement circuit 151A has a function of calculating the time (also called time difference or time differential) required for the input voltage to change a predetermined voltage value (for example, 1 mV) and outputting the time. Therefore, the voltage measurement circuit 151A may also be called a differentiator or a time measurement circuit, for example.
[0243] The S / H 162 has a function of acquiring (sampling) and holding the voltage Vbp of the positive electrode of the secondary battery 121 based on the signal SMP1. In addition, the S / H 162 has a function of supplying the held voltage Vin to the inverting input terminal of the comparator 171.
[0244] The S / H 174 has a function of acquiring and holding the voltage output from the DAC 172 based on the signal SMP2 . The S / H 174 also has a function of supplying the held voltage Vref to the non-inverting input terminal of the comparator 171 .
[0245] DAC 172 has a function of outputting an analog voltage according to the digital voltage data stored in register 173 c.
[0246] The comparator 171 has a function of comparing the magnitudes of the voltage Vin and the voltage Vref and outputting a voltage (H level) corresponding to digital data “1” or a voltage (L level) corresponding to digital data “0” according to the comparison result.
[0247] The signal processing circuit 173a has, for example, a function of performing various processes based on the output of the comparator 171 and the signal from the timing circuit 173b. As various processes, the signal processing circuit 173a has, for example, a function of updating the voltage data stored in the register 173c. In addition, the signal processing circuit 173a has, for example, a function of outputting the voltage data (data OUTV) stored in the register 173c and the time data (data OUTt) from the timing circuit 173b to the control circuit 153. In addition, the signal processing circuit 173a has, for example, a function of outputting a signal SMP2 for controlling the operation of the S / H 174. In addition, the signal processing circuit 173a has, for example, a function of outputting a signal WKUP and a signal SLEP for transmitting the operating state of the voltage measurement circuit 151A to the control circuit 153.
[0248] The timing circuit 173b has, for example, a function of performing various processes based on the signal from the signal processing circuit 173a and the signal STUP supplied from the control circuit 153. As various processes, the timing circuit 173b has, for example, a function of outputting a signal SMP1 for controlling the operation of the S / H 162. In addition, the timing circuit 173b has, for example, a function of measuring time. In the timing circuit 173b, in order to measure the time, for example, a counter (not shown) and an oscillator (not shown) can be used. And, for example, the count value of the counter can be time data.
[0249] The register 173c has a function of storing voltage data.
[0250] Each circuit constituting the voltage measurement circuit 151A (for example, S / H162, S / H174, DAC172, comparator 171, signal processing circuit 173a, timing circuit 173b, register 173c, etc.) includes a transistor containing silicon (Si transistor) in a channel formation region or a circuit containing Si transistors. That is, the voltage measurement circuit 151A is a semiconductor device. In addition, part or all of each circuit may also include a transistor containing an oxide semiconductor (OS transistor) in a channel formation region or a circuit containing OS transistors.
[0251] The band gap of the oxide semiconductor forming the channel of the OS transistor is above 2eV, so the OS transistor has the characteristic of extremely low off-state current (the current flowing between the source and the drain when the transistor is in the off state). The off-state current value of the OS transistor with a channel width of 1μm at room temperature can be 1aA (1×10 -18 A) or less, 1zA(1×10 -21 A) or less or 1yA(1×10 -24 Note that the off-state current value of a Si transistor with a channel width of 1 μm at room temperature is 1 fA (1×10 -15 A) or more and 1pA (1×10 -12 Therefore, it can be said that the off-state current of the OS transistor is about 10 bits lower than the off-state current of the Si transistor.
[0252] In addition, even in a high temperature environment, the off-state current of the OS transistor hardly increases. Specifically, even at an ambient temperature above room temperature and below 200°C, its off-state current hardly increases. In addition, even in a high temperature environment, the on-state current of the OS transistor is not easy to drop. On the other hand, in a high temperature environment, the on-state current of the Si transistor drops. In other words, the on-state current of the OS transistor is higher than that of the Si transistor in a high temperature environment. In addition, even at an ambient temperature above 125°C and below 150°C, the ratio of the on-state current to the off-state current of the OS transistor is large, so good switching operation can be performed. Therefore, a semiconductor device including an OS transistor operates stably and has high reliability even in a high temperature environment.
[0253] The semiconductor layer of the OS transistor preferably contains at least one of indium and zinc. In addition, the semiconductor layer of the OS transistor preferably contains, for example, indium, M (M is one or more selected from gallium, aluminum, yttrium, tin, silicon, boron, copper, vanadium, beryllium, titanium, iron, nickel, germanium, zirconium, molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten, magnesium and cobalt) and zinc. In particular, M is preferably one or more selected from gallium, aluminum, yttrium and tin.
[0254] In particular, as the semiconductor layer, it is preferable to use an oxide containing indium (In), gallium (Ga) and zinc (Zn) (also recorded as IGZO). Alternatively, as the semiconductor layer, an oxide containing indium (In), aluminum (Al) and zinc (Zn) (also recorded as IAZO) may be used. Alternatively, as the semiconductor layer, an oxide containing indium (In), aluminum (Al), gallium (Ga) and zinc (Zn) (also recorded as IAGZO) may be used.
[0255] When In-M-Zn oxide is used for the semiconductor layer, the atomic ratio of In in the In-M-Zn oxide is preferably equal to or greater than the atomic ratio of M. Examples of the atomic ratio of metal elements in such an In-M-Zn oxide include a composition of In:M:Zn=1:1:1 or in the vicinity thereof, a composition of In:M:Zn=1:1:1.2 or in the vicinity thereof, a composition of In:M:Zn=2:1:3 or in the vicinity thereof, a composition of In:M:Zn=3:1:2 or in the vicinity thereof, a composition of In:M:Zn=4:2:3 or in the vicinity thereof, a composition of In:M:Zn=4:2:4.1 or in the vicinity thereof, a composition of In:M:Zn=5:1:3 or in the vicinity thereof, a composition of In:M:Zn=5:1:6 or in the vicinity thereof, a composition of In:M:Zn=5:1:7 or in the vicinity thereof, a composition of In:M:Zn=5:1:8 or in the vicinity thereof, a composition of In:M:Zn=6:1:6 or in the vicinity thereof, or a composition of In:M:Zn=5:2:5 or in the vicinity thereof. In addition, the atomic ratio of In in the In-M-Zn oxide may be smaller than the atomic ratio of M in some cases. Examples of the atomic ratio of metal elements in the In-M-Zn oxide include a composition of In:M:Zn=1:3:2 or in the vicinity thereof, and a composition of In:M:Zn=1:3:4 or in the vicinity thereof. Note that the vicinity of the composition includes a range of ±30% of the desired atomic ratio.
[0256] For example, in a storage circuit (or storage device) using an OS transistor and a capacitor, since the off-state current of the OS transistor is extremely low, the charge stored in the capacitor can be retained for a long period of time. Therefore, by making the high and low potentials corresponding to the amount of charge retained in the capacitor correspond to digital data of "1" or "0", the storage circuit can store the data for a long period of time. Therefore, for example, a nonvolatile memory can also be configured.
[0257] An OS transistor or a storage circuit using an OS transistor may be provided in a part or all of the circuits constituting the voltage measurement circuit 151A. For example, by using an OS transistor as a transistor constituting the S / H 174, the voltage Vref held by the S / H 174 can be maintained for a long period of time even when the power supply to the DAC 172 is stopped. In addition, by providing a storage circuit using an OS transistor in the register 173c, for example, the voltage data in the register 173c can be stored for a long period of time even when the power supply to the register 173c is stopped.
[0258] The voltage measurement circuit 151A may be in a sleep mode until the input voltage changes by a predetermined voltage value, in other words, during a period when the change in the input voltage is less than the predetermined voltage value. By adopting the sleep mode, for example, the power supply to the DAC 172 and the register 173c may be stopped. In addition, for example, a part of the operation of the signal processing circuit 173a may be stopped by power gating or clock gating. In addition, when the voltage measurement circuit 151A is transferred to the sleep mode, the signal processing circuit 173a may output a signal SLEP.
[0259] The voltage measurement circuit 151A can also maintain the voltage Vref stored in the S / H 174 and continue to store the voltage data in the register 173c in the sleep mode. Therefore, the S / H 162 can be used to obtain the voltage Vbp and the comparator 171 can be used to compare the voltage Vin with the voltage Vref in the sleep mode.
[0260] When the voltage measurement circuit 151A changes the input voltage by a predetermined voltage value in the sleep mode, it can recover (wake up) from the sleep mode by changing the output of the comparator 171. When waking up, for example, the power supply to the DAC 172 and the register 173c can be restarted. In addition, the operation of the signal processing circuit 173a can be restarted. In addition, when waking up, the signal processing circuit 173a can output the signal WKUP.
[0261] In addition, for example, an OS transistor or a storage circuit using an OS transistor may be provided in a part of the control circuit 153. In addition, for example, in the control circuit 153, a part of the operation can be stopped by power gating or clock gating by supplying a signal SLEP, and the operation can be restarted by supplying a signal WKUP.
[0262] {Working Example}
[0263] Fig. 9 151A is a flowchart illustrating an operation example of the voltage measurement circuit 151A.
[0264] First, in step S300, the process starts by supplying a signal STUP from the control circuit 153. Note that the secondary battery 121 is charged by a constant current.
[0265] Next, in step S301 to step S303, the analog input voltage is converted into digital voltage data and stored in register 173c. In step S301 to step S303, each bit from the most significant bit to the least significant bit is compared in sequence to determine "1" or "0".
[0266] In step S301, register 173c is initialized. In other words, only the highest bit of register 173c is set to "1", and all other bits are set to "0". For example, when register 173c is 16 bits, the data of register 173c is "1000000000000000". DAC172 is used to convert the data of register 173c into an analog voltage, and S / H174 is used to maintain the voltage as voltage Vref. In addition, S / H162 is used to obtain the voltage Vbp of the positive electrode of the secondary battery 121, and it is maintained as voltage Vin. After step S301 is completed, step S302 is entered.
[0267] In step S302, it is determined whether the voltage Vbp (the voltage Vin obtained and held by S / H162 in step S301) is greater than the voltage Vref. That is, when the voltage Vin is greater than the voltage Vref, the comparison bit is determined to be "1" in step S3021. Alternatively, when the voltage Vin is less than the voltage Vref, the comparison bit is determined to be "0" in step S3022. After step S3021 or step S3022 is completed, the process proceeds to step S303.
[0268] In step S303, it is determined whether the data of register 173c is determined to the lowest bit. If the data of register 173c is not determined to the lowest bit, the lower bit of register 173c is set to "1" and the process returns to step S302. Alternatively, if the data of register 173c is determined to the lowest bit, the process proceeds to step S304. For example, if register 173c is 16 bits, the data of register 173c can be determined to the lowest bit by repeating steps S302 to S303 16 times.
[0269] Next, in step S304, the voltage data of register 173c and the time data (count value of the counter) of timing circuit 173b are output, and the state is transferred to the sleep mode. At this time, the signal SLEP is output. Here, before transferring to the sleep mode, the data of register 173c is updated to data with a specified data value (for example, a data value equivalent to 1mV). As a result, the voltage output from DAC172 is increased by a specified voltage value (for example, 1mV), and the voltage is maintained in S / H174. In other words, the voltage Vref maintained in S / H174 is increased by a specified voltage value, and then transferred to the sleep mode. After step S304 is completed, step S311 is entered.
[0270] Next, in steps S311 to S314 , the time required for the input voltage to change by a predetermined voltage value is calculated and the time is output.
[0271] In step S311, the voltage Vbp is obtained by the S / H 162 at regular intervals (eg, 100 ms) and is maintained as the voltage Vin. Furthermore, the voltage Vin and the voltage Vref are compared using the comparator 171. After step S311 is completed, the process proceeds to step S312.
[0272] In step S312, the voltage Vbp (the voltage Vin obtained and held by S / H 162 in step S311) is higher than the voltage Vref, and thus the output of the comparator 171 changes (for example, from the H level to the L level). As a result, the sleep mode is restored (wake up). At this time, the signal WKUP is output. After the sleep mode is restored, the voltage data of the register 173c and the time data of the timing circuit 173b are output. After step S312 is completed, the process proceeds to step S313.
[0273] In step S312, the difference between the count value of the counter at the last output and the count value of the counter at the current output may be calculated as time data, thereby outputting time difference data. In other words, the time difference data is data on the time required for the input voltage to change by a predetermined voltage value.
[0274] In step S313, it is determined whether the condition for stopping charging is satisfied. As the condition for stopping charging, for example, the conditions described in the above-mentioned example 1 to the example 3 of the charging method can be appropriately used. When the condition for stopping charging is satisfied, the process ends in step S399. Alternatively, when the condition for stopping charging is not satisfied, the process proceeds to step S314.
[0275] In step S399 , it is preferable to send a signal indicating that the condition for stopping charging is satisfied to the control circuit 153 so as to stop the constant current charging of the secondary battery 121 by the charger 201 in the power storage system 200 .
[0276] In step S314, the data of register 173c is updated to data with a predetermined value. As a result, the voltage output from DAC172 is increased by a predetermined voltage value, and the voltage is held in S / H174. In other words, the voltage Vref held in S / H174 is increased by a predetermined voltage value. Then, the signal SLEP is outputted, and the sleep mode is transferred again. After step S314 is completed, the process returns to step S311.
[0277] As described above, the voltage measurement circuit 151A can calculate the time required for the voltage Vbp of the secondary battery 121 to change by a predetermined voltage value (for example, 1 mV) and output the time. In addition, the voltage measurement circuit 151A can be in a sleep mode during the period until the voltage Vbp changes by a predetermined voltage value, in other words, during the period when the change in the voltage Vbp is less than the predetermined voltage value. By putting the voltage measurement circuit 151A in the sleep mode, for example, the power supply to the DAC 172 and the register 173c can be stopped and part of the operation of the signal processing circuit 173a can be stopped. As a result, the power consumption of the voltage measurement circuit 151A can be reduced.
[0278] Note that in the above description, for example, the time required for the voltage Vbp to increase by a predetermined voltage value when the secondary battery 121 is charged can be calculated. On the other hand, for example, the time required for the voltage Vbp to decrease by a predetermined voltage value when the secondary battery 121 is discharged can also be calculated. In this case, for example, in step S304 and step S314, the data of the register 173c can be updated to data that decreases the predetermined data value. In other words, the voltage Vref held in the S / H 174 can be decreased by a predetermined voltage value.
[0279] By including the voltage measurement circuit 151A in a charger applicable to the power storage system according to one embodiment of the present invention, power consumption can be reduced.
[0280] <Example 2 of voltage measurement circuit>
[0281] As another configuration example of the voltage measurement circuit 151 included in the charger 201, a voltage measurement circuit 151B is described. The voltage measurement circuit 151B is a modified example of the voltage measurement circuit 151A described above. Therefore, in order to reduce repeated descriptions, the differences between the voltage measurement circuit 151B and the voltage measurement circuit 151A are mainly described. In addition, the description of the voltage measurement circuit 151A described above can be appropriately referred to.
[0282] {Structure Example}
[0283] Fig.10 is a block diagram illustrating a configuration example of the voltage measuring circuit 151B.
[0284] like Fig.10 As shown, the voltage measurement circuit 151B includes an integration circuit 175 and a selection circuit 176 in addition to the structure of the voltage measurement circuit 151A. In addition, the voltage measurement circuit 151B is different from the voltage measurement circuit 151A in that the voltage measurement circuit 151B may not include the S / H 162. In addition, the voltage measurement circuit 151B includes an oscillator 173d, an AND circuit 173e, and a counter 173f in a timing circuit 173b in addition to the structure of the voltage measurement circuit 151A in the control unit 173.
[0285] The voltage measurement circuit 151B is used as a dual-integration analog-to-digital conversion circuit (ADC). In addition, the voltage measurement circuit 151B has a function of calculating the time (also called time difference or time differential) required for the input voltage to change a predetermined voltage value (for example, 1 mV) and outputting the time. Therefore, the voltage measurement circuit 151B can also be called a differentiator or a time measurement circuit, for example.
[0286] The selection circuit 176 has a function of supplying any one of the voltage Vin (voltage Vbp) and the voltage Vref to the input terminal of the integration circuit 175 according to the signal SEL.
[0287] The integration circuit 175 has a function of integrating a voltage (either the voltage Vin or the voltage Vref) supplied to an input terminal and supplying the integrated voltage Vin2 to an output terminal.
[0288] The integration circuit 175 includes an operational amplifier 175a, a resistor 175r, and a capacitor 175c. In the integration circuit 175, the inverting input terminal of the operational amplifier 175a is electrically connected to one terminal of the resistor 175r and one terminal of the capacitor 175c. The non-inverting input terminal of the operational amplifier 175a is electrically connected to a wiring to which the voltage Vref2 is supplied. The output terminal of the operational amplifier 175a is electrically connected to the other terminal of the capacitor 175c and the output terminal of the integration circuit 175. The other terminal of the resistor 175r is electrically connected to the input terminal of the integration circuit 175. In addition, in the integration circuit 175, it is preferable to provide a switch (not shown) having a function of making one terminal and the other terminal of the capacitor 175c conductive or non-conductive.
[0289] The output terminal of the integration circuit 175 is electrically connected to the inverting input terminal of the comparator 171. That is, the voltage Vin2 supplied to the output terminal of the integration circuit 175 is supplied to the inverting input terminal of the comparator.
[0290] The comparator 171 has a function of comparing the magnitudes of a voltage Vin2 supplied to an inverting input terminal and a voltage Vref2 supplied to a non-inverting input terminal and outputting an H level or an L level according to the comparison result.
[0291] The oscillator 173d has a function of outputting a clock pulse.
[0292] The AND circuit 173 e has a function of calculating a logical product of a clock pulse supplied from the oscillator 173 d and a signal supplied from the signal processing circuit 173 a and outputting a signal CCK.
[0293] The counter 173f has a function of counting the number of clock pulses supplied as the signal CCK. In addition, the counter 173f has a function of resetting the count value according to the signal CRE. In addition, the counter 173f has a function of outputting the count value (data OUTC).
[0294] The signal processing circuit 173a has, for example, a function of outputting a signal SEL for controlling the operation of the selection circuit 176. In addition, the signal processing circuit 173a has, for example, a function of controlling whether to supply the clock pulse output from the oscillator 173d to the counter 173f using the AND circuit 173e. In addition, the signal processing circuit 173a has, for example, a function of outputting a signal CRE for controlling the operation of the counter 173f. In addition, the signal processing circuit 173a has, for example, a function of outputting voltage data (data OUTV) based on the data OUTC output from the counter 173f to the control circuit 153.
[0295] The register 173c may have a function of storing the data OUTC output from the counter 173f. In order to store the data OUTC, for example, a storage circuit (not shown) may be provided in the register 173c.
[0296] Similar to the voltage measurement circuit 151A described above, an OS transistor or a memory circuit using an OS transistor may be provided in a part or all of the circuits constituting the voltage measurement circuit 151B.
[0297] During a period until the input voltage is changed by a predetermined voltage value, in other words, during a period when the change in the input voltage is smaller than the predetermined voltage value, the voltage measurement circuit 151B may be in the sleep mode similarly to the voltage measurement circuit 151A.
[0298] The voltage measurement circuit 151B can perform analog-digital conversion (A / D conversion) described later also in the sleep mode.
[0299] {Working Example}
[0300] Fig.11151B is a schematic diagram for explaining analog-to-digital conversion (A / D conversion) in the voltage measurement circuit 151B.
[0301] Fig.11 FIG. 2 shows the time variation of the voltage Vin2 output from the integration circuit 175 when performing A / D conversion. Fig.11 In FIG. 1 , the dashed line (vc2) indicates a case where the voltage Vin is higher than the solid line (vc1). In addition, the dotted line (vc3) indicates a case where the voltage Vref is higher than the solid line (vc1).
[0302] In the voltage measurement circuit 151B, in order to perform A / D conversion, the voltage Vref and the voltage Vref2 are set so as to satisfy the voltage Vin> the voltage Vref2> the voltage Vref. In addition, as an initial state, the voltage Vin2=the voltage Vref2 is satisfied. In addition, the count value of the counter 173f is reset to 0. In addition, the resistance value of the resistor 175r is Rv, and the electrostatic capacitance value of the capacitor 175c is Cv.
[0303] In the description of this working example, sometimes changing the voltage Vin so that the potential difference between the voltage Vin and the voltage Vref2 becomes larger (or smaller) means increasing (or decreasing) the voltage Vin. Also, sometimes changing the voltage Vref so that the potential difference between the voltage Vref and the voltage Vref2 becomes larger (or smaller) means increasing (or decreasing) the voltage Vref.
[0304] First, the selection circuit 176 is controlled to input the voltage Vin to the integration circuit 175. Here, the voltage Vin2 decreases with a slope of "-(voltage Vin-voltage Vref2) / (Cv×Rv)".
[0305] Next, after a certain period (period tta) has passed, the selection circuit 176 is controlled to input the voltage Vref to the integration circuit 175. Here, the voltage Vin2 rises according to the slope of "-(voltage Vref-voltage Vref2) / (Cv×Rv)". At this time, the clock pulse output from the oscillator 173d is supplied to the counter 173f. Here, the counting of the counter 173f starts.
[0306] Next, the voltage Vin2 rises until it reaches the voltage Vref2, whereby the output of the comparator 171 changes (for example, from the H level to the L level) and at this time, the count value of the counter 173f is output.
[0307] The count value output from the counter 173f is a value counted in a period ttb (period ttb1, period ttb2, or period ttb3) from when the voltage Vref is input to the integration circuit 175 until the voltage Vin2 reaches the voltage Vref2, and has a positive correlation with the voltage Vin input to the integration circuit 175.
[0308] For example, when the voltage Vin is made higher than the solid line (vc1), as shown by the dotted line (vc2), the falling slope of the voltage Vin2 in the period tta becomes larger. As a result, the period ttb2>period ttb1 is satisfied, and the count value of the counter 173f becomes higher. In this way, the count value of the counter 173f is based on the voltage Vin.
[0309] Here, for example, when the voltage Vref is made higher than the solid line (vc1), as shown by the dotted line (vc3), the rising slope of the voltage Vin2 in the period ttb becomes larger. As a result, the period ttb3 < period ttb1 is satisfied, and the count value of the counter 173f becomes lower. As described later, by using the above content, the time required for the input voltage Vin to change by a predetermined voltage value can be calculated.
[0310] Fig.12 151B is a flowchart illustrating an example of the operation of the voltage measurement circuit 151B.
[0311] First, in step S400, the process starts by supplying a signal STUP from the control circuit 153. Note that the secondary battery 121 is charged by a constant current.
[0312] In addition, as an initial state, voltage Vin2 = voltage Vref2 is satisfied. For example, control is performed so that a switch provided between one terminal and the other terminal of capacitor 175c is turned on.
[0313] Next, in step S401, the analog input voltage is converted into digital voltage data. In step S401, the above-mentioned A / D conversion is performed to obtain data OUTC based on the voltage Vbp (voltage Vin). At this time, for example, the switch provided between one terminal and the other terminal of the capacitor 175c is controlled to be in a non-conductive state. The data OUTC obtained here is stored as a prescribed count value. For example, the prescribed count value can also be stored in a storage circuit for storing data OUTC in the register 173c. After step S401 is completed, step S402 is entered.
[0314] Next, in step S402, the voltage data based on the data OUTC and the time data of the timing circuit 173b are output, and the mode is transferred to the sleep mode. At this time, the signal SLEP is output. Here, before transferring to the sleep mode, the data of the register 173c is updated to data with a specified data value (for example, a data value equivalent to 1mV). As a result, the voltage output from the DAC172 is increased by a specified voltage value (for example, 1mV), and the voltage is maintained in the S / H174. In other words, the voltage Vref maintained in the S / H174 is increased by a specified voltage value, and then the mode is transferred to the sleep mode. After the end of step S402, step S411 is entered.
[0315] Next, in steps S411 to S414, the time required for the input voltage to change by a predetermined voltage value is calculated and the time is output.
[0316] In step S411, the A / D conversion is performed at regular intervals (e.g., 100 ms) to obtain data OUTC based on voltage Vbp. At this time, since voltage Vref is increased by a predetermined voltage value in the previous step, data OUTC is lower than a predetermined count value even if voltage Vbp is the same value. After step S411 is completed, step S412 is entered.
[0317] In step S412, the voltage Vbp is increased by a predetermined voltage value, so that the data OUTC becomes a predetermined count value. Thus, the sleep mode is restored (wake up). At this time, the signal WKUP is output. After the sleep mode is restored, the voltage data based on the data OUTC and the time data of the timing circuit 173b are output. After step S412 is completed, step S413 is entered.
[0318] In step S412, similarly to the voltage measurement circuit 151A, the time difference between the last output and the current output may be output as time data. That is, the time difference data is the time required for the input voltage to change to a predetermined voltage value.
[0319] In step S413, it is determined whether the condition for stopping charging is satisfied. As the condition for stopping charging, for example, the conditions described in the above-mentioned charging method example 1 to the charging method example 3 can be appropriately used. When the condition for stopping charging is satisfied, the process ends in step S499. Alternatively, when the condition for stopping charging is not satisfied, the process proceeds to step S414.
[0320] In step S414, the data in register 173c is updated to data that increases a specified data value. As a result, the voltage output from DAC172 increases by a specified voltage value, and this voltage is held in S / H174. In other words, the voltage Vref held in S / H174 is increased by a specified voltage value. Then, the output signal SLEP is output, and the system returns to the sleep mode again. After step S414 ends, the process returns to step S411.
[0321] As described above, the voltage measurement circuit 151B can calculate the time required for the voltage Vbp of the secondary battery 121 to change by a specified voltage value (e.g., 1 mV) and output this time. In addition, the voltage measurement circuit 151B can be in the sleep mode during the period until the voltage Vbp changes by a specified voltage value, that is, during the period when the change in the voltage Vbp is less than the specified voltage value. By putting the voltage measurement circuit 151B in the sleep mode, for example, the power supply to DAC172 and register 173c can be stopped and a part of the operation of the signal processing circuit 173a can be stopped. Thereby, the power consumption of the voltage measurement circuit 151B can be reduced.
[0322] Note that in the above description, for example, the time required for the voltage Vbp to increase by a specified voltage value during the charging of the secondary battery 121 can be calculated. On the other hand, for example, the time required for the voltage Vbp to decrease by a specified voltage value during the discharging of the secondary battery 121 can also be calculated. In this case, for example, in steps S402 and S414, the data in register 173c may be updated to data that decreases the specified data value. In other words, the voltage Vref held in S / H174 may be decreased by a specified voltage value.
[0323] By including the voltage measurement circuit 151B in the charger of an energy storage system that can be used in one embodiment of the present invention, the power consumption can be reduced.
[0324] <Estimation of SOH>
[0325] A charger according to one embodiment of the present invention preferably has a function of estimating the SOH (State Of Health) of the secondary battery. SOH is an index that represents the chargeable capacity at a certain point in time with respect to the chargeable capacity when the battery is in an unused state. Assuming that the chargeable capacity when the secondary battery is in an unused state is 100, as the degradation of the secondary battery progresses, SOH is represented by a value less than 100, and its unit is “%”.
[0326] Regarding the extreme value on the dQ / dV-V curve analyzed in the above example, the intensity of the extreme value (e.g., the height of the upwardly convex peak) sometimes decreases. This decrease in intensity sometimes results from the fact that the phase change corresponding to this extreme value in the positive electrode active material is not easily generated, and for example, it sometimes has a correlation with SOH.
[0327] The charger according to one embodiment of the present invention preferably has a function of estimating SOH by observing the intensity of an extreme value on a dQ / dV-V curve.
[0328] In addition, regarding the extreme value on the dQ / dV-V curve analyzed in the above example, the voltage as the extreme value and the full discharge capacity after charging (dischargeable capacity of the secondary battery) are sometimes correlated. The charger of one embodiment of the present invention preferably has a function of estimating the dischargeable capacity of the secondary battery by observing the intensity of the extreme value on the dQ / dV-V curve.
[0329] <Charging control based on operating temperature>
[0330] Charger 201 preferably uses temperature to control charging.
[0331] The control circuit 153 preferably changes the charging condition according to the ambient temperature of the secondary battery measured by the temperature sensor TS.
[0332] The storage circuit in the control circuit 153 preferably has, for example, a table that associates the ambient temperature of the secondary battery with the charging conditions.
[0333] In addition, the storage circuit in the control circuit 153 preferably stores the charging characteristics associated with the ambient temperature of the secondary battery. The charging characteristics may be past measurement values of the secondary battery 121, measurement values of other secondary batteries having the same characteristics, or waveforms obtained by calculation. Figure 5 and Figure 6 In the flowchart shown, these measured values can also be used to estimate the extreme value (peak). For example, machine learning can be used for the estimation.
[0334] The control circuit 153 may also use the charging characteristics of the secondary battery stored in the storage circuit in the analysis of the extreme values on the differential curve of the voltage and the electric quantity. Here, as the charging characteristics, for example, a capacity-voltage curve, a voltage-dQ / dV curve, a ΔV-t curve, an impedance characteristic, etc. may be used.
[0335] As the temperature sensor TS, for example, a temperature measuring resistor (for example, platinum, nickel, or copper), a thermistor (PTC (Positive Temperature Coefficient) thermistor or NTC (Negative Temperature Coefficient) thermistor), a thermocouple, or an IC temperature sensor can be used. Alternatively, as the temperature sensor TS, for example, a structure using a semiconductor temperature sensor (for example, a silicon diode temperature sensor, etc.) or a structure using a bandgap circuit can be used.
[0336] NTC thermistors (NTC elements) have the characteristic that the resistance value decreases slowly as the temperature rises. Therefore, they can be used, for example, for fine temperature detection or simple inrush current suppression. In addition, PTC thermistors (PTC elements) have the characteristic that the resistance value increases sharply when a certain temperature is exceeded. Therefore, they can be used, for example, for overheat detection, overcurrent protection, or inrush current suppression.
[0337] <Example 2 of Power Storage System>
[0338] Figure 1B The charger 201 is shown to Figure 1A The additional structure shown includes a detection circuit 185 having the function of detecting overcharging and overdischarging, a detection circuit 186 having the function of detecting charging overcurrent and discharging overcurrent, a short circuit detection circuit SD, a micro short circuit detection circuit MSD, transistors 140 and transistors 150.
[0339] Figure 1B The charger 201 shown has the function of suppressing overcharge, overdischarge, charge overcurrent, discharge overcurrent, short circuit, micro short circuit, etc., and can be used as a protection circuit for a secondary battery. Here, micro short circuit refers to a very small short circuit inside a secondary battery. It is not a state where charging and discharging cannot be performed due to a short circuit between the positive and negative electrodes of the secondary battery, but a phenomenon in which a short circuit current slightly flows in a very small short circuit portion. Even in a short time and in a tiny portion, a large voltage change may occur.
[0340] As the transistor 140 and the transistor 150 , for example, a transistor called a power MOSFET can be used.
[0341] The control circuit 153 has a function of supplying signals to the gates of the transistor 140 and the transistor 150 respectively to block the current flowing through the secondary battery 121 .
[0342] The detection circuit 185 monitors the voltage of the secondary battery, and when overcharge or overdischarge is detected, a signal indicating the detection can be provided to the control circuit 153. The control circuit receives the signal and provides the signal to at least one of the gates of the transistor 140 and the transistor 150, thereby blocking the current flowing through the secondary battery 121.
[0343] The detection circuit 186 monitors the current of the secondary battery 121, and when an overcurrent is detected during charging or discharging, a signal indicating the detection can be provided to the control circuit 153. The control circuit receives the signal and provides the signal to at least one of the gates of the transistor 140 and the transistor 150, thereby blocking the current flowing through the secondary battery 121.
[0344] The overcharge detected in the detection circuit 185 can also be detected using the extreme value of the charging voltage versus time curve (e.g., ΔV-t curve) shown above or the extreme value of the voltage differential curve (dQ / dV curve) of the charging amount. Alternatively, the overcharge detected in the detection circuit 185 can also be detected by using a comparison circuit to compare with a predetermined voltage value. As a predetermined voltage value, a value that varies depending on the ambient temperature of the secondary battery can also be used. The voltage value according to the ambient temperature of the secondary battery is stored in, for example, a storage circuit of the control circuit 153.
[0345] exist FIG. 13A to FIG. 13C In the example of the power storage system 200 shown, a charger 201 is connected to each of the m secondary batteries 121 connected in series. Fig.13A An example of a power storage system 200 is shown when m is an integer greater than or equal to 4, and among the m secondary batteries 121, secondary battery 121 (1), secondary battery 121 (2), secondary battery 121 (3), and secondary battery 121 (m) are shown as the first, second, third, and mth secondary batteries 121, and other secondary batteries are omitted. Fig. 13B An example of the power storage system 200 when m is 3 is shown. Fig. 13C An example of the power storage system 200 when m is 2 is shown.
[0346] The m chargers 201 may also share some functions. For example, the detection circuit 185 in the charger 201 may also detect overcharge in the voltage between the terminal 124 electrically connected to the positive electrode of the secondary battery 121 (1) and the terminal 125 electrically connected to the negative electrode of the secondary battery 121 (m). For example, the detection circuit 186 and the short circuit detection circuit SD in the charger 201 may also detect overcharge or short circuit based on the current between the terminal 124 and the terminal 125.
[0347] The power storage system 200 can independently control the m secondary batteries 121 using the chargers 201 connected thereto respectively. In this case, the secondary battery 121 that is charged first is configured to allow the current to flow through a path connected in parallel with the secondary battery 121 after charging is completed, such as a transistor, a resistor, or a diode connected in parallel with the secondary battery 121. Therefore, the charger 201 preferably has a switch that switches the secondary battery 121 and the path as a current path.
[0348] In the case of the m secondary batteries 121 connected in series in the power storage system 200, the total voltage of the m secondary batteries (for example, Fig.13A In this case, m times the voltage value may be used as the voltage used for charge control.
[0349] This embodiment mode can be combined with the description of other embodiment modes and the like as appropriate.
[0350] (Implementation Method 2)
[0351] In this embodiment, an example of a secondary battery which is one embodiment of the present invention is described.
[0352] The secondary battery according to one embodiment of the present invention preferably includes a positive electrode, a negative electrode, and an electrolyte.
[0353] <Positive electrode>
[0354] A positive electrode according to one embodiment of the present invention includes a positive electrode active material.
[0355] Reference FIG. 14A to FIG. 23C A positive electrode active material that can be used for a secondary battery according to one embodiment of the present invention and a method for producing the same will be described.
[0356] [Positive electrode active material]
[0357] Fig.14A and Fig. 14B This is a cross-sectional view of a positive electrode active material 100 that can be used in a secondary battery according to one embodiment of the present invention. Fig. 14C and Fig.14D Show enlarged Fig.14A The diagram near AB in . Fig.14E and Fig.14F Show enlarged Fig.14A Figure near the CD in .
[0358] like FIG. 14A to FIG. 14F As shown, the positive electrode active material 100 includes a surface portion 100a and a bulk body 100b. In the above figure, the boundary between the surface portion 100a and the bulk body 100b is indicated by a dotted line. Fig. 14B A portion of the grain boundary 101 is shown by a dashed line.
[0359] In addition, in this specification, etc., the positive electrode active material 100 refers to a compound containing transition metal and oxygen in which lithium can be embedded and released. Therefore, the interface between the region where the transition metal M (e.g., Co, Ni, Mn, Fe, etc.) or oxygen that is oxidized and reduced with the embedding and release of lithium exists and the region where they do not exist is called the surface of the positive electrode active material. The surface generated by at least one of sliding, cracks and fissures can also be called the surface of the positive electrode active material.
[0360] In addition, in this specification, etc., the surface of the positive electrode active material in the line analysis of EDX (Energy Dispersive X-ray Spectroscopy) refers to the following measurement point: the measured value of 50% of the average value of the detected amount closest to the bulk of the above-mentioned transition metal or oxygen. Alternatively, the above-mentioned surface refers to the following intersection: the intersection of the tangent drawn on the intensity distribution of the EDX line analysis of the above-mentioned transition metal or oxygen by the tangent method and the axis in the depth direction. In addition, when the measured values of 50% of the average value of the detected amount closest to the bulk of the above-mentioned transition metal and oxygen are different, the measured value located further outside can be used. The surface of the positive electrode active material in the STEM (Scanning Transmission Electron Microscope) image, etc. refers to the boundary between the area where the image derived from the crystal structure of the positive electrode active material is observed and the area where the image is not observed, which is the outermost area of the area where the atomic column derived from the nucleus of the metal element whose atomic number is larger than lithium is confirmed. Alternatively, the surface refers to the intersection of a tangent line drawn on the distribution of brightness from the surface to the bulk in the STEM image and the axis in the depth direction. The surface in the STEM image or the like can also be determined by referring to an analysis with a higher spatial resolution.
[0361] In addition, in this specification, etc., the surface portion 100a of the positive electrode active material 100 refers to a region within 10nm from the surface in a vertical or substantially vertical manner from the surface to the inside. Alternatively, it refers to a region within 50nm. Alternatively, it refers to a region within 5nm. The surface portion is synonymous with the vicinity of the surface, the region near the surface, or the shell. Substantially vertical means 80° or more and 100° or less.
[0362] In addition, a region deeper than the surface layer portion 100a in the positive electrode active material is referred to as a bulk body 100b. The bulk body 100b is synonymous with an interior or a core.
[0363] In addition, the surface of the positive electrode active material 100 refers to the surface of the composite oxide having the above-mentioned surface layer 100a, the bulk 100b and the convex portion 103. The positive electrode active material 100 does not contain carbonates, hydroxyls, etc. chemically adsorbed after the positive electrode active material 100 is manufactured. In addition, the electrolyte, organic solvent, adhesive, conductive agent or compound derived from them attached after the positive electrode active material 100 is manufactured is not included in the positive electrode active material 100. In addition, the surface of the positive electrode active material 100 in the cross-sectional STEM image, etc. refers to the boundary between the area where the coupling image of the electron beam is observed and the area where the coupling image is not observed, and refers to the outermost side of the area where the bright spot of the nucleus of the metal element with an atomic number greater than lithium is confirmed. The surface in the cross-sectional STEM image, etc. can also be judged based on the analysis results of higher spatial resolution analysis, such as EELS (Electron Energy Loss Spectroscopy: Electron Energy Loss Spectroscopy).
[0364] In addition, the grain boundary 101 refers to, for example: a portion where the particles of the positive electrode active material 100 are bonded together; a portion where the crystal orientation changes inside the positive electrode active material 100, that is, a portion where the bright lines and dark lines in the STEM image are repeatedly discontinuous, a portion containing multiple crystal defects, a portion with a disordered crystal structure, etc. In addition, a crystal defect refers to a defect observable through a cross-sectional TEM image, a cross-sectional STEM image, etc., that is, a structure where other atoms enter the lattice, a void, etc. The grain boundary 101 can be said to be a type of surface defect. In addition, the vicinity of the grain boundary 101 refers to an area within 10 nm from the grain boundary 101.
[0365] {Contains elements}
[0366] The positive electrode active material 100 includes lithium, transition metal M, oxygen, and additive element A. Alternatively, the positive electrode active material 100 may include a material in which the additive element A is added to a composite oxide (LiMO2) containing lithium and transition metal M. Note that the composition of the composite oxide is not strictly limited to Li:M:O=1:1:2. In addition, the positive electrode active material to which the additive element A is added is sometimes also referred to as a composite oxide.
[0367] In order to maintain charge neutrality even when lithium ions are embedded and released, the positive electrode active material of the lithium ion secondary battery needs to contain a transition metal that can be oxidized and reduced. Preferably, the positive electrode active material 100 of one embodiment of the present invention mainly uses cobalt as the transition metal M for redox reaction. In addition to cobalt, at least one or two or more selected from nickel and manganese can also be used. Preferably, cobalt accounts for more than 75 atomic% of the transition metal M contained in the positive electrode active material 100, preferably more than 90 atomic%, and more preferably more than 95 atomic%, because there are many advantages at this time, such as: it can be synthesized more easily; easy to handle; has good cycle characteristics; etc.
[0368] In addition, compared with composite oxides such as lithium nickelate (LiNiO2) in which nickel accounts for more than half of the transition metal M, when cobalt accounts for more than 75 atomic%, preferably more than 90 atomic%, and more preferably more than 95 atomic% of the transition metal M in the positive electrode active material 100, Li x The smaller the x in CoO2, the better the stability. This may be because cobalt is less affected by the distortion caused by the Jan-Taylor effect than nickel. The intensity of the Jan-Taylor effect in transition metal compounds varies according to the number of electrons in the d orbital of the transition metal. Layered rock salt-type composite oxides such as lithium nickelate, in which octahedrally coordinated low-spin nickel (III) accounts for more than half of the transition metal M, are greatly affected by the Jan-Taylor effect, and the layers composed of nickel and oxygen octahedra are prone to distortion. Therefore, there is a greater concern about the collapse of the crystal structure during the charge and discharge cycle. In addition, nickel ions are larger than cobalt ions and are close to the size of lithium ions. Therefore, in layered rock salt-type composite oxides such as lithium nickelate, in which nickel accounts for more than half of the transition metal M, there is a problem of cation mixing of nickel and lithium.
[0369] On the other hand, when nickel is used as the transition metal M contained in the positive electrode active material 100 at 33 atomic %, preferably at least 60 atomic %, and more preferably at least 80 atomic %, the raw material is sometimes cheaper than in the case of a higher cobalt content, and the discharge capacity per unit weight is sometimes improved, so it is preferred.
[0370] As the additive element A included in the positive electrode active material 100, one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine and beryllium are preferably used. In addition, the sum of transition metals in the additive element A is preferably less than 25 atomic%, more preferably less than 10 atomic%, and further preferably less than 5 atomic%.
[0371] That is, the positive electrode active material 100 may include lithium cobalt oxide added with magnesium and fluorine, lithium cobalt oxide added with magnesium, fluorine and titanium, lithium cobalt oxide added with magnesium, fluorine and aluminum, lithium cobalt oxide added with magnesium, fluorine and nickel, lithium cobalt oxide added with magnesium, fluorine, nickel and aluminum, etc.
[0372] As described below, the crystal structure of the positive electrode active material 100 is further stabilized by the addition of the element A. Note that in this specification and the like, the added element A is synonymous with a mixture or a part of a raw material.
[0373] As the additive element A, it is not necessary to contain magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine or beryllium.
[0374] For example, by manufacturing a positive electrode active material 100 that does not substantially contain manganese, the above advantages such as being easy to synthesize, easy to handle, having good cycle characteristics, etc. can be improved. The weight of manganese contained in the positive electrode active material 100 is preferably 600 ppm or less, and more preferably 100 ppm or less. The weight of manganese can be analyzed, for example, by GD-MS (Glow Discharge Mass Spectrometry).
[0375] {Crystal Structure}
[0376] < <Li x When x is 1 in CoO2 >>
[0377] Preferably, the positive electrode active material 100 of one embodiment of the present invention is in a discharged state, that is, in a Li x When x=1 in CoO2, it has a layered rock salt type crystal structure belonging to the space group R-3m. The layered rock salt type composite oxide has a large discharge capacity and a two-dimensional lithium ion diffusion path, which is suitable for the insertion and extraction reaction of lithium ions, and is excellent as a positive electrode active material for secondary batteries. Therefore, the bulk 100b that occupies most of the volume of the positive electrode active material 100 preferably has a layered rock salt type crystal structure. Fig.17 In the figure, R-3m O3 represents a layered rock salt type crystal structure.
[0378] On the other hand, the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably reinforces the layered structure composed of the transition metal M and the octahedron of the bulk 100b so as to avoid the collapse of the layered structure even if a lot of lithium is released from the positive electrode active material 100 due to charging. Alternatively, the surface portion 100a is preferably used as a barrier film of the positive electrode active material 100. Alternatively, the surface portion 100a of the outer peripheral portion of the positive electrode active material 100 preferably reinforces the positive electrode active material 100. Here, reinforcement refers to at least one of suppressing the structural changes of the surface portion 100a and the bulk 100b of the positive electrode active material 100 such as the release of oxygen and suppressing the oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.
[0379] Therefore, the surface portion 100a preferably has a composition and crystal structure different from those of the bulk 100b. In addition, the composition and crystal structure of the surface portion 100a at room temperature (25°C) are preferably more stable than those of the bulk 100b. For example, at least a portion of the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably has a rock salt type crystal structure. Alternatively, the surface portion 100a preferably has both a layered rock salt type crystal structure and a rock salt type crystal structure. Alternatively, the surface portion 100a preferably has the characteristics of both a layered rock salt type and a rock salt type crystal structure.
[0380] The surface part 100a is the area where lithium ions are first separated during charging, and is also the area where the lithium concentration is easily lower than that of the bulk 100b. In addition, it can also be said that some of the bonds in the atoms on the surface of the positive electrode active material 100 including the surface part 100a are cut. Therefore, the surface part 100a is likely to become an unstable area where crystal structure degradation is likely to begin. On the other hand, as long as the surface part 100a can be sufficiently stabilized, the lithium ion concentration in the lithium ion battery can be reduced. x When x in CoO2 is small, for example, when x is less than 0.24, the layered structure of the bulk 100b composed of transition metal M and oxygen octahedra is not easily collapsed. Furthermore, the deviation of the layer composed of transition metal M and oxygen octahedra in the bulk 100b can be suppressed.
[0381] In order to make the surface part 100a have a stable composition and crystal structure, the surface part 100a preferably contains an additive element A, and more preferably contains a plurality of additive elements A. In addition, the concentration of one or more selected from the additive elements A in the surface part 100a is preferably higher than that in the bulk 100b. In addition, one or more selected from the additive elements A contained in the positive electrode active material 100 preferably have a concentration gradient. In addition, it is more preferred that the distribution of the additive element A in the positive electrode active material 100 is different. For example, it is more preferred that the depth of the concentration peak of the additive element A from the surface is different. Here, the concentration peak refers to the maximum value of the detected amount in the surface part 100a or the range below 50nm from the surface.
[0382] For example, Fig. 14C In the example shown in FIG. 1 , a portion of the additive element A, such as magnesium, fluorine, nickel, titanium, silicon, phosphorus, boron, calcium, etc., preferably has a concentration gradient increasing from the bulk 100b to the surface. The element having such a concentration gradient is referred to as additive element X.
[0383] like Fig.14D It is preferably indicated by the shaded concentration in the figure, and other added elements A such as aluminum, manganese, etc. have a concentration gradient and are in the ratio Fig. 14C The deeper region has a concentration peak. The concentration peak may exist in the surface portion 100a or in a region deeper than the surface portion 100a. For example, it is preferred that a region 5 nm or more and 30 nm or less from the surface has a peak in a vertical or substantially vertical manner. An element having such a concentration gradient is referred to as an additive element Y.
[0384] Magnesium, one of the added elements X, is divalent. In the layered rock salt type crystal structure, magnesium ions are more stable in the lithium position than in the transition metal M position in the layered rock salt type crystal structure, and thus easily enter the lithium position. When magnesium is present at an appropriate concentration at the lithium position of the surface portion 100a, the layered rock salt type crystal structure can be easily maintained. This is because magnesium present at the lithium position is used as a support between CoO2 layers. In addition, when magnesium is present, for example, in Li x When x in CoO2 is 0.24 or less, the oxygen around magnesium can be suppressed from being released. In addition, the density of the positive electrode active material 100 may be improved when magnesium is present. In addition, when the magnesium concentration of the surface portion 100a is high, the corrosion resistance to hydrofluoric acid generated by the decomposition of the electrolyte may be improved.
[0385] If the concentration of magnesium is appropriate, it will not have a negative impact on the insertion and removal of lithium accompanying charging and discharging, so the above advantages can be achieved. However, excess magnesium may have a negative impact on the insertion and removal of lithium. In addition, the effect of contributing to the stabilization of the crystal structure is sometimes reduced. This may be because magnesium not only enters the lithium position but also enters the transition metal M position. In addition, there is also the following concern: unnecessary magnesium compounds (oxides or fluorides, etc.) that are not substituted at the lithium position or the transition metal M position are segregated on the surface of the positive electrode active material and become the resistance component of the secondary battery. In addition, the increase in the magnesium concentration of the positive electrode active material sometimes reduces the discharge capacity of the positive electrode active material. This may be because the excess magnesium enters the lithium position and the amount of lithium contributing to charging and discharging is reduced.
[0386] Therefore, it is preferred that an appropriate amount of magnesium is included in the positive electrode active material 100 as a whole. For example, in the positive electrode active material 100 of one embodiment of the present invention, the magnesium ratio (Mg / Co) relative to the sum of the transition metals M is preferably 0.25% or more and 5% or less, more preferably 0.5% or more and 2% or less, and further preferably about 1%. Here, the amount of magnesium in the positive electrode active material 100 as a whole can be, for example, a value obtained by elemental analysis of the positive electrode active material 100 as a whole using GD-MS, ICP-MS (Inductively Coupled Plasma Mass Spectrometry), etc., or a value based on the coordination value of the raw materials in the manufacturing process of the positive electrode active material 100.
[0387] In addition, nickel, which is one of the added elements X, may be present at the transition metal M site or the lithium site. When nickel is present at the transition metal M site, the redox potential is lowered compared to cobalt, and the discharge capacity is increased, which is preferred.
[0388] In addition, when nickel is present at the lithium position, the deviation of the layered structure composed of the transition metal M and the octahedron of oxygen may be suppressed. In addition, the volume change caused by charging and discharging is also suppressed. In addition, the elastic modulus is increased, that is, it becomes hard. This may be because the nickel present at the lithium position is also used as a support between the CoO2 layers. Therefore, it is possible that the crystal structure is more stable, especially when charged at a high temperature of 45°C or above, so it is preferred.
[0389] On the other hand, when the amount of nickel is too large, the influence of distortion due to the Jan-Teller effect may increase. In addition, when the amount of nickel is too large, it may have a negative impact on the insertion and extraction of lithium.
[0390] Therefore, it is preferred that an appropriate amount of nickel is included in the positive electrode active material 100 as a whole. For example, the number of nickel atoms contained in the positive electrode active material 100 is preferably greater than 0% of the number of cobalt atoms and less than 7.5%, more preferably greater than 0.05% and less than 4%, further preferably greater than 0.1% and less than 2%, and further preferably greater than 0.2% and less than 1%. Alternatively, it is preferably greater than 0% and less than 4%. Alternatively, it is preferably greater than 0% and less than 2%. Alternatively, it is preferably greater than 0.05% and less than 7.5%. Alternatively, it is preferably greater than 0.05% and less than 2%. Alternatively, it is preferably greater than 0.1% and less than 7.5%. Alternatively, it is preferably greater than 0.1% and less than 4%. The amount of nickel shown here can be, for example, a value obtained by elemental analysis of the positive electrode active material as a whole using GD-MS, ICP-MS, etc., or a value obtained by mixing raw materials in the manufacturing process of the positive electrode active material.
[0391] In addition, aluminum, one of the added elements Y, may exist in the position of the transition metal M in the layered rock salt type crystal structure. Aluminum is a typical trivalent element and its valence does not change, so the lithium around aluminum is not easy to move during charging and discharging. Therefore, aluminum and the lithium around it are used as a support to suppress changes in the crystal structure. In addition, aluminum has the effect of suppressing the dissolution of the surrounding transition metal M and improving the continuous charging tolerance. In addition, the Al-O bond is stronger than the Co-O bond, so the oxygen around aluminum can be suppressed from detaching. Through the above effects, thermal stability is improved. Therefore, when aluminum is included as an added element Y, the safety of the positive electrode active material 100 when used in a secondary battery can be improved. In addition, a positive electrode active material 100 that is not prone to collapse of the crystal structure even after repeated charging and discharging can be achieved.
[0392] On the other hand, when the amount of aluminum is too large, there is a possibility that the insertion and extraction of lithium may be adversely affected.
[0393] Therefore, it is preferred that an appropriate amount of aluminum is included in the positive electrode active material 100 as a whole. For example, the number of aluminum atoms in the positive electrode active material 100 as a whole is preferably greater than 0.05% and less than 4% of the number of cobalt atoms, more preferably greater than 0.1% and less than 2%, and further preferably greater than 0.3% and less than 1.5%. Alternatively, it is preferably greater than 0.05% and less than 2%. Alternatively, it is preferably greater than 0.1% and less than 4%. The amount in the positive electrode active material 100 as a whole shown here can be, for example, a value obtained by elemental analysis of the positive electrode active material 100 as a whole using GD-MS, ICP-MS, etc., or a value obtained by mixing raw materials in the manufacturing process of the positive electrode active material 100.
[0394] In addition, fluorine, one of the added elements X, is a monovalent anion, and when part of the oxygen in the surface portion 100a is replaced by fluorine, the lithium detachment energy is reduced. This is because the valence change of the cobalt ion accompanying the detachment of lithium varies according to the presence or absence of fluorine, for example, from trivalent to tetravalent in the absence of fluorine, and from divalent to trivalent in the presence of fluorine, and the redox potential is different. Therefore, when part of the oxygen in the surface portion 100a of the positive electrode active material 100 is replaced by fluorine, it can be said that the detachment and embedding of lithium ions near fluorine occur smoothly. Therefore, the charge and discharge characteristics, current characteristics, etc. can be improved when it is used in a secondary battery. In addition, by having fluorine in the surface portion 100a of the surface including the portion in contact with the electrolyte, the corrosion resistance to hydrofluoric acid can be effectively improved. In addition, when the melting point of fluorides such as lithium fluoride is lower than the melting point of other added element A sources, it can be used as a flux (also known as a solubility aid) to reduce the melting point of other added element A sources.
[0395] In addition, it is known that the oxide of titanium, which is one of the added elements X, has super hydrophilicity. Therefore, by manufacturing the positive electrode active material 100 containing titanium oxide in the surface layer 100a, it is sometimes possible to have good wettability to a solvent with high polarity. When manufacturing a secondary battery, the positive electrode active material 100 has good contact with the interface of the electrolyte with high polarity, and sometimes the increase of the internal resistance can be suppressed.
[0396] In addition, by including phosphorus, which is one of the additional elements X, in the surface layer portion 100a, it is possible to maintain Li x When x in CoO 2 is small, short circuit can be suppressed, which is preferable. For example, it is preferable that it exists in the surface layer portion 100 a as a compound containing phosphorus and oxygen.
[0397] When the positive electrode active material 100 contains phosphorus, hydrogen fluoride generated by decomposition of the electrolyte reacts with phosphorus to reduce the concentration of hydrogen fluoride in the electrolyte, which is preferable.
[0398] In the case where the electrolyte contains LiPF6, hydrogen fluoride is sometimes produced by hydrolysis. In addition, hydrogen fluoride is sometimes produced by the reaction of polyvinylidene fluoride (PVDF) used as a constituent element of the positive electrode with an alkali. By reducing the concentration of hydrogen fluoride in the electrolyte, at least one of the corrosion of the current collector and the peeling of the coating can sometimes be suppressed. In addition, the reduction in adhesion caused by at least one of the gelation and insolubility of PVDF can sometimes be suppressed.
[0399] When the positive electrode active material 100 contains phosphorus in addition to magnesium, xCoO2 is preferred because its stability is extremely high when x is small. When the positive electrode active material 100 contains phosphorus, the number of phosphorus atoms is preferably 1% or more and 20% or less of the number of cobalt atoms, more preferably 2% or more and 10% or less, and further preferably 3% or more and 8% or less. Alternatively, it is preferably 1% or more and 10% or less. Alternatively, it is preferably 1% or more and 8% or less. Alternatively, it is preferably 2% or more and 20% or less. Alternatively, it is preferably 2% or more and 8% or less. Alternatively, it is preferably 3% or more and 20% or less. Alternatively, it is preferably 3% or more and 10% or less. In addition, the number of magnesium atoms is preferably 0.1% or more and 10% or less of the number of cobalt atoms, more preferably 0.5% or more and 5% or less, and further preferably 0.7% or more and 4% or less. Alternatively, it is preferably 0.1% or more and 5% or less. Alternatively, it is preferably 0.1% or more and 4% or less. Alternatively, it is preferably 0.5% or more and 10% or less. Alternatively, it is preferably 0.5% or more and 4% or less. Alternatively, it is preferably 0.7% or more and 10% or less. Alternatively, it is preferably 0.7% or more and 5% or less. The phosphorus and magnesium concentrations shown here may be values obtained by elemental analysis of the entire positive electrode active material 100 using GD-MS, ICP-MS, etc., or values obtained by mixing raw materials in the manufacturing process of the positive electrode active material 100.
[0400] When the positive electrode active material 100 has cracks, if phosphorus, more specifically, a compound containing phosphorus and oxygen, exists near the center of the positive electrode active material where the cracks are on the surface, such as in the embedded portion 102 , the expansion of the cracks may be suppressed.
[0401] In addition, when the surface layer 100a contains both magnesium and nickel, it is possible that divalent magnesium exists more stably near divalent nickel. x When x in CoO 2 is small, the dissolution of magnesium is also suppressed. Thus, magnesium and nickel contribute to the stabilization of the surface layer portion 100 a.
[0402] In addition, when adding elements A with different distributions such as adding elements X and adding elements Y are used simultaneously, the crystal structure of a wider area can be stabilized, so it is preferred. For example, when the positive electrode active material 100 simultaneously contains magnesium and nickel, which are part of the adding element X, and aluminum, which is part of the adding element Y, the crystal structure of a wider area can be stabilized compared to the case where only one of the adding elements X and the adding element Y is included. In this way, when the positive electrode active material 100 contains adding elements X and adding elements Y at the same time, the adding elements X such as magnesium and nickel can fully stabilize the surface, so adding elements Y such as aluminum are not required on the surface. On the contrary, aluminum is preferably widely distributed in a deeper area, such as an area with a depth of more than 5nm and less than 50nm from the surface, so that the crystal structure of a wider area can be stabilized.
[0403] When a plurality of additive elements A are included as described above, each additive element A acts synergistically and contributes to further stabilization of the surface layer portion 100a. In particular, when magnesium, nickel, and aluminum are included, the effect of achieving a stable composition and crystal structure is high, and therefore, it is preferred.
[0404] Note that it is not preferred that lithium is not easily inserted and removed when only the compound of element A and oxygen is added to the surface portion 100a. For example, it is not preferred that the surface portion 100a has at least one of MgO, a structure in which MgO and NiO(II) are solid-dissolved, and a structure in which MgO and CoO(II) are solid-dissolved. Therefore, the surface portion 100a needs to contain at least cobalt, also contain lithium in the discharge state, and have a path for the insertion and removal of lithium.
[0405] In order to fully ensure the path of lithium insertion and extraction, the cobalt concentration of the surface portion 100a is preferably higher than the magnesium concentration. For example, the ratio of the number of atoms of magnesium Mg to the number of atoms of cobalt Co Mg / Co is preferably 0.62 or less. In addition, the cobalt concentration of the surface portion 100a is preferably higher than the nickel concentration. In addition, the cobalt concentration of the surface portion 100a is preferably higher than the aluminum concentration. In addition, the cobalt concentration of the surface portion 100a is preferably higher than the fluorine concentration.
[0406] If nickel is too much, the diffusion of lithium may be blocked, so the magnesium concentration of the surface layer 100a is preferably higher than the nickel concentration. For example, the number of nickel atoms is preferably 1 / 6 or less of the number of magnesium atoms.
[0407] In addition, the concentration of a part of the added element A, especially magnesium, nickel and aluminum in the surface part 100a is preferably higher than the concentration in the bulk 100b, but they are preferably also present irregularly and in small amounts in the bulk 100b. When magnesium and aluminum are present in the lithium position of the bulk 100b at appropriate concentrations, it has the same effect as described above, such as easily maintaining the layered rock salt type crystal structure. In addition, when nickel is present in the bulk 100b at an appropriate concentration, the deviation of the layered structure composed of the octahedron of the transition metal M and oxygen is suppressed, as described above. In addition, when magnesium and nickel are used simultaneously, divalent magnesium may also be more stably present near divalent nickel, so it is possible to exert a synergistic effect of suppressing the dissolution of magnesium.
[0408] In addition, it is preferable that the crystal structure changes continuously from the bulk 100b to the surface due to the concentration gradient of the added element A. Alternatively, it is preferable that the crystal orientations of the surface layer 100a and the bulk 100b are substantially consistent.
[0409] For example, it is preferred that the crystal structure changes continuously from the bulk 100b of the layered rock salt type to the surface and the surface layer 100a of the rock salt type or having both the characteristics of the rock salt type and the layered rock salt type. Alternatively, it is preferred that the orientation of the surface layer 100a of the rock salt type or having both the characteristics of the rock salt type and the layered rock salt type is roughly consistent with that of the bulk 100b of the layered rock salt type.
[0410] In addition, in this specification, etc., the layered rock salt type crystal structure belonging to the space group R-3m possessed by the composite oxide containing transition metal M such as lithium and cobalt refers to the following crystal structure: having a rock salt type ion arrangement in which cations and anions are alternately arranged, and the transition metal M and lithium are regularly arranged to form a two-dimensional plane, so that lithium can diffuse in two dimensions. In addition, defects such as vacancies of cations or anions may also be included. Strictly speaking, the layered rock salt type crystal structure is sometimes a structure formed by deformation of the lattice of the rock salt type crystal structure.
[0411] In addition, the rock salt type crystal structure has a cubic crystal structure such as space group Fm-3m, in which cations and anions are arranged alternately. In addition, vacancies of cations or anions may also be included.
[0412] In addition, whether or not the crystal has the characteristics of both the layered rock salt type crystal structure and the rock salt type crystal structure can be determined using an electron diffraction pattern, a TEM image, a cross-sectional STEM image, and the like.
[0413] There is no difference in the position of cations in the rock salt type crystal structure, but in the layered rock salt type crystal structure, there are two types of cation positions, one is the position where lithium occupies most of the position and the other is the position where the transition metal M occupies. Both the rock salt type and the layered rock salt type have a stacked structure in which the two-dimensional planes of cations and the two-dimensional planes of anions are arranged alternately. In the bright spots of the electron diffraction pattern corresponding to the crystal planes forming the above-mentioned two-dimensional planes, when the central spot (transmitted spot) is taken as the origin 000, the bright spot closest to the central spot is, for example, a bright spot of the (111) plane representing the ideal state of the rock salt type crystal structure or a bright spot of the (003) plane representing the layered rock salt type crystal structure. For example, when comparing the electron diffraction patterns of rock salt type MgO and layered rock salt type LiCoO2, a bright spot of the (003) plane of LiCoO2 is observed at a distance of about half the distance between the bright spots of the (111) plane of MgO. Therefore, for example, when the analysis region includes two phases of rock salt type MgO and layered rock salt type LiCoO2, there are plane orientations in which bright spots of relatively strong brightness and bright spots of relatively weak brightness are arranged alternately in the electron diffraction pattern. Bright spots common to the rock salt type and the layered rock salt type have high brightness, while bright spots occurring only in the layered rock salt type have low brightness.
[0414] In addition, in cross-sectional STEM images, when observing the layered rock salt type crystal structure from a direction perpendicular to the c-axis, layers with higher brightness and layers with lower brightness are observed alternately. The position of the cations of the rock salt type is the same, so the above characteristics are not observed. When a crystal structure having characteristics of both the rock salt type and the layered rock salt type is adopted, when observing from a specific crystal orientation, layers with higher brightness and layers with lower brightness are observed alternately in cross-sectional STEM images, and a metal having an atomic number greater than lithium exists in a part of the lower brightness layer, that is, the lithium layer.
[0415] The layered rock salt type crystal structure and the anions of the rock salt type crystal structure form a cubic closest packing structure (face-centered cubic lattice structure) respectively. It can be considered that the anions of the O3' type crystal structure described later also form a cubic closest packing structure. Therefore, when the layered rock salt type crystal structure contacts the rock salt type crystal structure, there are crystal planes with consistent orientation of the cubic closest packing structure formed by the anions.
[0416] In addition, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock salt type has a rhombus structure belonging to the space group R-3m, but in order to facilitate the understanding of the structure, it is usually expressed as a composite hexagonal lattice, and the (0001) plane of the layered rock salt type has a hexagonal lattice. The triangular lattice of the {111} plane of the cubic crystal has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock salt type. The state in which the lattices of the two are integrated can be said to be a state in which the orientation of the cubic closest packing structure is consistent.
[0417] Note that the space group of the layered rock salt type crystal structure and the O3' type crystal structure is R-3m, which is different from the space group Fm-3m (the space group of the general rock salt type crystal structure) of the rock salt type crystal structure, so the Miller index of the crystal plane that satisfies the above conditions is different between the layered rock salt type crystal structure and the O3' type crystal structure and the rock salt type crystal structure. In this specification, etc., sometimes the state of the orientation of the cubic closest packing structure formed by the anions in the layered rock salt type crystal structure, the O3' type crystal structure and the rock salt type crystal structure is consistent, which means that the orientation of the crystal is roughly consistent, in a topological derivative (topotaxy) or in an epitaxy.
[0418] Topological derivation refers to the state in which the orientation of the crystals is roughly the same and has three-dimensional structural similarity or the same orientation crystallographically. In addition, surface derivation refers to the structural similarity of the two-dimensional interface.
[0419] Whether the crystal orientations of two regions are roughly consistent can be determined by using TEM images, STEM images, HAADF-STEM (High-Angle Annular Dark-Field STEM: High-angle annular dark-field scanning transmission electron microscope) images, ABF-STEM (Annular Bright-Field STEM: Annular bright-field scanning transmission electron microscope) images, eHCI-TEM (enhanced Hollow-Cone Illumination TEM: Improved hollow cone illumination transmission electron microscope) images, FFT (Fast Fourier Transformation: Fast Fourier Transformation) patterns of TEM images and STEM images, etc. In addition, XRD patterns, electron diffraction patterns, neutron diffraction patterns, etc. can also be used as judgment materials.
[0420] Fig.15 An example of a TEM image showing that the orientations of the layered rock salt type crystal structure LRS and the rock salt type crystal structure RS are substantially consistent. TEM images, STEM images, HAADF-STEM images, ABF-STEM images, etc. can be used to obtain images reflecting the crystal structure.
[0421] For example, the contrast derived from the crystal plane can be obtained from the high-resolution images of TEM. Due to the diffraction and interference of the electron beam, for example, when the electron beam is incident on the c-axis perpendicular to the layered rock salt type composite hexagonal lattice, the repetition of high contrast bands (bright band lines) and dark bands (dark band lines) derived from the (0003) plane can be obtained. Therefore, the repetition of bright lines and dark lines is observed in the TEM image, and between the bright lines (for example, Fig.15 L RS and L LRS When the angle between the bright lines is greater than 0 degrees and less than 5 degrees or greater than 0 degrees and less than 2.5 degrees, it can be judged that the crystal planes are roughly consistent, that is, the orientation of the crystals is roughly consistent. Similarly, when the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can also be judged that the orientation of the crystals is roughly consistent. Note that, in general, it is difficult to clearly distinguish between "completely consistent" and "roughly consistent". Therefore, in this specification, etc., "consistent" includes both the case of complete consistency (for example, the case where the angle between the bright lines is 0 degrees) and the case of roughly consistent.
[0422] In addition, in the HAADF-STEM image, a contrast ratio proportional to the atomic number is obtained, and the larger the atomic number of the element, the brighter it is observed. For example, when using a layered rock salt type lithium cobalt oxide belonging to the space group R-3m, the atomic number of cobalt (atomic number 27) is the largest, so the electron beam is scattered more strongly at the position of the cobalt atom, so that the arrangement of the cobalt atoms is observed as a bright line or an arrangement of points with higher brightness. Therefore, when observing lithium cobalt oxide with a layered rock salt type crystal structure in a direction perpendicular to the c-axis, the arrangement of cobalt atoms is observed as a bright line or an arrangement of points with higher brightness in the direction perpendicular to the c-axis, and the arrangement of lithium atoms and oxygen atoms is observed as dark lines or areas with lower brightness. The same is true when fluorine (atomic number 9) and magnesium (atomic number 12) are included as additive elements of lithium cobalt oxide.
[0423] Therefore, in the HAADF-STEM image, when the repetition of bright and dark lines is observed in two regions with different crystal structures, when the angle between the bright lines is less than 5 degrees or less than 2.5 degrees, it can be judged that the atomic arrangement is roughly consistent, that is, the orientation of the crystal is roughly consistent. Similarly, when the angle between the dark lines is less than 5 degrees or less than 2.5 degrees, it can also be judged that the orientation of the crystal is roughly consistent.
[0424] In addition, in the ABF-STEM image, the smaller the atomic number, the brighter the element is observed, but the contrast corresponding to the atomic number can be obtained in the same way as the HAADF-STEM image, so the ABF-STEM image can determine the orientation of the crystal in the same way as the HAADF-STEM image.
[0425] Fig.16A An example of a STEM image showing that the orientations of the layered rock salt type crystal structure LRS and the rock salt type crystal structure RS are substantially consistent with each other. Fig. 16B FFT pattern of the region showing the rock salt type crystal structure RS, Fig. 16C FFT pattern of a region showing a layered rock-salt type crystal structure LRS. Fig. 16B and Fig. 16C The left side shows the composition, the card number of JCPDS (Joint Committee on Powder Diffraction Standard), and the d value and angle calculated from the number. The right side shows the measured value. The spot with O indicates the zero-order diffraction, and X is attached to the center position of the half point.
[0426] exist Fig. 16B The spots marked with A in the figure come from the 11-1 reflection of the cubic crystal. Fig. 16C The spots marked with A in the figure are from the 0003 reflection of the layered rock salt type. Fig. 16B and Fig. 16CIt can be seen that the orientation of the 11-1 reflection of the cubic crystal is roughly consistent with the orientation of the 0003 reflection of the layered rock salt type. Fig. 16B The straight line of AO and the Fig. 16C The straight lines of AO are substantially parallel. The "substantially consistent" and "substantially parallel" described here refer to the case where the angle is greater than 0 degrees and less than 5 degrees or greater than 0 degrees and less than 2.5 degrees.
[0427] As described above, in some cases, in the FFT pattern and the electron diffraction pattern, the orientation of the layered rock salt type crystal structure is roughly the same as that of the rock salt type crystal structure, and the layered rock salt type <0003> The orientation is roughly consistent with the <11-1> orientation of the rock salt type. At this time, their reciprocal points are preferably spot-shaped, that is, not continuous with other reciprocal points. The reciprocal points are spot-shaped and not continuous with other reciprocal points, which means that the crystallinity is high.
[0428] In addition, as described above, when the orientation of the 11-1 reflection of the cubic crystal is roughly the same as the orientation of the 0003 reflection of the layered rock salt type, a spot that does not originate from the 0003 reflection of the layered rock salt type is sometimes observed in a reciprocal space different from the orientation of the 0003 reflection of the layered rock salt type, depending on the incident orientation of the electron beam. Fig. 16C The spot with B in the figure is from the 10-14 reflection of the layered rock salt type. This spot is sometimes at the inverse grid point ( Fig. 16C A) is 52° to 56° (i.e., ∠AOB is 52° to 56°) and d is 0.19nm to 0.21nm. Note that the above index is only an example and does not need to be consistent with the index. For example, reciprocal grid points equivalent to 0003 and 10-14 may also be used.
[0429] Similarly, a spot not derived from the 11-1 reflection of a cubic crystal is sometimes observed in a reciprocal space different from the orientation at which the 11-1 reflection of a cubic crystal is observed. Fig. 16B The spots in the figure are from the 200 reflection of the cubic crystal. Sometimes, the reflections of 11-1 ( Fig. 16B Diffraction spots are observed at locations where the difference in azimuth between A and B is greater than 54° and less than 56° (i.e., ∠AOB is greater than 54° and less than 56°). Note that this index is only an example and does not need to be consistent with this index. For example, reciprocal grid points equivalent to 11-1 and 200 may also be used.
[0430] Note that when determining the consistency of crystal orientation, it is preferable to thin the sample for easy observation of the (0003) plane of the layered rock salt type. Therefore, it is preferable to thin the observation sample using FIB (Focused Ion Beam) or the like so that, for example, the electron beam is incident as [1-210] in a TEM image or the like. It is known that layered rock salt type positive electrode active materials such as lithium cobaltate are likely to exhibit crystal planes on the (0003) plane and equivalent planes thereof and the (10-14) plane and equivalent planes thereof. Therefore, by appropriately observing the shape of the positive electrode active material using an SEM (Scanning Electron Microscope) image or the like, the observation sample can be thinned in a manner that allows easy observation of the (0003) plane.
[0431] <<Li x a state where x in CoO2 is small>>
[0432] The positive electrode active material 100 of one embodiment of the present invention has at least one of the above-described distribution of additive element A and crystal structure in the discharged state, and thus Li x The crystal structure in the state where x in CoO2 is small is different from that of the conventional positive electrode active material. Note that here, a small x means a case where 0.1 < x ≤ 0.24.
[0433] Use Figures 17 to 21 To compare the conventional positive electrode active material and the positive electrode active material 100 of one embodiment of the present invention to illustrate the change in crystal structure accompanying the change in x in x CoO2.
[0434] Fig.18 Show the change in the crystal structure of the conventional positive electrode active material. Fig.18 The conventional positive electrode active material shown is lithium cobaltate (LiCoO2) that does not contain additive element A. Non-Patent Document 1 and Non-Patent Document 2 etc. describe the change in the crystal structure of lithium cobaltate that does not contain additive element A.
[0435] In Fig.18 attach R-3m O3 to indicate Li xThe crystal structure of lithium cobalt oxide with x=1 in CoO2. In this crystal structure, the unit cell includes three CoO2 layers, and lithium is located between the CoO2 layers. In addition, lithium occupies the octahedral position of six coordinated oxygens. Therefore, this crystal structure is sometimes called an O3 type crystal structure. Note that the CoO2 layer refers to a structure in which the octahedral structure of cobalt coordinated to six oxygens is continuous on a plane in a state of sharing edges. Sometimes this structure is called a layer composed of octahedra of cobalt and oxygen. R-3m O3 can be represented by Li(0,0,0)Co(0,0,0.5)O(0,0,0.23951) to represent the coordinates of lithium, cobalt and oxygen in the unit cell.
[0436] In addition, it is known that the symmetry of lithium in existing cobalt oxide increases when x=0.5, and the cobalt oxide has a monoclinic crystal structure belonging to the space group P2 / m. In this structure, the unit cell includes one CoO2 layer. Therefore, it is sometimes called an O1-type crystal structure or a monoclinic O1-type crystal structure.
[0437] The positive electrode active material when x=0 has a trigonal crystal structure belonging to the space group P-3m1, and the unit cell also includes a CoO2 layer. Therefore, this crystal structure is sometimes called an O1-type crystal structure or a trigonal O1-type crystal structure. In addition, the trigonal crystal is sometimes converted into a composite hexagonal lattice and called a hexagonal O1-type.
[0438] In addition, the existing lithium cobalt oxide has a crystal structure belonging to the space group R-3m when x=0.12. It can also be said that the structure is a structure in which CoO2 structures such as the trigonal O1 type crystal structure and LiCoO2 structures such as those belonging to R-3m O3 are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3 type crystal structure. Note that in reality, the insertion and extraction of lithium will occur unevenly, so in experiments, an H1-3 type crystal structure is observed from about x=0.25. In addition, in reality, the number of cobalt atoms in each unit cell of the H1-3 type crystal structure is twice that of other structures. However, in the case of Fig.18 In this specification, etc., in order to facilitate comparison with other crystal structures, the c-axis of the H1-3 type crystal structure is 1 / 2 of the unit cell.
[0439] As an example of an H1-3 type crystal structure, as shown in non-patent literature 2, the coordinates of cobalt and oxygen in the unit cell can be represented by Co (0, 0, 0.42150 ± 0.00016), O1 (0, 0, 0.27671 ± 0.00045), O2 (0, 0, 0.11535 ± 0.00045). O1 and O2 are both oxygen atoms. For example, by performing Rietveld analysis on the XRD pattern, it can be determined which unit cell is used to represent the crystal structure of the positive electrode active material. At this time, a unit cell with a small GOF (goodness of fit) value can be used.
[0440] When repeated Li x During charge and discharge when x in CoO2 is 0.24 or less, the crystal structure of conventional lithium cobalt oxide changes repeatedly between the H1-3 type crystal structure and the R-3m O3 crystal structure in the discharged state (ie, non-equilibrium phase transition).
[0441] However, the CoO2 layers of the above two crystal structures deviate greatly. Fig.18 As shown by the dotted line and arrow in the figure, in the H1-3 type crystal structure, the CoO2 layer deviates greatly from the R-3m O3 crystal structure in the discharge state. Such dynamic structural changes will have an adverse effect on the stability of the crystal structure.
[0442] Furthermore, the volume difference between the two crystal structures is also large. When comparing the same number of cobalt atoms, the volume difference between the H1-3 type crystal structure and the R-3m O3 type crystal structure in the discharge state exceeds 3.5%, typically 3.9% or more.
[0443] In addition to the above, the structure of the H1-3 type crystal structure having a continuous CoO2 layer like that of the trigonal O1 type is likely to be unstable.
[0444] Therefore, when charging and discharging are repeated until x becomes less than 0.24, the crystal structure of the existing lithium cobalt oxide collapses. The collapse of the crystal structure causes the deterioration of the cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably, and the insertion and removal of lithium become difficult.
[0445] On the other hand, Fig.17 In the positive electrode active material 100 of one embodiment of the present invention shown in FIG. xThe change in the crystal structure between the discharge state where x is 1 and the state where x is less than 0.24 in CoO2 is less than that of the existing positive electrode active materials. More specifically, the deviation of the CoO2 layer between the state where x is 1 and the state where x is less than 0.24 can be reduced. In addition, the volume change when comparing each cobalt atom can be reduced. Therefore, even if the positive electrode active material 100 of one embodiment of the present invention is repeatedly charged and discharged with x being less than 0.24, it is not easy to cause the crystal structure to collapse and good cycle characteristics can be achieved. In addition, the positive electrode active material 100 of one embodiment of the present invention is not easy to cause the crystal structure to collapse and good cycle characteristics can be achieved. x When x in CoO2 is 0.24 or less, it can have a more stable crystal structure than the existing positive electrode active material. x When x in CoO2 is 0.24 or less, short circuit is less likely to occur. In this case, the safety of the secondary battery is further improved, which is preferred.
[0446] Fig.17 Shown in Li x The crystal structure of the bulk 100b of the positive electrode active material 100 in each case where x in CoO2 is about 1 and 0.2. The bulk 100b occupies most of the volume of the positive electrode active material 100 and is the part that has a great influence on charging and discharging, so it can be said that the deviation of the CoO2 layer and the change in volume have the greatest influence.
[0447] When x=1, the positive electrode active material 100 has the same R-3m O3 type crystal structure as that of conventional lithium cobalt oxide.
[0448] However, when the conventional lithium cobalt oxide has an H1-3 type crystal structure and x is 0.24 or less, for example, about 0.2 or about 0.12, the positive electrode active material 100 has crystals with a structure different from the above structure.
[0449] When x=0.2, the positive electrode active material 100 of one embodiment of the present invention has a crystal structure belonging to the space group R-3m belonging to the trigonal system. The symmetry of the CoO2 layer of this structure is the same as that of O3. Therefore, this crystal structure is called O3' type crystal structure. Fig.17 The crystal structure is indicated by R-3m O3'.
[0450] The coordinates of cobalt and oxygen in the unit cell of the O3' type crystal structure can be represented by Co(0, 0, 0.5) and O(0, 0, x) respectively, and are within the range of 0.20≤x≤0.25. In addition, the lattice constant of the unit cell is as follows: the a-axis is preferably More preferably Typical is The c-axis is preferably More preferably Typical is
[0451] In the O3' type crystal structure, ions of cobalt, nickel, magnesium, etc. occupy the positions coordinated to six oxygen atoms. In addition, light elements such as lithium may occupy the positions coordinated to four oxygen atoms.
[0452] like Fig.17 The dashed line in the figure shows that there is almost no deviation of the CoO2 layer between the R-3m(O3) type crystal structure and the O3' type crystal structure in the discharged state.
[0453] The difference in volume of the same number of cobalt atoms between the R-3m (O3) type crystal structure and the O3' type crystal structure in the discharged state is 2.5% or less, more specifically 2.2% or less, and typically 1.8%.
[0454] Thus, in the positive electrode active material 100 of one embodiment of the present invention, Li x When x in CoO2 is smaller, that is, when more lithium is detached, the change in the crystal structure is suppressed compared with the existing positive electrode active material. In addition, the change in volume when compared by the same number of cobalt atoms is also suppressed. Therefore, the crystal structure of the positive electrode active material 100 is not easy to collapse even if x is repeatedly charged and discharged to be less than 0.24. Therefore, the decrease in the discharge capacity of the positive electrode active material 100 caused by the charge and discharge cycle is suppressed. In addition, a larger amount of lithium can be stably used than the existing positive electrode active material, so the discharge capacity per unit weight and unit volume of the positive electrode active material 100 is larger. Therefore, by using the positive electrode active material 100, a secondary battery with a larger discharge capacity per unit weight and unit volume can be manufactured.
[0455] In addition, it was confirmed that the positive electrode active material 100 x When x in CoO2 is greater than 0.15 and less than 0.24, it sometimes has an O3' type crystal structure. x When x in CoO2 is greater than 0.1 and less than 0.2, and typically when x is greater than 0.15 and less than 0.17, it sometimes has a monoclinic O1(15) type crystal structure. x In addition to x in CoO2, it is also affected by the number of charge and discharge cycles, charge and discharge current, temperature, electrolyte, etc., and is therefore not limited to the above range of x.
[0456] Therefore, the positive electrode active material 100 in Li xWhen x in CoO2 is greater than 0.1 and less than 0.24, the bulk 100b of the positive electrode active material 100 does not need to be entirely of the O3' type crystal structure, but may have other crystal structures, or may be partially amorphous.
[0457] In addition, in order to achieve Li x In the case of CoO2 with a small x value, a high charging voltage is generally required for charging. x The state in which x in CoO2 is smaller is referred to as a state of charging at a high charging voltage. For example, when CCCV charging is performed at a voltage of 4.6V or more based on the potential of lithium metal in an environment of 25°C, an H1-3 type crystal structure is presented in the existing positive electrode active material. Therefore, it can be said that a charging voltage of 4.6V or more based on the potential of lithium metal is a high charging voltage. In addition, in this specification, etc., unless otherwise specified, the charging voltage is expressed based on the potential of lithium metal.
[0458] Therefore, it can be said that the positive electrode active material 100 of one embodiment of the present invention can maintain a crystal structure having R-3m O3 symmetry even when charged at a high charging voltage of 4.6V or higher at 25°C, so it is preferred. In addition, it can be said that it can have an O3' type crystal structure when charged at a voltage of 4.65V or higher and 4.7V or lower at 25°C, so it is preferred.
[0459] In the positive electrode active material 100, the H1-3 type crystal structure is sometimes observed only when the charging voltage is further increased. In addition, as described above, the crystal structure is affected by the number of charge and discharge cycles, the charge and discharge current, the temperature, the electrolyte, etc., so when the charging voltage is lower, for example, even at 25° C. and the charging voltage is 4.5 V or more and less than 4.6 V, the positive electrode active material 100 of one embodiment of the present invention sometimes has an O3' type crystal structure.
[0460] In addition, for example, when graphite is used as the negative electrode active material of the secondary battery, the voltage of the secondary battery is lower than the above voltage by the difference between the potential of graphite and the potential of lithium metal. The potential of graphite is about 0.05V to 0.2V based on the potential of lithium metal. Therefore, the secondary battery using graphite as the negative electrode active material has the same crystal structure as the case where the voltage is obtained by subtracting the potential of graphite from the above voltage.
[0461] In addition, Fig.17 In the O3' type crystal structure, lithium exists in all lithium positions with equal probability, but the present invention is not limited to this. It can exist in a part of the lithium positions in a concentrated manner, for example, it can also have a Fig.18 The monoclinic O1 crystal structure (Li 0.5The distribution of lithium can be analyzed, for example, by neutron diffraction patterns.
[0462] In addition, although the O3' type crystal structure contains lithium irregularly between layers, it can also have a crystal structure similar to the CdCl2 type crystal structure. This crystal structure similar to the CdCl2 type crystal structure is similar to the crystal structure of lithium nickel oxide charged to become Li 0.06 The crystal structure of NiO2, but it is known that pure lithium cobalt oxide or layered rock salt-type positive electrode active materials containing a large amount of cobalt generally do not have a CdCl2-type crystal structure.
[0463] In addition, the concentration gradient of the added element A preferably has the same gradient in multiple regions of the surface portion 100a of the positive electrode active material 100. In other words, it is preferred that the reinforcing effect derived from the added element A is homogeneously present in the surface portion 100a. Even if a portion of the surface portion 100a is reinforced, if there is a portion that is not reinforced, stress may be concentrated in that portion. When stress is concentrated in a portion of the positive electrode active material 100, defects such as cracks may occur from that portion, thereby causing the positive electrode active material to rupture and a decrease in discharge capacity.
[0464] Note that the added element A in the surface layer portion 100 a of the positive electrode active material 100 does not necessarily have the same concentration gradient. Fig.14E Show Fig.14A Example of the distribution of the added element X near the CD of, Fig.14F Show Fig.14A Example of the distribution of the added element Y near the CD.
[0465] Here, the vicinity of CD has a layered rock salt type crystal structure belonging to R-3m, and the surface is (001) oriented. The distribution of the additive element A on the (001) oriented surface may also be different from other surfaces. For example, compared with other orientations, the distribution of one or more concentration peaks selected from the additive element X and the additive element Y in the (001) oriented surface and its surface portion 100a may also be located in a portion shallower from the surface. Alternatively, compared with other orientations, the concentration of one or more selected from the additive element X and the additive element Y in the (001) oriented surface and its surface portion 100a may also be lower. Alternatively, one or more selected from the additive element X and the additive element Y in the (001) oriented surface and its surface portion 100a may also be below the detection limit.
[0466] In the layered rock salt type crystal structure belonging to R-3m, cations are arranged parallel to the (001) plane. It can be said that this is a structure in which CoO2 layers and lithium layers are stacked alternately parallel to the (001) plane. Therefore, the diffusion path of lithium ions is also parallel to the (001) plane.
[0467] The CoO2 layer is relatively stable, so the CoO2 layer is relatively stable on the (001) surface. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) surface.
[0468] On the other hand, on the surface other than the (001) orientation, the diffusion path of lithium ions is exposed. Therefore, the surface other than the (001) orientation and the surface layer 100a are important areas for maintaining the diffusion path of lithium ions, and are the areas where lithium ions first leave, so they tend to be unstable. Therefore, in order to maintain the overall crystal structure of the positive electrode active material 100, it is very important to strengthen the surface other than the (001) orientation and the surface layer 100a.
[0469] Therefore, in the positive electrode active material 100 of another embodiment of the present invention, it is important that the distribution of the added element A in the plane other than (001) and the surface layer portion 100a thereof is Fig. 14C and Fig.14D On the other hand, in the (001) plane and its surface layer portion 100a, the concentration of the additive element A may be relatively low as described above, or the additive element A may not be contained.
[0470] In the manufacturing method of manufacturing high-purity LiCoO2 and then mixing the additive element A and heating, the additive element A diffuses mainly through the diffusion path of lithium ions. Therefore, it is easy to set the distribution of the additive element A in the surface other than (001) and its surface part 100a to a preferred range.
[0471] In addition, the surface of the positive electrode active material 100 is preferably smooth and less uneven, but it is not necessary that the entire surface of the positive electrode active material 100 is smooth and less uneven. In a composite oxide having a layered rock salt type crystal structure belonging to R-3m, sliding is likely to occur on a plane parallel to the (001) plane, such as a plane where lithium is arranged. For example, Fig.19A As shown, when there is a (001) plane, by applying pressure or other processes, sometimes Fig.19B As shown by the arrow in the figure, the material slides and deforms in a direction parallel to the (001) plane.
[0472] In this case, in the surface newly generated by sliding and the surface layer portion 100 a thereof, the added element A may not exist or may be below the detection limit. Fig.19B EF in FIG. 1 shows an example of a surface regenerated by sliding and its surface layer portion 100a. Fig.19C and Fig.19D This is a magnified view of the area around EF. FIG. 14C to FIG. 14F Different, in Fig.19C and Fig.19D There is no distribution of added element X and added element Y.
[0473] However, sliding easily occurs in the direction parallel to the (001) plane, so the newly generated surface and its surface layer 100a tend to be (001) oriented. At this time, the diffusion path of lithium ions is not exposed and is relatively stable, so there is almost no problem even if the added element A does not exist or is below the detection limit.
[0474] As described above, in a layered rock salt type composite oxide whose composition is LiCoO2 and whose crystal structure belongs to R-3m, cobalt is arranged parallel to the (001) plane. In addition, in the HAADF-STEM image, the brightness of cobalt, which has the largest atomic number in LiCoO2, is the highest. Therefore, in the HAADF-STEM image, the arrangement of atoms with higher brightness can be regarded as the arrangement of cobalt. In addition, the repetition of the arrangement with higher brightness can also be synonymous with crystal stripes and lattice stripes.
[0475] <<Grain Boundary>>
[0476] More preferably, in addition to having the above-described distribution, the additional element A of the positive electrode active material 100 according to one embodiment of the present invention is at least partially distributed concentratedly at the grain boundary 101 and its vicinity.
[0477] In this specification, etc., concentrated distribution means that the element concentration in any region is different from that in other regions. Concentrated distribution is synonymous with segregation, precipitation, non-uniformity, deviation, or a mixture of a high-concentration region and a low-concentration region.
[0478] For example, the magnesium concentration in the grain boundary 101 and its vicinity of the positive electrode active material 100 is preferably higher than that in other regions of the block 100b. In addition, the fluorine concentration in the grain boundary 101 and its vicinity is also preferably higher than that in other regions of the block 100b. In addition, the nickel concentration in the grain boundary 101 and its vicinity is also preferably higher than that in other regions of the block 100b. In addition, the aluminum concentration in the grain boundary 101 and its vicinity is also preferably higher than that in other regions of the block 100b.
[0479] The grain boundary 101 is a type of surface defect. Therefore, it tends to be unstable like the surface and is easy to start the change of crystal structure. Therefore, the higher the concentration of the additive element A in the grain boundary 101 and its vicinity, the more effectively the change of crystal structure can be suppressed.
[0480] In addition, when the magnesium concentration and fluorine concentration in the grain boundary 101 and its vicinity are high, even if cracks are generated along the grain boundary 101 of the positive electrode active material 100 of one embodiment of the present invention, the magnesium concentration and fluorine concentration near the surface generated by the cracks become high. Therefore, the corrosion resistance of the positive electrode active material to hydrofluoric acid after the cracks are generated can also be improved.
[0481] {Particle size}
[0482] When the particle size of the positive electrode active material 100 in one embodiment of the present invention is too large, there are the following problems: the diffusion of lithium becomes difficult; when applied on the current collector, the surface of the active material layer is too rough, etc. On the other hand, when the particle size of the positive electrode active material 100 is too small, there are the following problems: it is not easy to support the active material layer when applied on the current collector; excessive reaction with the electrolyte, etc. Therefore, the median particle size (D50) is preferably greater than 1 μm and less than 100 μm, more preferably greater than 2 μm and less than 40 μm, and further preferably greater than 5 μm and less than 30 μm. Alternatively, it is preferably greater than 1 μm and less than 40 μm. Alternatively, it is preferably greater than 1 μm and less than 30 μm. Alternatively, it is preferably greater than 2 μm and less than 100 μm. Alternatively, it is preferably greater than 2 μm and less than 30 μm. Alternatively, it is preferably greater than 5 μm and less than 100 μm. Alternatively, it is preferably greater than 5 μm and less than 40 μm.
[0483] {Analysis Methods}
[0484] In order to determine whether a positive electrode active material is in Li x The positive electrode active material 100 of one embodiment of the present invention, which has an O3' type crystal structure when x in CoO2 is small, can contain Li x The positive electrode of the positive electrode active material having a smaller x in CoO2 is judged by analyzing using XRD pattern, electron diffraction pattern, neutron diffraction pattern, ESR (Electron Spin Resonance) spectrum, NMR (Nuclear Magnetic Resonance) spectrum, and the like.
[0485] In particular, the XRD pattern is preferred because it has the following advantages: the symmetry of the transition metal M such as cobalt possessed by the positive electrode active material can be analyzed with high resolution; the height of the crystallinity and the orientation of the crystal can be compared; the periodic distortion and grain size of the lattice can be analyzed; sufficient accuracy can be obtained when directly measuring the positive electrode obtained by disassembling the secondary battery, etc. Through the XRD pattern, especially the powder XRD pattern, the diffraction peak of the crystal structure of the bulk 100b of the positive electrode active material 100 that occupies most of the volume of the positive electrode active material 100 can be obtained.
[0486] As described above, the positive electrode active material 100 according to one embodiment of the present invention is characterized in that: x When x in CoO2 is 1 or 0.24 or less, the crystal structure changes little. When charging at a high voltage, if the material with a large change in crystal structure accounts for more than 50%, the material cannot withstand high voltage charging and discharging, so it is not preferred.
[0487] It should be noted that sometimes the O3' type crystal structure cannot be obtained by adding only the additive element A. For example, even under the same conditions of lithium cobalt oxide containing magnesium and fluorine or lithium cobalt oxide containing magnesium and aluminum, depending on the concentration and distribution of the additive element A in Li x When x in CoO2 is 0.24 or less, the O3' type crystal structure may account for 50% or more, or the H1-3 type crystal structure may account for 50% or more.
[0488] In addition, when x is too small such as 0.1 or less or when the charging voltage exceeds 4.9 V, a H1-3 type or trigonal O1 type crystal structure may be generated in the positive electrode active material 100 of one embodiment of the present invention. Therefore, in order to determine whether it is the positive electrode active material 100 of one embodiment of the present invention, analysis of the crystal structure such as analysis of the XRD pattern and information such as the charge capacity (charge amount) or the charge voltage are required.
[0489] However, the positive electrode active material in a state where x is small may change its crystal structure when exposed to air. For example, it may change from an O3' type crystal structure to an H1-3 type structure. Therefore, all samples used in analyzing the crystal structure are preferably treated in an inert atmosphere such as an argon atmosphere.
[0490] In addition, whether the distribution of the additional element A contained in a positive electrode active material is in the above-mentioned state can be determined by analyzing, for example, XPS (X-ray Photoelectron Spectroscopy), EDX, EPMA (Electron Probe Micro Analysis) or the like.
[0491] In addition, the crystal structure of the surface layer portion 100 a , the grain boundary 101 , and the like can be analyzed by an electron diffraction pattern of a cross section of the positive electrode active material 100 , and the like.
[0492] <<Charging Method>>
[0493] Whether a composite oxide is a positive electrode active material 100 of one embodiment of the present invention can be determined by high voltage charging. For example, a coin battery (CR2032 type, 20 mm in diameter, 3.2 mm in height) is manufactured by using the composite oxide as the positive electrode and counter electrode lithium as the negative electrode, and high voltage charging can be performed.
[0494] More specifically, as the positive electrode, a positive electrode obtained by applying a slurry obtained by mixing a positive electrode active material, a conductive material, and a binder to a positive electrode current collector of an aluminum foil can be used.
[0495] Lithium metal can be used as the counter electrode. Note that the potential of the positive electrode when a material other than lithium metal is used as the counter electrode is different from that of the secondary battery. Unless otherwise specified, the voltage and potential in this specification and the like refer to the potential of the positive electrode.
[0496] As the electrolyte contained in the electrolytic solution, 1 mol / L lithium hexafluorophosphate (LiPF6) is used. As the electrolytic solution, a solution obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) at a volume ratio of 3:7 and 2 wt% vinylene carbonate (VC) can be used.
[0497] As the separator, a polypropylene porous film having a thickness of 25 μm can be used.
[0498] The positive electrode can and the negative electrode can may be formed of stainless steel (SUS).
[0499] The coin cell manufactured under the above conditions is charged at a constant current of 10 mA / g until any voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V). In order to observe the phase change of the positive electrode active material, it is preferred to charge at the above smaller current value. The temperature is set to 25°C or 45°C. After charging in this manner, the coin cell is disassembled in a glove box with an argon atmosphere and the positive electrode is taken out, thereby obtaining a positive electrode active material in any charged state. When various analyses are performed later, in order to prevent reaction with external components, it is preferably sealed under an argon atmosphere. For example, the measurement of the XRD pattern can be performed under the condition of a sealed container sealed in an argon atmosphere. In addition, it is preferred to take out the positive electrode for analysis immediately after charging. Specifically, it is preferred to analyze within 1 hour after charging, and more preferably within 30 minutes after charging.
[0500] In addition, when analyzing the crystal structure of the charged state after multiple charge and discharge, the multiple charge and discharge conditions may be different from the above-mentioned charging conditions. For example, charging can be performed at a current value of 100mA / g to perform constant current charging to any voltage (for example, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V), and then constant voltage charging is performed until the current value becomes 10mA / g, and discharging can be performed at a constant current discharge of 100mA / g to 2.5V.
[0501] Furthermore, when analyzing the crystal structure in a discharged state after multiple charge and discharge, for example, the battery may be discharged at a constant current of 100 mA / g to 2.5 V.
[0502] < <xrd>>
[0503] There is no particular limitation on the apparatus and conditions for measuring the XRD pattern if appropriate adjustments and corrections are made. For example, the measurement can be performed with the following apparatus and conditions.
[0504] XRD device: D8 ADVANCE manufactured by Bruker AXS
[0505] X-ray source: Cu
[0506] Output: 40kV, 40mA
[0507] Emission angle: Div. Slit, 0.5°
[0508] Detector: LynxEye
[0509] Scanning mode: 2θ / θ continuous scanning
[0510] Measuring range (2θ): 15° to 90°
[0511] Step width (2θ): set to 0.01°
[0512] Counting time: 1 second / step
[0513] Sample stage rotation: 15rpm
[0514] As a standard sample for adjustment and calibration, for example, a standard alumina sintered plate SRM 1976 of NIST (National Institute of Standards and Technology) or the like can be used.
[0515] When the sample to be measured is a powder sample, the sample can be mounted by the following methods: wearing it on a glass sample holder; or sprinkling the sample on a silicon non-reflective plate coated with grease; etc. When the sample to be measured is a positive electrode, the positive electrode active material layer can be mounted according to the measurement surface required by the device by attaching the positive electrode to the substrate with double-sided tape.
[0516] The monochromatization of characteristic X-rays can be performed using a filter or the like, or using XRD data analysis software after obtaining the XRD pattern. For example, DEFFRAC.EVA (XRD data analysis software manufactured by Bruker) can be used to extract the peaks shown by the CuKα1 line in addition to the peaks shown by the CuKα2 line. In addition, the software can also be used to remove background noise, etc.
[0517] In this specification, etc., when the 2θ value of a certain diffraction peak is mentioned, it means the 2θ value of the peak top of the diffraction peak that appears in the XRD pattern after fitting the calculation model. There is no particular limitation on the crystal structure analysis software used for fitting, for example, TOPASver.3 (crystal structure analysis software manufactured by Bruker) can be used.
[0518] Fig. 20 and Fig.21 The ideal powder XRD patterns calculated by CuKα1 radiation from the models of O3' type crystal structure and H1-3 type crystal structure are shown. In addition, for comparison, the XRD patterns calculated from Li x Ideal XRD patterns calculated for the crystal structures of LiCoO2 O3 and H1-3 type with x being 1 in CoO2 and trigonal O1 with x being 0. The patterns of LiCoO2(O3) and CoO2(O1) were prepared using the ReflexPowder Diffraction, one of the modules of Materials Studio (BIOVIA), based on the crystal structure information obtained from ICSD (Inorganic Crystal Structure Database) (see Non-Patent Document 3). The range of 2θ was set to 15° to 75°, Step size = 0.01, and wavelength λ1 = 1.540562×10 -10 m, λ2 are not set, and Monochromator is set to single. The pattern of the H1-3 type crystal structure is prepared in the same manner as the crystal structure information recorded in Non-Patent Document 2. The pattern of the O3' type crystal structure is prepared by the following method: the crystal structure is inferred from the XRD pattern of the positive electrode active material of one embodiment of the present invention and fitted using TOPAS ver.3, and the XRD pattern is prepared in the same manner as other structures.
[0519] like Fig. 20 As shown, in the O3'-type crystal structure, diffraction peaks appear at 2θ of 19.25±0.12° (19.13° or more and less than 19.37°) and 2θ of 45.47±0.10° (45.37° or more and less than 45.57°).
[0520] However, if Fig.21 As shown, in the H1-3 type crystal structure and the trigonal O1 type, the peak does not appear at the above position. x The appearance of diffraction peaks at 2θ=19.25±0.12° (19.13° or more and less than 19.37°) and 2θ=45.47±0.10° (45.37° or more and less than 45.57°) when x in CoO2 is small is a characteristic of the positive electrode active material 100 of one embodiment of the present invention.
[0521] This also indicates that: the position of the diffraction peak of the XRD pattern appearing in the crystal structure when x=1 is close to the position of the diffraction peak of the XRD appearing in the crystal structure when x≤0.24; more specifically, regarding the peaks appearing at 2θ above 42° and below 46° in the main diffraction peaks of the crystal structure when x=1 and the crystal structure when x≤0.24, the difference in 2θ is less than 0.7°, preferably less than 0.5°.
[0522] In addition, the positive electrode active material 100 of one embodiment of the present invention is Li x When x in CoO2 is small, it has an O3' type crystal structure, but the positive electrode active material 100 as a whole may not have an O3' type crystal structure. It may have other crystal structures, or it may be partially amorphous. Note that when performing Rietveld analysis on the XRD pattern, the O3' type crystal structure is preferably 50% or more, more preferably 60% or more, and further preferably 66% or more. When the O3' type crystal structure is 50% or more, more preferably 60% or more, and further preferably 66% or more, a positive electrode active material with sufficiently excellent cycle characteristics can be achieved.
[0523] Furthermore, the O3′ type crystal structure measured by Rietveld analysis after 100 or more charge and discharge cycles from the start of measurement is preferably 35% or more, more preferably 40% or more, and even more preferably 43% or more.
[0524] For analysis using the Rietveld method, for example, analysis program RIETAN-FP (see Non-Patent Document 4) can be used.
[0525] In addition, the sharpness of the diffraction peak in the XRD pattern indicates the height of the crystallinity. Therefore, each diffraction peak after charging is preferably sharp, that is, the half-width is preferably narrow. The half-width of the peak of the same crystal phase also varies according to the measurement conditions of the XRD pattern or the value of 2θ. When the above-mentioned measurement conditions are adopted, for example, the half-width of the peak observed at 2θ of 43° or more and 46° or less is preferably 0.2° or less, more preferably 0.15° or less, and further preferably 0.12° or less. Note that it is not necessary for all peaks to meet the above conditions. As long as a part of the peaks meet the above conditions, it can be said that the crystallinity of its crystal phase is higher. This higher crystallinity fully contributes to the stabilization of the crystal structure after charging.
[0526] In addition, the grain size of the O3' type crystal structure of the positive electrode active material 100 is reduced to only about 1 / 20 of that of LiCoO2(O3) in the discharged state. Therefore, even under the same XRD pattern measurement conditions as the positive electrode before charge and discharge, the Li x When x in CoO2 is small, a clear peak of O3' type crystal structure is confirmed. On the other hand, even if a part of the existing LiCoO2 may have a structure similar to O3' type crystal structure, the grain size will become smaller and its peak will become wider and smaller. The grain size can be obtained from the half width of the peak of the XRD pattern.
[0527] < <xps>>
[0528] XPS can analyze inorganic oxides and use monochromated aluminum Kα rays as the X-ray source. It can analyze the depth range of about 2nm to 8nm (typically less than 5nm) from the surface, so it can quantitatively analyze the concentration of each element in about half of the depth direction of the surface part 100a. In addition, by performing narrow scan analysis, the bonding state of the elements can be analyzed. The quantitative accuracy of XPS is about ±1 atomic% in many cases. Although it depends on the element, the detection limit is about 1 atomic%.
[0529] In the positive electrode active material 100 of one embodiment of the present invention, the concentration of one or more selected from the additive elements A in the surface portion 100a is preferably higher than the concentration in the bulk 100b. That is, the concentration of one or more selected from the additive elements A contained in the surface portion 100a is preferably higher than the average concentration of the positive electrode active material 100 as a whole. Therefore, for example, it can be said that the concentration of one or more selected from the additive elements A contained in the surface portion 100a measured by XPS or the like is preferably higher than the average concentration of the positive electrode active material 100 as a whole measured by ICP-MS or GD-MS or the like. For example, the magnesium concentration of at least a portion of the surface portion 100a measured by XPS or the like is preferably higher than the magnesium concentration of the positive electrode active material 100 as a whole. In addition, the nickel concentration of at least a portion of the surface portion 100a is preferably higher than the nickel concentration of the positive electrode active material 100 as a whole. In addition, the aluminum concentration of at least a portion of the surface portion 100a is preferably higher than the aluminum concentration of the positive electrode active material 100 as a whole. Furthermore, the fluorine concentration of at least a portion of the surface layer portion 100 a is preferably higher than the fluorine concentration of the entire positive electrode active material 100 .
[0530] Note that the surface and surface layer 100a of the positive electrode active material 100 of one embodiment of the present invention do not include carbonates, hydroxyls, etc. chemically adsorbed after the positive electrode active material 100 is manufactured. In addition, it does not include electrolytes, adhesives, conductive materials, or compounds derived from them attached to the surface of the positive electrode active material 100. Therefore, when quantifying the elements contained in the positive electrode active material, the following correction can also be performed, that is, removing carbon, hydrogen, excess oxygen, excess fluorine, etc. that may be detected by surface analysis such as XPS. For example, XPS can identify the type of bonding by analysis, and can also perform corrections to remove CF bonds derived from the adhesive.
[0531] In addition, the samples of the positive electrode active material and the positive electrode active material layer can be washed before various analyses to remove the electrolyte, adhesive, conductive material or compounds derived from them attached to the surface of the positive electrode active material. At this time, sometimes lithium is dissolved in the solvent used for washing, but the added element A is not easy to dissolve, so it has no effect on the atomic ratio of the added element A.
[0532] In addition, the concentration of the added element A can also be compared with the ratio of cobalt. By using the ratio with cobalt, the influence of carbonates chemically adsorbed after manufacturing the positive electrode active material can be reduced for comparison, so it is preferred. For example, the ratio of the number of atoms of magnesium and cobalt obtained by XPS analysis Mg / Co is preferably 0.4 or more and 1.5 or less. On the other hand, the Mg / Co obtained by ICP-MS analysis is preferably 0.001 or more and 0.06 or less.
[0533] Similarly, in order to fully ensure the path for the insertion and extraction of lithium, the concentration of lithium and cobalt in the surface portion 100a of the positive electrode active material 100 is preferably higher than the concentration of each added element A. This can be said that the concentration of lithium and cobalt in the surface portion 100a is preferably higher than the concentration of one or more of the added elements A selected from the surface portion 100a measured by XPS, etc. For example, the concentration of cobalt in at least a portion of the surface portion 100a measured by XPS, etc. is preferably higher than the concentration of magnesium in at least a portion of the surface portion 100a measured by XPS, etc. Similarly, the concentration of lithium is preferably higher than the concentration of magnesium. In addition, the concentration of cobalt is preferably higher than the concentration of nickel. Similarly, the concentration of lithium is preferably higher than the concentration of nickel. In addition, the concentration of cobalt is preferably higher than the concentration of aluminum. Similarly, the concentration of lithium is preferably higher than the concentration of aluminum. In addition, the concentration of cobalt is preferably higher than the concentration of fluorine. Similarly, the concentration of lithium is preferably higher than the concentration of fluorine.
[0534] In addition, the added element Y such as aluminum is more preferably widely distributed in a deeper region, for example, a region with a depth of 5 nm or more and within 50 nm from the surface. Therefore, the added element Y such as aluminum is detected in the overall analysis of the positive electrode active material 100 using ICP-MS, GD-MS, etc., but it is more preferred that the added element Y such as aluminum is below the detection limit in XPS, etc.
[0535] Furthermore, when the positive electrode active material 100 of one embodiment of the present invention is subjected to XPS analysis, the number of atoms of magnesium relative to the number of atoms of cobalt is preferably 0.4 times or more and 1.2 times or less, and more preferably 0.65 times or more and 1.0 times or less. In addition, the number of atoms of nickel relative to the number of atoms of cobalt is preferably 0.15 times or less, and more preferably 0.03 times or more and 0.13 times or less. In addition, the number of atoms of aluminum relative to the number of atoms of cobalt is preferably 0.12 times or less, and more preferably 0.09 times or less. In addition, the number of atoms of fluorine relative to the number of atoms of cobalt is preferably 0.3 times or more and 0.9 times or less, and more preferably 0.1 times or more and 1.1 times or less.
[0536] When performing XPS analysis, for example, monochromatized aluminum Kα rays can be used as an X-ray source. In addition, for example, the extraction angle can be 45°. For example, the measurement can be performed with the following apparatus and conditions.
[0537] Measuring device: Quantera II manufactured by PHI
[0538] X-ray source: monochromated aluminum Kα (1486.6 eV)
[0539] Detection area:
[0540] Detection depth: about 4nm to 5nm (extraction angle is 45°)
[0541] Measurement spectrum: wide scan, narrow scan of each detection element
[0542] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, the peak of the bonding energy between fluorine and other elements is preferably 682 eV or more and less than 685 eV, and more preferably about 684.3 eV. This value is different from the bonding energy of lithium fluoride of 685 eV and the bonding energy of magnesium fluoride of 686 eV.
[0543] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, the peak of the bonding energy between magnesium and other elements is preferably 1302 eV or more and less than 1304 eV, and more preferably about 1303 eV. This value is different from the bonding energy of magnesium fluoride, which is 1305 eV, and is close to the bonding energy of magnesium oxide.
[0544] < <edx>>
[0545] One or two selected from the additional elements A contained in the positive electrode active material 100 preferably have a concentration gradient. In addition, the positive electrode active material 100 is more preferably different in depth from the surface according to the concentration peak of the additional element A. The concentration gradient of the additional element A can be evaluated by, for example, exposing a cross section of the positive electrode active material 100 by FIB or the like and analyzing the cross section by EDX, EPMA or the like.
[0546] In EDX measurement, the method of measuring while scanning in the region to perform two-dimensional evaluation is called EDX surface analysis. In addition, the method of evaluating the atomic concentration distribution in the positive electrode active material by scanning in a linear manner and measuring is called line analysis. Sometimes the method of extracting the data of the linear region from the surface analysis of EDX is called line analysis. In addition, the method of measuring a certain region without scanning is called point analysis.
[0547] By EDX surface analysis (e.g., element mapping), the concentration of the added element A in the surface portion 100a, bulk 100b, and near the grain boundary 101 of the positive electrode active material 100 can be semi-quantitatively analyzed. In addition, by EDX line analysis, the concentration distribution and maximum value of the added element A can be analyzed. In addition, in the analysis of thinning the sample such as STEM-EDX, the concentration distribution in the depth direction from the surface of the positive electrode active material in a specific area to the center can be analyzed without being affected by the distribution in the depth direction, so it is preferred.
[0548] Therefore, when EDX surface analysis or EDX point analysis is performed on the positive electrode active material 100 of one embodiment of the present invention, the concentration of each additional element A, especially the additional element X, is preferably higher in the surface layer portion 100 a than in the bulk 100 b .
[0549] For example, when performing EDX surface analysis or EDX point analysis on the positive electrode active material 100 containing magnesium as an added element X, the magnesium concentration of the surface portion 100a is preferably higher than the magnesium concentration of the bulk 100b. In addition, when performing EDX line analysis, the magnesium concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. In addition, the magnesium concentration is preferably reduced to less than 60% of the peak concentration at a point from the peak top to a depth of 1nm. In addition, it is preferred that the peak concentration is reduced to less than 30% of the peak concentration at a point from the peak top to a depth of 2nm. Here, the concentration peak refers to the maximum value of the concentration.
[0550] In addition, in the positive electrode active material 100 containing magnesium and fluorine as the added element X, the distribution of fluorine preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction between the fluorine concentration peak and the magnesium concentration peak is preferably within 10 nm, more preferably within 3 nm, and further preferably within 1 nm.
[0551] In addition, when performing EDX line analysis, the fluorine concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. In addition, the fluorine concentration peak is preferably slightly closer to the surface side than the magnesium concentration peak, and the resistance to fluorine is improved at this time, so it is preferred. For example, the fluorine concentration peak is preferably closer to the surface side by more than 0.5nm than the magnesium concentration peak, and more preferably closer to the surface side by more than 1.5nm than the magnesium concentration peak.
[0552] In addition, in the positive electrode active material 100 containing nickel as the added element X, the nickel concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface to the center of the positive electrode active material 100, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. In addition, in the positive electrode active material 100 containing magnesium and nickel, the distribution of nickel preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction of the nickel concentration peak and the magnesium concentration peak is preferably within 10nm, more preferably within 3nm, and further preferably within 1nm.
[0553] In addition, when the positive electrode active material 100 includes aluminum as an additive element Y, when performing EDX line analysis, it is preferred that the concentration peak of magnesium, nickel or fluorine is closer to the surface than the aluminum concentration peak of the surface portion 100a. For example, the aluminum concentration peak preferably appears in a range of 0.5 nm or more and 50 nm or less from the surface of the positive electrode active material 100 to the center, and more preferably appears in a range of 5 nm or more and 50 nm or less.
[0554] In addition, when the positive electrode active material 100 is subjected to EDX line analysis, surface analysis or point analysis, the ratio of the number of atoms of magnesium Mg to cobalt Co in the magnesium concentration peak (Mg / Co) is preferably 0.05 or more and 0.6 or less, more preferably 0.1 or more and 0.4 or less. The ratio of the number of atoms of aluminum Al to cobalt Co in the aluminum concentration peak (Al / Co) is preferably 0.05 or more and 0.6 or less, more preferably 0.1 or more and 0.45 or less. The ratio of the number of atoms of nickel Ni to cobalt Co in the nickel concentration peak (Ni / Co) is preferably 0 or more and 0.2 or less, more preferably 0.01 or more and 0.1 or less. The ratio of the number of atoms of fluorine F to cobalt Co in the fluorine concentration peak (F / Co) is preferably 0 or more and 1.6 or less, more preferably 0.1 or more and 1.4 or less.
[0555] From the EDX line analysis results, the surface of the positive electrode active material 100 can be estimated as follows: The point where the amount of an element uniformly present in the bulk 100b of the positive electrode active material 100, such as oxygen or cobalt, becomes 1 / 2 of the detected amount of the bulk 100b is the surface.
[0556] The positive electrode active material 100 is a composite oxide, so the surface can be estimated using the detected amount of oxygen. Specifically, first, the average value of the oxygen concentration is obtained from the region where the detected amount of oxygen in the bulk 100b is stable. ave At this time, when oxygen O is detected in an area that can be judged to be clearly outside the surface, it is possible that it is caused by chemical adsorption or background. background When O is subtracted from the measured value background To find the average oxygen concentration O ave It can be inferred that the average value O ave The value of 1 / 2 is closest to 1 / 2O ave The measurement point of the measured value is the surface of the positive electrode active material.
[0557] In addition, the surface can be estimated in the same manner as described above using the detected amount of cobalt. Alternatively, the surface can be estimated in the same manner using the sum of the detected amounts of multiple transition metals. The detected amount of transition metals such as cobalt is not easily affected by chemical adsorption, which is very suitable for surface estimation.
[0558] When the positive electrode active material 100 is subjected to line analysis or surface analysis, the ratio of the added element A to cobalt Co near the grain boundary 101 (A / Co) is preferably greater than 0.020 and less than 0.50. More preferably, it is greater than 0.025 and less than 0.30. Further preferably, it is greater than 0.030 and less than 0.20. Alternatively, it is preferably greater than 0.020 and less than 0.30. Alternatively, it is preferably greater than 0.020 and less than 0.20. Alternatively, it is preferably greater than 0.025 and less than 0.50. Alternatively, it is preferably greater than 0.025 and less than 0.20. Alternatively, it is preferably greater than 0.030 and less than 0.50. Alternatively, it is preferably greater than 0.030 and less than 0.30.
[0559] For example, when the added element X is magnesium, when the positive electrode active material 100 is subjected to line analysis or surface analysis, the ratio of the number of atoms of magnesium to cobalt near the grain boundary 101 (Mg / Co) is preferably greater than 0.020 and less than 0.50. More preferably, it is greater than 0.025 and less than 0.30. Further preferably, it is greater than 0.030 and less than 0.20. Alternatively, it is preferably greater than 0.020 and less than 0.30. Alternatively, it is preferably greater than 0.020 and less than 0.20. Alternatively, it is preferably greater than 0.025 and less than 0.50. Alternatively, it is preferably greater than 0.025 and less than 0.20. Alternatively, it is preferably greater than 0.030 and less than 0.50. Alternatively, it is preferably greater than 0.030 and less than 0.30.
[0560] < <epma>>
[0561] EPMA can also be used to quantify elements. In surface analysis, the distribution of each element can be analyzed.
[0562] Similar to the analysis results of EDX, when the cross section of the positive electrode active material 100 of one embodiment of the present invention is subjected to EPMA surface analysis, one or more of the selected additive elements A preferably have a concentration gradient. In addition, it is more preferred that the depth of the concentration peak from the surface is different depending on the additive element A. The preferred range of the concentration peak of each additive element A is also the same as that of the EDX analysis.
[0563] Note that in EPMA, the area with a depth of about 1 μm from the surface is analyzed. Therefore, the quantitative value of each element may be different from the measurement result measured by other analysis methods. For example, when analyzing the surface of the positive electrode active material 100 by EPMA, the concentration of each added element A present in the surface layer 100a may be lower than the result measured by XPS.
[0564] <<Charging curve and dQ / dV curve>>
[0565] The positive electrode active material 100 of one embodiment of the present invention sometimes has a unique voltage change when charging. The voltage change can be read from the dQ / dV curve obtained by the differential (dQ / dV) of the capacity (Q) and the voltage (V) in the charging curve. For example, it is possible that a non-equilibrium phase change occurs near the peak of the dQ / dV curve, and the crystal structure changes greatly. In this specification, etc., a non-equilibrium phase change refers to a phenomenon in which a nonlinear change in a physical quantity occurs.
[0566] The positive electrode active material 100 of one embodiment of the present invention sometimes has a broad peak near 4.55V of the dQ / dV curve. The peak near 4.55V reflects the change in voltage when the phase changes from the O3 type to the O3' type. Therefore, the wider the peak is, the less change in energy required when lithium is extracted, that is, the less change in the crystal structure, compared with the case where the peak is sharp. The deviation of the CoO2 layer and the change in volume have little effect, so the above changes are preferably less.
[0567] More specifically, when the maximum value appearing at 4.5V to 4.6V of the dQ / dV curve of the charging curve is recorded as the first peak, it is preferable that the half-peak width of the first peak is 0.10V or more because it can be said to be sufficiently wide. In this specification, etc., the half-peak width of the first peak is set as follows: when the minimum value of the dQ / dV value appearing at 4.3V to 4.5V is taken as the first minimum value, the difference between the average value HWHM1 of the first peak and the first minimum value and the average value HWHM2 of the first peak and the second minimum value when the minimum value of the dQ / dV value appearing at 4.6V to 4.8V is the second minimum value.
[0568] The charging when obtaining the dQ / dV curve may be, for example, performed by constant current charging at 10 mA / g to 4.9 V. When obtaining the dQ / dV in the initial charge, it is preferred that the battery be discharged at 100 mA / g to 2.5 V before measurement and then the charging is started.
[0569] For example, the data reading interval during charging can be set as follows: 1 second interval; or every time a 1mV voltage change occurs, the voltage and current are read. The integrated value of the current value and time is set as the charging capacity (charged electricity).
[0570] The difference between the nth data and the n+1th data in the above-mentioned charging capacity (charge amount) data is set as the nth value of the capacity change dQ. Similarly, the difference between the nth data and the n+1th data in the above-mentioned voltage data is set as the nth value of the voltage change dV.
[0571] Note that when using the above data, the influence of minute noise is large, so the difference between voltage and charge capacity (charge amount) can also be calculated by calculating dQ / dV from the moving average of an arbitrary number of intervals. The number of intervals can be set to 500, for example.
[0572] Specifically, the average value of the dQ from the nth to the n+500th is calculated, and the average value of the dV from the nth to the n+500th is calculated similarly. dQ (average of 500 dQs) / dV (average of 500 dVs) can be used as dQ / dV. The voltage on the horizontal axis of the dQ / dV chart can also use a moving average value of 500 intervals. Note that when using the moving average value of 500 intervals, the data from the 501st to the last data is greatly affected by noise, so it is preferably not used in the dQ / dV chart.
[0573] In addition, when analyzing the dQ / dV curve after multiple charge and discharge, the multiple charge and discharge conditions may be different from the above-mentioned charging conditions. For example, charging may be performed at a constant current of 100 mA / g to any voltage (e.g., 4.6 V, 4.65 V, 4.7 V, 4.75 V, or 4.8 V), and then constant voltage charging may be performed at a current value of 10 mA / g, and discharging may be performed at a constant current of 100 mA / g to 2.5 V.
[0574] In addition, the phase changes from O3 type to O3' type at around 4.55V. At this time, Li x The x in CoO2 is about 0.3. The O3 type structure when x is about 0.3 is similar to Fig.17 The O3 type with x being 1 described above has the same symmetry, but the distance between the CoO2 layers is slightly different. When different O3 types with different x sizes are distinguished in this specification, the O3 type with x being 1 is called O3 (2θ is 18.85), and the O3 type with x being about 0.3 is called O3 (2θ is 18.57). This is because the position of the peak that appears near 2θ of 19° in the measurement of the XRD pattern corresponds to the distance between the CoO2 layers.
[0575] <<Discharge Curve and dQ / dV Curve>>
[0576] When the positive electrode active material 100 of one embodiment of the present invention is discharged at a low current of, for example, 40 mA / g or less after being charged at a high voltage, a characteristic voltage change occurs near the end of the discharge. This change can be clearly observed when at least one peak in dQ / dV calculated from the discharge curve is within a voltage range from a lower voltage than the peak appearing at about 3.9 V to 3.5 V.
[0577] < <esr>>
[0578] In the positive electrode active material 100 of one embodiment of the present invention, it is preferred that cobalt is contained and nickel and magnesium are contained as the additive element A. As a result, it is preferred that a portion of Co 3+ Be Ni 3+ Replace and part of Li + Mg 2+ Replace. With Li + Mg 2+ Replacement, sometimes the Ni 3+ Reduced to Ni 2+ In addition, as part of Li + Mg 2+ Replacement, sometimes Mg 2+ Nearby Co 3+ is reduced to Co 2+ In addition, as part of Co 3+ Mg 2+ Replacement, sometimes Mg 2+ Nearby Co 3+ Oxidized to Co 4+ .
[0579] Therefore, the positive electrode active material 100 preferably contains Ni 2+ 、Ni 3+ 、Co 2+ and Co 4+ In addition, the unit weight of the positive electrode active material 100 is caused by Ni 2+ 、Ni 3+ 、Co 2+ and Co 4+ The spin density of any one or more of 17 spins / g and above 1.0×10 21 spins / g or less. The positive electrode active material 100 has the above spin density, which is preferred because the crystal structure is stable, especially in the charged state. Note that when the magnesium concentration is too high, Ni 2+ 、Ni 3+ 、Co 2+ and Co 4+ The spin density of any one or more of them decreases.
[0580] For example, the spin density in the positive electrode active material can be analyzed by using ESR spectroscopy or the like.
[0581] <<Surface roughness and specific surface area>>
[0582] The positive electrode active material 100 of one embodiment of the present invention preferably has a smooth surface and few irregularities. A smooth surface and few irregularities indicate that the effect of the flux described later is fully exerted and the surface of the source of the added element A and the composite oxide is melted. Therefore, this is an element indicating that the distribution of the added element A in the surface portion 100a is good. "Good distribution" means, for example, that the concentration distribution of the added element A in the surface portion 100a is uniform.
[0583] For example, whether the surface is smooth and has few irregularities can be determined by referring to a cross-sectional SEM image or a cross-sectional TEM image of the positive electrode active material 100 , the specific surface area of the positive electrode active material 100 , or the like.
[0584] For example, as shown below, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 .
[0585] First, the positive electrode active material 100 is processed by FIB or the like to expose its cross section. At this time, it is preferred to cover the positive electrode active material 100 with a protective film, a protective agent, or the like. Next, a SEM image of the interface between the protective film or the like and the positive electrode active material 100 is taken. The SEM image is subjected to noise processing using image processing software. For example, binarization is performed after Gaussian Blur (σ=2). In addition, the interface is extracted using image processing software. Furthermore, the interface line between the protective film or the like and the positive electrode active material 100 is selected using an automatic selection tool, and the data is extracted to a spreadsheet software or the like. The root mean square (RMS) surface roughness is calculated using the function of a spreadsheet software or the like as described below, that is, correction is performed according to a regression curve (quadratic regression), and the roughness calculation parameters are calculated from the tilt-corrected data, thereby calculating the standard deviation. In addition, the surface roughness is the surface roughness of at least 400 nm around the periphery of the positive electrode active material.
[0586] The surface of the positive electrode active material 100 described in this embodiment has a root mean square (RMS) surface roughness, which is an index of roughness, of preferably less than 3 nm, more preferably less than 1 nm, and still more preferably less than 0.5 nm.
[0587] Note that there is no particular limitation on image processing software for performing noise processing, interface extraction, etc., and for example, "ImageJ" described in Non-Patent Documents 5 to 7 can be used. In addition, there is no particular limitation on spreadsheet software, and for example, Microsoft Office Excel can be used.
[0588] For example, the actual specific surface area S measured by the constant volume gas adsorption method can also be used. R With the ideal specific surface area S i The ratio of quantifies the surface smoothness of the positive electrode active material 100.
[0589] Ideal specific surface area S i The value was calculated based on the assumption that all positive electrode active materials had the same diameter and median diameter (D50), the same weight, and an ideal spherical shape.
[0590] The median particle size (D50) can be measured by a particle size distribution analyzer using a laser diffraction and scattering method, etc. The specific surface area can be measured by a specific surface area measuring device using a constant volume gas adsorption method, etc., for example.
[0591] In the positive electrode active material 100 of one embodiment of the present invention, the ideal specific surface area S obtained from the median diameter (D50) is preferably i Compared with the actual specific surface area S R The ratio S R / S i Below 2.1.
[0592] Alternatively, the surface smoothness can be quantified from a cross-sectional SEM image of the positive electrode active material 100 by the following method.
[0593] First, a surface SEM image of the positive electrode active material 100 is obtained. At this time, a conductive coating may be performed as a pretreatment for observation. The observation surface is preferably perpendicular to the electron beam. When comparing multiple samples, the measurement conditions and observation area are set to be the same.
[0594] Next, use image processing software (e.g., "ImageJ") to obtain, for example, an 8-bit image (called a grayscale image) by converting the above SEM image. The grayscale image includes brightness (brightness information). For example, in an 8-bit grayscale image, the brightness can be represented by 2 to the 8th power = 256 grayscales. The grayscale number of the dark part is low, and the grayscale number of the bright part is high. The brightness change can be quantified in association with the grayscale number. This numerical value is called a grayscale value. By obtaining the grayscale value, the concavity and convexity of the positive electrode active material can be evaluated as a numerical value.
[0595] In addition, the brightness change of the target area can also be represented by a histogram. Here, the histogram represents the brightness distribution in the target area in a graphical form, and is also called a brightness histogram. By obtaining a brightness histogram, the unevenness of the positive electrode active material can be evaluated in a visually clear manner.
[0596] The difference between the maximum and minimum values of the grayscale value of the positive electrode active material 100 of one embodiment of the present invention is preferably 120 or less, more preferably 115 or less, and further preferably 70 or more and 115 or less. In addition, the standard deviation of the grayscale value is preferably 11 or less, more preferably 8 or less, and further preferably 4 or more and 8 or less.
[0597] <<Current dormancy method>>
[0598] The distribution of the added element A such as magnesium contained in the surface layer of the positive electrode active material 100 of one embodiment of the present invention sometimes changes slightly during repeated charge and discharge. For example, sometimes the distribution of the added element A becomes better and the resistance decreases. Therefore, at the beginning of the charge and discharge cycle, sometimes the resistance, that is, the faster-response resistance component R (0.1s) measured by the current dormancy method, decreases.
[0599] For example, when comparing the nth (n is an integer greater than 2) charge and the n+1th charge, sometimes the faster-responding resistance component R (0.1s) measured by the current dormancy method of the n+1th charge is lower than that of the nth charge. Therefore, the discharge capacity of the n+1th charge is sometimes higher than that of the nth charge. When n is 1, that is, when comparing the first charge and the second charge, it is possible that the second discharge capacity is larger in the positive electrode active material that does not contain the added element, so for example, n is preferably greater than 2 and less than 10. Note that this is not limited to the initial stage of the charge and discharge cycle. When the charge and discharge capacity is the same as the rated capacity, for example, when the discharge capacity is greater than 97% of the rated capacity, it can be said to be the initial stage of the charge and discharge cycle.
[0600] {Other Features}
[0601] Other features of the positive electrode active material according to one embodiment of the present invention will be described.
[0602] The positive electrode active material 100 may have a covering portion. The covering portion may not cover the entire positive electrode active material. The covering portion may be an inorganic compound formed when the positive electrode active material is manufactured, or may be an electrolyte deposited during charge and discharge or a decomposition product of an organic electrolyte.
[0603] In the case where the coating contains electrolyte and decomposition products of organic electrolyte, it is preferred to contain carbon, oxygen and fluorine. Furthermore, when at least one of LiBOB and SUN (suberonitrile) is used in a part of the electrolyte, a high-quality coating is easily obtained. Therefore, a coating containing one or more selected from boron, nitrogen, sulfur and fluorine is sometimes a high-quality coating, so it is preferred.
[0604] The positive electrode active material 100 may have concave portions, cracks, depressions, V-shaped cross sections, etc. These are defects, and when charging and discharging are repeated, they may cause dissolution of the transition metal M, collapse of the crystal structure, rupture of the positive electrode active material 100, and separation of oxygen. However, in the presence of these defects, Fig. 14B When the embedded portion 102 is formed, dissolution of the transition metal M can be suppressed. Therefore, the positive electrode active material 100 having excellent reliability and cycle characteristics can be manufactured.
[0605] In addition, as a region where the additive element A is concentratedly distributed, the positive electrode active material 100 may also include Fig. 14B The convex portion 103 is shown.
[0606] As described above, when the positive electrode active material 100 contains an excess of the added element A, there is a concern that the insertion and extraction of lithium may be negatively affected. In addition, there is also a concern that the internal resistance may increase or the discharge capacity may decrease when manufacturing a secondary battery. On the other hand, when the added element A is insufficient, the added element A is not distributed throughout the surface portion 100a, and it is possible that the effect of sufficiently suppressing the degradation of the crystal structure may not be obtained. In this way, although the added element A in the positive electrode active material 100 needs to have an appropriate concentration, it is not easy to adjust its concentration.
[0607] Therefore, when the positive electrode active material 100 has an area where the additive element A is concentratedly distributed, a portion of the excess additive element A is removed from the block 100b of the positive electrode active material 100, and a suitable concentration of the additive element A can be achieved in the block 100b. As a result, the increase in internal resistance and the decrease in discharge capacity when manufacturing a secondary battery can be suppressed. The ability to suppress the increase in the internal resistance of a secondary battery is a very good characteristic, especially in large current charging and discharging, for example, charging and discharging at 400mA / g or more.
[0608] In addition, in the positive electrode active material 100 having a region where the additive element A is concentratedly distributed, a certain amount of excess additive element A may be mixed in the manufacturing process. This is preferred because the degree of freedom in production is increased.
[0609] In addition, when charging and discharging at a temperature of 4.5 V or above or at a high temperature of 45 ° C or above, a progressive defect that deepens from the surface to the inside is sometimes generated in the positive electrode active material. The phenomenon that defects in the positive electrode active material form holes can also be called pitting corrosion. In this specification, the holes generated in this phenomenon are also called pits.
[0610] Fig. 22 1 is a schematic cross-sectional view showing a positive electrode active material 51 having pits. In addition, a crystal plane 55 parallel to the cation arrangement is also shown. Fig. 22 Since this is a cross-sectional view, the pits 54 and 58 are shown as holes, but the opening shape is not circular but a deep groove-like shape. In addition, unlike the recessed portion 52, the pits 54 and 58 are easily generated parallel to the arrangement of lithium ions.
[0611] In addition, symbols 53 and 56 indicate that there is a surface portion of the added element A in the positive electrode active material 51. In the surface portion where the pits are generated, the added element A is less than the surface portions 53 and 56 or the added element A is below the detection limit, and it can be considered that the function of the barrier film is reduced. In addition, the crystal structure of the composite oxide may collapse near the pits and become a crystal structure different from the layered rock salt type crystal structure. When the crystal structure collapses, the diffusion and release of lithium ions as carrier ions are blocked, so the pits may be the cause of the deterioration of the cycle characteristics.
[0612] The pits may be caused by point defects. It is possible that the point defects of the positive electrode active material change due to repeated charge and discharge, and pits are caused by chemical or electrochemical corrosion of the surrounding electrolyte or material degradation. This degradation does not occur uniformly on the surface of the positive electrode active material but occurs locally and concentratedly.
[0613] In addition, if Fig. 22 Sometimes, defects such as cracks (also called fissures) are generated due to the expansion and contraction of the positive electrode active material during charge and discharge, such as the cracks 57 in the positive electrode active material. In this specification, etc., cracks are different from pits. Immediately after the positive electrode active material is manufactured, cracks exist but pits do not exist. Pits can be said to be holes formed by extracting transition metal M and oxygen in several layers by charging and discharging at high voltage conditions such as above 4.5V or high temperature (above 45°C). They can also be said to be parts where transition metal M is dissolved. Cracks refer to, for example, new surfaces generated by the application of physical pressure or cracks generated by grain boundaries 101. Sometimes cracks are generated due to the expansion and contraction of the positive electrode active material that occurs with charge and discharge. In addition, pits are sometimes generated from at least one of cracks and cavities inside the positive electrode active material.
[0614] [Method for producing positive electrode active material]
[0615] In order to produce the positive electrode active material 100 having at least one of the distribution, composition and crystal structure of the additive element A, it is important to use a method of adding the additive element A. Furthermore, it is also important that the bulk 100 b has good crystallinity.
[0616] Therefore, in the manufacturing process of the positive electrode active material 100 , it is preferable to first synthesize a composite oxide containing lithium and a transition metal, and then add a source of the element A to the mixture and perform a heat treatment.
[0617] In the method of simultaneously mixing the transition metal M source, the lithium source and the additive element A source to synthesize the additive element A and the composite oxide containing lithium and the transition metal M, it is not easy to increase the concentration of the additive element A in the surface layer portion 100a. In addition, when only the additive element source A is mixed without heating after synthesizing the composite oxide containing lithium and the transition metal M, the additive element A only adheres to the composite oxide and does not dissolve in the composite oxide. Unless it is sufficiently heated, it is not easy to distribute the additive element A well. Therefore, it is preferred that the additive element A source is mixed after the composite oxide is synthesized to perform a heat treatment. Sometimes the heat treatment after the mixing of the additive element A source is called annealing.
[0618] However, when the annealing temperature is too high, cation mixing occurs and the possibility of the added element A such as magnesium entering the transition metal M position increases. Magnesium existing at the transition metal M position does not have x When x in CoO2 is small, the effect of maintaining the R-3m layered rock salt type crystal structure is maintained. In addition, when the heating temperature is too high, there is a concern that cobalt is reduced to become divalent, lithium evaporates, and other adverse effects may occur.
[0619] Therefore, it is preferred to mix the source of the additive element A and the material used as a flux. A material whose melting point is lower than that of the composite oxide containing lithium and transition metal M can be said to be a material used as a flux. For example, fluorine compounds such as lithium fluoride are preferred. When the flux is added, the melting point of the source of the additive element A and the composite oxide containing lithium and transition metal M decreases. By performing the melting point decrease, the additive element A can be easily distributed well at a temperature where cation mixing is not likely to occur.
[0620] Furthermore, it is more preferable to perform heating after synthesizing the composite oxide containing lithium and the transition metal M and before mixing and adding the element A. This heating may be referred to as initial heating.
[0621] By performing the initial heating, lithium is released from a part of the surface layer portion 100 a of the composite oxide containing lithium and the transition metal M, so that the distribution of the additive element A becomes better.
[0622] More specifically, it is possible that the distribution of each additive element A is easily different due to the initial heating through the following mechanism. First, lithium is separated from a part of the surface portion 100a due to the initial heating. Next, the composite oxide containing lithium and transition metal M having the surface portion 100a lacking lithium is mixed with a source of additive element A such as a nickel source, an aluminum source, and a magnesium source, and heated. Magnesium in the additive element A is a typical divalent element, and nickel is a transition metal but easily becomes a divalent ion. Therefore, a composite oxide containing Mg is formed in a part of the surface portion 100a. 2+ And Ni 2+ and Co reduced due to lithium deficiency 2+ of rock salt type phase.
[0623] When the surface portion 100a is a layered rock salt type composite oxide containing lithium and transition metal M, the nickel in the added element A is easily dissolved and diffused into the bulk 100b, but when a part of the surface portion 100a is a rock salt type, it is easy to remain in the surface portion 100a.
[0624] In addition, in these rock salt types, the bonding distance between metal Me and oxygen (Me—O distance) tends to be longer than that of the layered rock salt type.
[0625] For example, rock salt Ni 0.5 Mg 0.5 The Me-O distance in O is The Me-O distance in rock salt MgO is If a spinel phase is formed in a part of the surface layer 100a, the Me-O distance of the spinel NiAl2O4 is The Me-O distance of spinel MgAl2O4 is The above distances are more than in addition,
[0626] On the other hand, the bonding distance between metals other than lithium and oxygen in the layered rock salt type is shorter than the above distance. For example, the Al-O distance in the layered rock salt type LiAlO2 is (Li-O distance is ). In addition, the Co-O distance in layered rock salt LiCoO2 is (Li-O distance is ).
[0627] In addition, according to Shannon ionic radius (Shannon, RD Acta Crystallogr. 1976, A32, 751.), the ionic radius of hexacoordinated aluminum is The ionic radius of the hexacoordinated oxygen is Their sum is
[0628] Thus, compared with the rock salt type, aluminum is more likely to exist in a position other than lithium in the layered rock salt type more stably. Therefore, compared with the area close to the surface having the rock salt type phase in the surface portion 100a, aluminum is more likely to be distributed in one or both of the deeper area having the layered rock salt type and the bulk 100b.
[0629] In addition, due to the initial heating, it is possible to exert the effect that the crystallinity of the layered rock salt type crystal structure of the bulk 100 b is improved.
[0630] However, initial heating is not always necessary. By controlling the atmosphere, temperature, time, etc. in other heating steps such as annealing, it is sometimes possible to produce Li x When x in CoO 2 is small, the positive electrode active material 100 has an O3′ type crystal structure.
[0631] Reference FIG. 23A to FIG. 23C An example of a production process of the positive electrode active material 100 after annealing and initial heating will be described.
[0632] {Step S11}
[0633] exist Fig.23A In step S11 shown in the figure, as starting materials of lithium and transition metal M, a lithium source (Li source) and a transition metal M source (M source) are prepared, respectively.
[0634] As the lithium source, a compound containing lithium is preferably used, for example, lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. The purity of the lithium source is preferably high, for example, a material with a purity of 99.99% or more is preferably used.
[0635] The transition metal M may be selected from the elements recorded in Groups 4 to 13 of the periodic table, for example, at least one of manganese, cobalt and nickel is used. As the transition metal M, only cobalt is used, only nickel is used, two kinds of cobalt and manganese are used, two kinds of cobalt and nickel are used, or three kinds of cobalt, manganese and nickel are used. When only cobalt is used, the positive electrode active material obtained includes lithium cobaltate (LCO), and when three kinds of cobalt, manganese and nickel are used, the positive electrode active material obtained includes nickel-cobalt-manganese oxide (NCM).
[0636] As the transition metal M source, a compound containing the above transition metal M is preferably used, for example, an oxide or hydroxide of the metal shown as an example of the above transition metal M can be used. As a cobalt source, cobalt oxide, cobalt hydroxide, etc. can be used. As a manganese source, manganese oxide, manganese hydroxide, etc. can be used. As a nickel source, nickel oxide, nickel hydroxide, etc. can be used. As an aluminum source, aluminum oxide, aluminum hydroxide, etc. can be used.
[0637] The purity of the transition metal M source is preferably high, for example, preferably a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and further preferably 5N (99.999%) or more. By using a high-purity material, impurities in the positive electrode active material can be controlled. As a result, the discharge capacity of the secondary battery is improved. In addition, the reliability of the secondary battery is improved.
[0638] In addition, the crystallinity of the transition metal M source is preferably high, for example, it preferably has single crystal particles. As a method for evaluating the crystallinity of the transition metal M source, there can be cited: judgment using TEM images, STEM images, HAADF-STEM images, ABF-STEM images, etc.; or judgment using XRD patterns, electron diffraction patterns, neutron diffraction patterns, etc. The above-mentioned method for evaluating crystallinity can also be used for evaluating other crystallinities in addition to the transition metal M source.
[0639] When two or more transition metal M sources are used, it is preferred that the two or more transition metal M sources be prepared in such a ratio (mixing ratio) that the two or more transition metal M sources can have a layered rock salt type crystal structure.
[0640] {Step S12}
[0641] Then, as Fig.23A In step S12 shown, the lithium source and the transition metal M source are crushed and mixed to produce a mixed material. The crushing and mixing can be performed by a dry method or a wet method. The wet method can grind smaller, so it is preferred. When crushing and mixing are performed by a wet method, a solvent is prepared. As a solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is preferred to use a non-protonic solvent that does not react easily with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. Preferably, the lithium source and the transition metal M source are mixed with dehydrated acetone with a moisture content suppressed to less than 10 ppm and a purity of 99.5% or more for crushing and mixing. By using dehydrated acetone of the above purity, impurities that may be mixed in can be reduced.
[0642] As a unit for mixing, a ball mill or a sand mill can be used. When a ball mill is used, alumina balls or zirconia balls are preferably used as the crushing medium. Zirconia balls are preferred because they have less impurities discharged. In addition, when a ball mill or a sand mill is used, in order to suppress contamination from the medium, the circumferential speed is preferably set to 100 mm / s or more and 2000 mm / s or less. In the present embodiment, the circumferential speed is preferably set to 838 mm / s (the number of rotations is 400 rpm, and the diameter of the ball mill is 40 mm) for crushing and mixing.
[0643] {Step S13}
[0644] Then, as Fig.23A In step S13 shown, the mixed material is heated. The heating temperature is preferably 800°C to 1100°C, more preferably 900°C to 1000°C, and further preferably about 950°C. When the temperature is too low, there is a concern that the decomposition and melting of the lithium source and the transition metal M source are insufficient. On the other hand, when the temperature is too high, defects may occur due to the following reasons, for example: lithium evaporates from the lithium source; or the metal used as the transition metal M source is excessively reduced; etc. As such a defect, for example, when cobalt is used as the transition metal M, the cobalt is excessively reduced and changes from trivalent to divalent, causing oxygen defects, etc.
[0645] When the heating time is too short, LiMO2 is not synthesized, but when the heating time is too long, the productivity decreases. For example, the heating time is preferably more than 1 hour and less than 100 hours, preferably more than 2 hours and less than 20 hours.
[0646] Although it varies depending on the temperature to be reached by the heating temperature, the heating rate is preferably 80° C. / h or more and 250° C. / h or less. For example, when heating at 1000° C. for 10 hours, the heating rate is preferably 200° C. / h.
[0647] The heating atmosphere is preferably carried out in an atmosphere with less water such as dry air, for example, preferably in an atmosphere with a dew point of -50°C or less, more preferably in an atmosphere with a dew point of -80°C or less. In this embodiment, heating is carried out in an atmosphere with a dew point of -93°C. In addition, in order to suppress impurities that may be mixed into the material, the impurity concentrations of CH4, CO, CO2, H2, etc. in the heating atmosphere are preferably all 5 ppb (parts per billion) or less.
[0648] As the heating atmosphere, an oxygen-containing atmosphere is preferably used. For example, a method of continuously introducing dry air into the reaction chamber can be cited. In this case, the flow rate of the dry air is preferably 10 L / min. The method of continuously introducing oxygen into the reaction chamber so that the oxygen flows through the reaction chamber is called "flowing".
[0649] When the heating atmosphere is an oxygen-containing atmosphere, a non-flowing method may also be used. For example, a method of first depressurizing the reaction chamber and then filling it with oxygen may be used to prevent the oxygen from leaking from the reaction chamber or entering the reaction chamber. This method is called purging. For example, the reaction chamber may be depressurized to -970 hPa, and then continuously filled with oxygen until the pressure reaches 50 hPa.
[0650] After heating, the mixture may be cooled naturally, and the cooling time from the specified temperature to room temperature is preferably in the range of 10 hours to 50 hours. Note that it is not necessarily necessary to cool to room temperature, but only to a temperature allowed by the next step.
[0651] The heating in this step can be performed using a rotary kiln or a roller hearth kiln. Heating using a continuous or batch-type rotary kiln can be performed while stirring.
[0652] The crucible or sheath used for heating preferably includes a material with high heat resistance such as a material made of alumina (aluminum oxide), a material made of mullite-cordierite, a material made of magnesium oxide, a material made of zirconium oxide, etc. In addition, since aluminum oxide is a material that does not easily mix impurities, the purity of the crucible or sheath made of alumina is 99% or more, preferably 99.5% or more. In this embodiment, a crucible made of aluminum oxide with a purity of 99.9% is used. It is preferred to heat the crucible or sheath by covering it with a lid. In this way, volatilization of the material can be prevented.
[0653] After the heating is completed, it can also be crushed and screened as needed. When recovering the heated material, the heated material can also be moved from the crucible to the mortar and then recovered. In addition, it is preferred to use a mortar made of aluminum oxide as the mortar. A mortar made of aluminum oxide does not easily release impurities. Specifically, a mortar with an aluminum oxide purity of 90% or more, preferably 99% or more, is used. In addition, the same heating conditions as step S13 can be used in the heating process described later other than step S13.
[0654] {Step S14}
[0655] Through the above process, Fig.23A In step S14 shown, a composite oxide (LiMO2) containing a transition metal M is obtained. The composite oxide may have a crystal structure of a lithium composite oxide represented by LiMO2, and its composition is not strictly limited to Li:M:O=1:1:2. When cobalt is used as the transition metal M, the composite oxide is called a composite oxide containing cobalt and represented by LiCoO2. The composition is not strictly limited to Li:Co:O=1:1:2.
[0656] Although an example in which the composite oxide is produced by a solid phase method as shown in steps S11 to S14 is shown, the composite oxide may also be produced by a coprecipitation method or a hydrothermal method.
[0657] {Step S15}
[0658] Then, as Fig.23A In step S15, the composite oxide is heated. This heating is the first heating of the composite oxide, so the heating in step S15 can be called initial heating. Alternatively, this heating is performed before step S20 shown below, and is sometimes called preheating treatment or pretreatment.
[0659] As described above, lithium is separated from a part of the surface layer of the composite oxide by initial heating. In addition, it is possible to cause an effect of improving the crystallinity of the bulk. In addition, one or both of the lithium source and the transition metal M prepared in step S11 etc. are sometimes mixed with impurities. By performing initial heating, impurities in the composite oxide completed in step S14 can be reduced.
[0660] After the initial heating, the surface of the composite oxide is also smoothed. The surface smoothness of the composite oxide means that there are fewer bumps and the whole is curved, and the corners are curved. In addition, the state with fewer foreign matter attached to the surface is also called "smooth". Foreign matter may be the cause of bumps and bumps, and it is preferred that it is not attached to the surface.
[0661] In the above-mentioned initial heating, it is not necessary to prepare a lithium compound source, or it is not necessary to prepare a source of the added element A, or it is not necessary to prepare a material used as a flux.
[0662] When the heating time of this step is too short, the full effect cannot be obtained, but when the heating time is too long, the productivity decreases. For example, it can be implemented by selecting from the heating conditions described in step S13. Supplementary explanation of the heating conditions: In order to maintain the crystal structure of the composite oxide, the heating temperature of this step is preferably lower than the temperature of step S13. In addition, in order to maintain the crystal structure of the composite oxide, the heating time of this step is preferably shorter than the heating time of step S13. For example, it is preferred to heat at a temperature of 700°C or more and 1000°C or less for 2 hours or more and 20 hours or less.
[0663] The effect of improving the crystallinity of the bulk refers to, for example, an effect of alleviating distortion, deviation, and the like caused by differences in shrinkage of the composite oxide produced in step S13.
[0664] In the above-mentioned composite oxide, a temperature difference sometimes occurs between the surface and the bulk of the composite oxide due to the heating of step S13. Sometimes the temperature difference leads to a shrinkage difference. Since the fluidity of the surface and the bulk is different according to the temperature difference, a shrinkage difference may occur. A difference in internal stress occurs in the composite oxide due to the energy associated with the shrinkage difference. The difference in internal stress is also called distortion, and this energy is sometimes called distortion energy. The internal stress may be removed by the initial heating of step S15, in other words, the distortion energy may be homogenized by the initial heating of step S15. When the distortion energy is homogenized, the distortion of the composite oxide is relaxed. Therefore, by step S15, the surface of the composite oxide may become smooth. It can also be said that the surface is improved. In other words, the shrinkage difference generated in the composite oxide by step S15 is relaxed, so that the surface of the composite oxide may become smooth.
[0665] In addition, the shrinkage difference sometimes leads to the generation of small deviations in the above-mentioned composite oxide, such as the generation of crystal deviations. In order to reduce this deviation, it is preferred to perform this process. Through this process, the deviation of the above-mentioned composite oxide can be uniformized. When the deviation is uniformized, the surface of the composite oxide may become smooth. It can also be said that the crystal particles are arranged. In other words, through step S15, the deviation of the crystals etc. generated in the composite oxide is alleviated, so that the surface of the composite oxide may become smooth.
[0666] By using a composite oxide having a smooth surface as a positive electrode active material, deterioration during charge and discharge as a secondary battery is reduced, and cracking of the positive electrode active material can be prevented.
[0667] When surface concavo-convex information is quantified based on measurement data on a cross section of a composite oxide, a smooth surface of the composite oxide can be considered to have a surface roughness of at least 10 nm or less. A cross section of a composite oxide is, for example, a cross section obtained by STEM observation.
[0668] In addition, a composite oxide containing lithium, transition metal M and oxygen synthesized in advance may be used in step S14. In this case, steps S11 to S13 may be omitted. By performing step S15 on the composite oxide synthesized in advance, a composite oxide having a smooth surface can be obtained.
[0669] The initial heating may reduce the amount of lithium in the composite oxide. As the amount of lithium is reduced, the additional element A described in the next step S20 may be easily incorporated into the composite oxide.
[0670] {Step S20}
[0671] In addition, the additive element A may be added to the composite oxide having a smooth surface within the range that the composite oxide has a layered rock salt type crystal structure. When the additive element A is added to the composite oxide having a smooth surface, the additive element A can be added uniformly. Therefore, it is preferred to perform initial heating first and then add the additive element A. Fig. 23B and Fig.23C Describe the steps for adding the additional element A.
[0672] {Step S21}
[0673] exist Fig. 23B In step S21 shown, a source of an additional element A (A source) to be added to the composite oxide is prepared. In addition to the source of the additional element A, a lithium source may be prepared.
[0674] As the additive element A, one or more selected from nickel, cobalt, magnesium, calcium, chlorine, fluorine, aluminum, manganese, titanium, zirconium, yttrium, vanadium, iron, chromium, niobium, lanthanum, hafnium, zinc, silicon, sulfur, phosphorus, boron and arsenic can be used. In addition, as the additive element, one or more selected from bromine and beryllium can be used. Note that bromine and beryllium are elements toxic to organisms, so it is preferable to use the above additive elements.
[0675] When magnesium is selected as the additive element A, the source of the additive element A may be referred to as a magnesium source. As the magnesium source, magnesium fluoride, magnesium oxide, magnesium hydroxide, magnesium carbonate, etc. may be used. In addition, a plurality of the above magnesium sources may be used.
[0676] When fluorine is selected as the additive element A, the source of the additive element A may be referred to as a fluorine source. As the fluorine source, for example, lithium fluoride, magnesium fluoride, aluminum fluoride, titanium fluoride, cobalt fluoride, nickel fluoride, zirconium fluoride, vanadium fluoride, manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride, calcium fluoride, sodium fluoride, potassium fluoride, barium fluoride, cerium fluoride, lanthanum fluoride or sodium aluminum hexafluoride may be used. Among them, lithium fluoride has a relatively low melting point of 848° C. and is easily melted in the heating step described later, so it is preferred.
[0677] Magnesium fluoride can be used as both a fluorine source and a magnesium source. In addition, lithium fluoride can be used as a lithium source. As another lithium source used in step S21, there is lithium carbonate.
[0678] The fluorine source may be a gas, or fluorine, carbon fluoride, sulfur fluoride, or oxygen fluoride may be used, and mixed in the atmosphere in the heating step described later.
[0679] In the present embodiment, lithium fluoride is prepared as a fluorine source, and magnesium fluoride is prepared as a fluorine source and a magnesium source. When lithium fluoride and magnesium fluoride are mixed at LiF:MgF2=65:35 (molar ratio) and thereabouts, it is most effective in lowering the melting point. On the other hand, when there is more lithium fluoride, there is too much lithium and this may cause deterioration in the cycle characteristics. Therefore, the molar ratio of lithium fluoride and magnesium fluoride is preferably LiF:MgF2=x:1 (0≤x≤1.9), more preferably LiF:MgF2=x:1 (0.1≤x≤0.5), and further preferably LiF:MgF2=x:1 (x=0.33 or thereabouts). In addition, in this specification, etc., "nearby" refers to a value greater than 0.9 times and less than 1.1 times its value.
[0680] In addition, the addition amount of magnesium is preferably more than 0.1 atomic% and less than 3 atomic% based on LiCoO2, more preferably more than 0.5 atomic% and less than 2 atomic%, and further preferably more than 0.5 atomic% and less than 1 atomic%. When the addition amount of magnesium is less than 0.1 atomic%, the initial discharge capacity is large, but the discharge capacity decreases sharply with repeated charge and discharge with increased depth of charge. When the addition amount of magnesium exceeds 0.1 atomic% and is less than 3 atomic%, the initial discharge characteristics and charge and discharge cycle characteristics of repeated charge and discharge with increased depth of charge are also good. On the other hand, when the addition amount of magnesium exceeds 3 atomic%, there is a tendency that the initial discharge capacity and charge and discharge cycle characteristics gradually decrease.
[0681] {Step S22}
[0682] Then, in Fig. 23B In step S22 shown in the figure, the magnesium source and the fluorine source are pulverized and mixed. This step can be carried out by selecting the conditions for pulverization and mixing described in step S12.
[0683] In addition, a heating process may be performed after step S22 as necessary. The heating process may be performed by selecting from the heating conditions described in step S13. The heating time is preferably 2 hours or more, and the heating temperature is preferably 800° C. or more and 1100° C. or less.
[0684] {Step S23}
[0685] Then, in Fig. 23B In step S23, the pulverized and mixed materials are collected to obtain a source of the additive element A (source A). The source of the additive element A shown in step S23 includes a plurality of starting materials and can be called a mixture.
[0686] The median particle size (D50) of the particle size of the above mixture is preferably 600 nm or more and 20 μm or less, more preferably 1 μm or more and 10 μm or less. The median particle size (D50) when using one material as the source of the added element A is also preferably 600 nm or more and 20 μm or less, more preferably 1 μm or more and 10 μm or less.
[0687] When the above-mentioned micronized mixture (including the case where the added element A is one) is used, it is easy to uniformly adhere the mixture to the surface of the composite oxide when mixed with the composite oxide in the subsequent process. When the mixture is uniformly attached to the surface of the composite oxide, it is easy to evenly distribute or diffuse fluorine and magnesium to the surface of the composite oxide after heating, so it is preferred. The area where fluorine and magnesium are distributed can also be referred to as the surface part. When there is an area that does not contain fluorine and magnesium in the surface part, it is sometimes not easy to become the above-mentioned O3' type crystal structure in the charged state. Note that fluorine is used for illustration, but chlorine can also be used instead of fluorine, and it can be called a halogen as a substance containing the above-mentioned elements.
[0688] {Other Examples of Step S20 (Step S21 to Step S23)}
[0689] use Fig.23C Description and Fig. 23B Different processes. Fig.23C In step S21 shown in FIG. 1 , four sources of additive elements A to be added to the composite oxide are prepared. That is, Fig.23C The type of source of added element A and Fig. 23B In addition to adding a source of element A, a lithium source can also be prepared.
[0690] As four sources of additive elements A, a magnesium source (Mg source), a fluorine source (F source), a nickel source (Ni source) and an aluminum source (Al source) are prepared. The magnesium source and the fluorine source can be obtained from Fig. 23B As the nickel source, nickel oxide, nickel hydroxide, etc. can be used. As the aluminum source, aluminum oxide, aluminum hydroxide, etc. can be used.
[0691] then, Fig.23C The steps S22 and S23 shown in FIG. Fig. 23B The steps described in are the same.
[0692] {Step S31}
[0693] Then, in Fig.23A In step S31, the composite oxide and the additive element A source (A source) are mixed. The number of atoms of the transition metal M in the composite oxide containing lithium, the transition metal M and oxygen is A. M The number of atoms of magnesium in the added element A Mg The ratio is preferably A M : A Mg =100:y(0.1≤y≤6), more preferably A M : A Mg =100:y(0.3≤y≤3).
[0694] In order not to damage the composite oxide, the mixing of step S31 is preferably performed under milder conditions than the mixing of step S12. For example, it is preferably performed under conditions with fewer rotations or shorter time than the mixing of step S12. In addition, the dry method is a milder condition than the wet method. For example, a ball mill, a sand mill, etc. can be used for mixing. When a ball mill is used, for example, zirconia balls are preferably used as the medium.
[0695] In the present embodiment, the mixing is performed by a dry method at 150 rpm for 1 hour using a ball mill using zirconia balls having a diameter of 1 mm. The mixing is performed in a dry room having a dew point of -100°C or higher and -10°C or lower.
[0696] {Step S32}
[0697] Then, in Fig.23A In step S32, the mixed materials are recovered to obtain a mixture 903. When recovered, the materials may be sieved after being crushed as needed.
[0698] Note that in this embodiment, lithium fluoride used as a fluorine source and magnesium fluoride used as a magnesium source are added to the composite oxide after initial heating. However, one aspect of the present invention is not limited to the above method. A magnesium source and a fluorine source can be added to a lithium source and a transition metal M source at the stage of step S11, i.e., the stage of the starting material of the composite oxide. Then, heating can be performed in step S13 to obtain LiMO2 added with magnesium and fluorine. In this case, there is no need to divide the process into steps S11 to S14 and the process of steps S21 to S23. It can be said that the above method is a simple and highly productive method.
[0699] Alternatively, a composite oxide to which magnesium and fluorine are added in advance may be used. When a composite oxide to which magnesium and fluorine are added is used, the processes of step S11 to step S32 and step S20 may be omitted. The above method can be said to be a simple method with high productivity.
[0700] Alternatively, a magnesium source and a fluorine source or a magnesium source, a fluorine source, a nickel source, and an aluminum source may be further added to the composite oxide to which magnesium and fluorine have been added in advance according to step S20.
[0701] {Step S33}
[0702] Then, in Fig.23A In step S33 shown, the mixture 903 is heated. The heating conditions can be selected from those described in step S13. The heating time is preferably 2 hours or more.
[0703] Here, the heating temperature is supplemented. The lower limit of the heating temperature in step S33 needs to be above the temperature at which the reaction of the composite oxide (LiMO2) and the source of the additive element A progresses. The temperature at which the reaction progresses can be set to the temperature at which the mutual diffusion of LiMO2 and the elements contained in the source of the additive element A occurs, and can also be lower than the melting temperature of the above-mentioned materials. Taking the oxide as an example, it is known that from the melting temperature T m 0.757 times (Taman temperature T d ) solid phase diffusion occurs. Therefore, the heating temperature in step S33 can be set to 500° C. or above.
[0704] Of course, the r...
Claims
1. A power storage system, comprising: Secondary batteries; as well as Differentiator, Wherein, the differentiator includes a register, The differentiator has a function of converting the first voltage of the secondary battery into first voltage data by analog-to-digital conversion, The differentiator has a function of measuring the time required for the first voltage to change by a first voltage value. The register has a function of storing second voltage data having a data value higher than the first voltage data by a data value corresponding to the first voltage value, Furthermore, the differentiator has a function of stopping the supply of power to the register until the first voltage is changed by the first voltage value.
2. The power storage system according to claim 1, The differentiator comprises a digital-to-analog conversion circuit. The digital-to-analog conversion circuit has a function of outputting a second voltage according to the second voltage data, Furthermore, the differentiator has a function of stopping the supply of power to the digital-analog conversion circuit until the first voltage is changed by the first voltage value.
3. The power storage system according to claim 1, The differentiator includes a transistor including an oxide semiconductor in a channel formation region.
4. The power storage system according to claim 2, The differentiator includes a transistor including an oxide semiconductor in a channel formation region.
5. The power storage system according to any one of claims 1 to 4, The secondary battery comprises a positive electrode, The positive electrode comprises lithium cobalt oxide, And the crystal structure identified by X-ray diffraction is a crystal structure represented by space group R-3m.
6. The power storage system according to claim 5, The lithium cobalt oxide contains magnesium in the surface layer.
Citation Information
Patent Citations
Battery state detection device, battery pack incorporated therewith and battery state detection method
JP2010066161A
Semiconductor device for protecting secondary battery and battery pack using the same, and electronic apparatus
JP2010220389A
Semiconductor device
JP2011151383A
Semiconductor integrated circuit
JP2012257187A
Protection monitoring circuit, battery pack, secondary battery monitoring circuit, and protection circuit
US20110267726A1